Method for the economic manufacture of light components
By using magnesium lithium alloy and alloying treatment, combined with 3D printing technology, the problem of light metal alloys being easily oxidized and burned at high temperatures is solved, and the efficient and low-cost manufacturing of lightweight structural components is achieved, and its application performance in structural components is improved.
Patent Information
- Application Number
- JP2024191595
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-07-19
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2038-02-26
AI Technical Summary
The prior art is difficult to manufacture light metal substrate components at high temperatures, and light metal alloys are prone to oxidation and combustion at high temperatures, limiting their application in structural components.
Magnesium lithium alloy is used as a light metal substrate, and magnesium lithium alloy powder with low melting point and high mechanical strength is prepared through alloying treatment. Lightweight structural components are manufactured using 3D printing technology, combining appropriate alloy element ratios and thermal mechanical treatment to improve the environmental resistance and flame resistance of the material.
It realizes the manufacture of lightweight structural components at high temperatures while maintaining high mechanical properties and environmental tolerance, reducing production costs, and expanding the application potential of light metal alloys in structural components.
Smart Images

Figure 2025016646000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to an economical method for manufacturing light metal substrate components. The method is particularly suitable for manufacturing structural components, as it allows for the production of lightweight components with high mechanical properties even at high temperatures. These components can also be manufactured with high environmental and combustion resistance. Intermetallic compounds may also be suitable in certain embodiments of the present invention. Summary of the Invention
[0002] Material properties are undoubtedly one of the main constraints on engineering advances. Materials with high mechanical resistance, along with other properties, are often desirable. For metals, their alloys, and metal-matrix composites, advances in manufacturing methods are often achieved through improved understanding of the effects of alloying. Furthermore, microstructures can be achieved through thermomechanical processing, and more recently through improved manufacturing processes. For mobile structural components, it is often desirable to keep them as light as possible. In many cases, the properties required for a given application are somewhat contradictory. That is, high levels of both properties are required, but increasing one often results in a decrease in the other. In such cases, finding an appropriate compromise is crucial. One well-known example of this is the conflict between properties more or less related to mechanical resistance (wear resistance, penetration resistance, etc.) and toughness-related properties (fracture toughness, elongation, elasticity, etc.). A better compromise between these properties can be achieved, among other things, through the strategies mentioned above. When it comes to metal ductility and damage tolerance or other properties related to the metal substrate, a combination of lightweight construction, component structural design optimization, and materials engineering design is desirable. Many feasible or economically viable designs are limited by the flexibility of available manufacturing methods. When a light metal substrate is desired, alloys of titanium, aluminum, magnesium, lithium, or even very high-strength steels are often utilized. For some applications, it is advisable to optimize the ratio of one dominant mechanical property to density, provided that it is balanced with other mechanical properties. Examples for structural components include yield strength / density, modulus of elasticity / density, modulus of elasticity / density squared, and fatigue strength / density. Surprisingly, very high-density materials can sometimes achieve the optimum ratio, often resulting in weight savings through thinner component wall thickness. In some applications, excessive thinning is less useful, especially when the building flexibility of molding techniques such as additive manufacturing (AM) and MIM is available. In these cases, and when lightweight construction is desired, the density of the material utilized becomes even more important. Indeed, AM technologies include a wide variety of techniques, such as i) binder jetting, ii) directed energy deposition, iii) material extrusion, iv) material jetting, v) powder bed fusion, vi) sheet lamination, and vii) vat photopolymerization. This classification summarizes a wide variety of techniques, including, but not limited to, 3D printing, inkjet, S-print, and M-print technologies, techniques in which focused energy creates a molten pool onto which the feedstock (powder or wire material) is deposited using a laser (laser deposition and laser solidification), arc or electron beam heat sources (direct metal deposition and direct electron beam melting), fused deposition modeling (FDM), material jetting, direct metal laser sintering (DMLS), selective laser melting (SLM), electron beam melting (EBM), selective laser sintering (SLS), stereolithography, and digital light processing (DLP). Building very light structures, such as in the case of microlattices, can require the feasibility of building very thin walls, on the order of tens of nanometers, which is currently limited to a limited number of metallic materials that can be electrodeposited. Lightweight construction often comes at a higher cost, which can be an obstacle to wider implementation. Cost is often a strong driver for the implementation of a particular technology. For some lightweight components, not only mechanical properties but also environmental resistance must be considered. Most light alloys are highly reactive to oxygen (often even more so at high temperatures) and many other agents. This is often a significant drawback for their applications. Also, the tendency of light metal alloys to burn when exposed to flame can be a major obstacle to their application. Lithium, magnesium, and their alloys are among the lightest metal alloys with very useful mechanical properties, but unfortunately, their strong reactions with oxygen and nitrogen at very low temperatures make their applications difficult. For structural or other types of components that require high modulus of elasticity at high temperatures, environmental resistance, and good creep resistance, some intermetallic compounds (such as gTiAl) can be very suitable candidates. However, they also exhibit low-temperature brittleness, making them very difficult to form into complex shapes. Also, some intermetallic compounds have particularly slow impurity diffusion rates, making the diffusion involved in joining components somewhat difficult. For applications requiring high stiffness, mechanical strength, and energy absorption in a crash, reinforced polymers are often a good technical solution. Some of the obstacles relate to cost, anisotropy, reliability (e.g., due to degradation of properties over long-term environmental conditions), electrical and thermal conductivity, and in some cases, compressive and fatigue (depending on loading mode) performance. As mentioned, there are different loading scenarios regarding the main loads of the structural components. There are also many components that benefit from high performance and light weight, which can benefit from the application of the present invention. The following are just a few examples: mechanical strength, modulus of elasticity, yield strength, environmental resistance, oxidation resistance at high temperatures, creep resistance, compression resistance, yield under compression, fatigue strength, energy absorption capacity in a crash, electrical conductivity, dielectric properties, thermal conductivity, etc., which can be relevant for different applications and can rarely be maximized all at once, so an optimal compromise is recommended. In application design, the present invention may contribute to improving the weight-to-performance ratio, and the combination of substrates with different properties may be useful. The present invention allows for the production of parts that are inexpensive and have a good weight-to-performance ratio, and also allows for better utilization of the properties of different materials, especially when at least some metal or intermetallic compounds are involved. Current state of the art The production of metal components has always been a challenge for additive manufacturing technologies, with poor mechanical properties and high costs continually cited as major obstacles to their deployment. Bampton et al. (US Pat. No. 5,745,834) reported an invention for freeform fabrication of metal components using selective laser bonding by transient liquid sintering of mixed powders. The mixed powder used in that invention includes a base metal or base metal alloy (75-85%), a low-melting-point metal alloy (5-15%), and a polymer binder (5-15%). The base metals considered include metallic elements such as nickel, iron, cobalt, copper, tungsten, molybdenum, rhenium, titanium, and aluminum. Regarding low-melting-point metal alloys, they can be selected from base metals containing melting-point depressants (boron, silicon, carbon, or phosphorus) to lower the melting point of the base alloy by approximately 300-400°C. The SLS method considered in this invention, as well as other powder-based AM technologies, strongly depend on the powder properties. Similar to the invention reported by Pfeifer & Shen in U.S. Patent Application Publication No. 2006 / 0251535 A1, plastic, metal, or ceramic particles can be coated with a particulate material that can bond and sinter, or form glass. In that patent application, the particulate material (submicrometer or nanoparticles of plastic, metal, or ceramic) is coated with an organic or organometallic polymeric compound that exhibits low hydrophilicity and accounts for the temperature difference when the powder material is heated to 100°C. In the case of metal powder materials, the particulate material is preferably formed from a metal or alloy composed of the elements Cu, Sn, Zn, Al, Bi, Fe, or Pb. Activation of the adhesive can occur by laser irradiation designed to sinter, or at least partially melt, the powder particles by forming glass bridges between adjacent powder particles. If the heat treatment is performed below the glass-forming or sintering temperature of the powder material, substantially no sintering shrinkage of the whole or green compact occurs. Green components can also be obtained by other 3D printing techniques, such as the work by Walter Lengauer in DE102013004182 on printing paints for direct FDM printing.Print coatings are composed of one or more polymeric organic binder components and inorganic powder components consisting of metals, hard materials including binder metals, or ceramic materials. The resulting green compact can then be subjected to a sintering process to produce the final part. FDM processes and other variations of 3D printing, such as direct metal machining, are limited in the resolution and size of components. In this regard, Canzona et al. (US2005 / 0191200 A) presented a direct metal manufacturing method for forming metal parts with a relative density of at least 96%. The powder mixture presented in that study consisted of a base alloy, a powdered low-melting-point alloy, and two organic polymer binders (thermoplastic and thermosetting organic polymers). This powder blend can be used in other powder-bed-related processes, such as selective laser sintering, which involves supersolidus liquid-phase sintering. As in the work published by Bampton, low-melting-point alloys were produced by incorporating small amounts of boron as a eutectic-forming element into the alloy. Scandium was also considered as a eutectic-forming element. Additive manufacturing of ceramic parts, which is done by laser stereolithography polymerization of ceramic particle-filled resins, can only produce small parts, as large parts in particular are prone to cracking. The thermosetting polymer binder hardens before the thermoplastic binder remelts, providing critical support for the compact shape while heating to temperatures where metal-to-metal powder sintering (neck formation at powder contact points) begins, enhancing the compact's strength. Description of the invention To achieve the very light structures desired in many applications at an economical price, it is often very interesting to combine the properties of different materials, and very often combinations involving metals are optimal. In some applications, monometallic structures may also be worth considering if the alloying system is appropriate. Also, the greater the design freedom, the greater the potential for weight optimization. However, customarily, this design freedom must come at the expense of cost. Additive manufacturing (AM) has evolved dramatically in recent years and become relatively inexpensive over the past few decades. However, the most advanced and cost-effective AM technologies enable manufacturing using polymers. Materials that combine the properties of metals and polymers, such as reinforced polymer composites, may be worth considering. Manufacturing methods for metal alloys, which offer greater design flexibility, are typically incompatible with the low decomposition temperatures of polymers. For this reason, some focus has been placed on developing methods for manufacturing complex geometries using metal alloys, yet still well below their melting points. Of all the light metal alloys of potential or relevant engineering applications, the inventors have discovered that a very interesting combination of properties can be achieved with magnesium alloys. Their melting points are very high compared to the decomposition temperatures of most polymers, making them a seemingly impossible combination. Magnesium and most of its known alloys react very violently with oxygen and with numerous other agents. This tendency to corrosion is a hindrance in many applications. They also tend to burn with a fairly high exotherm, a very detrimental property in many applications. Furthermore, many magnesium alloys are very difficult to weld, which, compared to others, makes them a hindrance in many structural applications. Therefore, despite their low density and relatively high abundance, magnesium alloys are used in relatively few applications. Although lithium is much lighter than magnesium, its significantly lower modulus makes it a major obstacle as a structural component, and it is more reactive with oxygen than magnesium. Magnesium-lithium alloys are lighter than magnesium alloys. Surprisingly, when the alloying is properly selected, it is possible to achieve suitable elastic modulus values, an order of magnitude larger than those of structural magnesium and aluminum alloys. Unfortunately, lithium exacerbates some of the important drawbacks of magnesium alloys, particularly in terms of corrosion, oxidation, tendency to burn, and difficulty of welding. Magnesium alloys containing large amounts of lithium may have a lower melting point, but the elastic modulus, mechanical strength, and especially creep resistance values are clearly too low for structural applications, or for almost any type of application. We found that magnesium alloys can be processed at low enough temperatures to allow polymers to retain their shape, even when they offer a good balance of mechanical properties, including high modulus of elasticity, mechanical strength, and creep resistance, especially when normalized (i.e., the property value divided by the alloy's density). Even more surprisingly, the alloys exhibit good environmental and combustion resistance. Lithium alloys with significantly higher magnesium content, when properly alloyed and processed, can also achieve this surprising behavior while exhibiting very low densities. This system allows the particles to be solidified at temperatures much lower than the melting point of magnesium. In certain embodiments, it has been found that at least two types of particulate magnesium alloys are worthy of consideration. In certain embodiments, it is worthy of consideration to have at least one particulate magnesium alloy containing lithium. In other embodiments, it is recommended that at least one of the particulate magnesium alloys containing lithium contains more than 36 wt.%, or more than 42 wt.%, or more than 52 wt.%, or more than 62 wt.%, or more than 72 wt.%, or more than 81 wt.% lithium. Furthermore, it has been found that in certain embodiments, it is worthy of consideration to have at least one particulate magnesium alloy having a sufficiently low melting point (unless otherwise specified, the melting point is defined herein as the temperature at which liquefaction begins). In various embodiments, at least one of the particulate magnesium alloys has a melting point less than 390°C, less than 340°C, less than 290°C, less than 240°C, or even less than 190°C. Test conditions are listed at the end of this specification. Melting points were measured in accordance with ASTM E794-06 (2012). Alternatively, a technical expert reproducing this disclosure may, at his or her discretion, obtain melting points using thermogravimetry or any other characterization technique. Typical deviations in the determination of this temperature are not significant, so the temperature determined by the solidus of the corresponding phase diagram is a sufficient approximation, as are temperatures determined by CALPHAD-type software, including Thermo-Calc, the latest version of which was available as of January 27, 2017 (Thermo-Calc 2016b, released in November 2016). Alternatively, a technical expert reproducing this disclosure may, at his or her discretion, obtain melting points using thermogravimetry or other characterization techniques, or even experimentally determine this temperature in the simplest way by DSC, DTA, or DTA using STA. Certain embodiments refer to magnesium alloys having the following compositions, expressed as weight percentages: %Si:0‐15; %Cu:0‐30; %Mn:0‐15; %Be:0‐15; %Zn:0‐15; %Li:0.6‐70; %Sc:0‐20; %Fe<30; %Pb:0‐10; %Zr:0‐10; %Cr:0‐15; %V:0‐10; %Ti:0‐20; %Bi:0‐20; %Ga:0‐20; %N:0‐2; %B:0‐5; %Al:0‐60; %Ni:0‐40; %Mo:0‐15; %W:0‐30; %Ta:0‐5; %Hf:0‐5; %Nb:0‐10; %Co:0‐30; %Ce:0‐15; %Ge:0‐20; %Ca:0‐15; %In:0‐20; %Cd:0‐20; %Sn:0‐40; %Cs:0‐20; %Se:0‐10; %Te:0‐10; %As:0‐10; %Sb:0‐20; %Rb:0‐20; %La:0‐15; %C:0‐5; %O:0‐15; %Y:0‐30; %Nd:0‐30; %Tm:0‐15; %Tb:0‐15; %Gd: 0 - 20; %Dy: 0 - 15; %Yb: 0 - 15; %Er: 0 - 15; %Sm: 0 - 15; %Pr: 0 - 15; %Ho: 0 - 25; %Lu: 0 - 15; %Th: 0 - 15; In the above formula, %Gd + %Nd + %Sm + %Y + %Pr + %Sc + %Pm + %Eu + %Tb + %Dy + %Ho + %Er + %Tm + %Yb + %Lu + %Th = 0.002 - 34; and %Zr + %Zn + %Mn + %Y + %Ce + %La + %Ca + %Sc = 0.002 - 34 The remainder is composed of magnesium and trace elements, with %Mg > 12%. Needless to say, the composition can only be added up to 100%, which is an obvious condition and thus not included as a condition. Accordingly, compositions within a range where the total exceeds 100% are automatically excluded. (In certain embodiments, the conditions are as follows. In applications with little significance in alloys in which elements beyond atomic number 103 are disclosed, in the above formula, %H + %He + %Li + “….“ + %Md + %No + %Lr <= 100%. Here, “….” represents the sum of elements in the periodic table with atomic numbers 4 - 100.) (In certain embodiments, the above conditions are also as follows. Characterized by the sum of all elements up to atomic number 118 being equal to 100%.) Needless to say, elements starting with a range of 0 or elements with a composition range expressed as (%Element < XX.X) are optional and generally mean that such elements are not included in general situations. For example, when the composition range is %Cu = 0 - 30% and %Fe < 30 wt% by weight, there are many embodiments where neither %Fe nor %Cu are present, and many embodiments where they are not intentionally added. (Therefore, this standard composition represents 0% or the absence of that element. However, these may exist as trace elements depending on the purity of the scrap, or contamination of alloying elements, dissolution recipients, and other possible sources of contamination during the production of the alloy.) There will also be many embodiments where only one is absent or undesirable while the other is not. What is exemplified by %Fe and %Cu is applicable to any other element. The nominal composition expressed herein may refer to the general final composition of particles or alloys with higher volume fractions. The presence of immiscible particles, such as ceramic reinforcements (especially particles, fibers, whiskers, etc.), graphene, nanotubes (often carbon nanotubes), and fibers (SiC, SiN, carbon, aramid, basalt, glass, etc.), does not qualify as a nominal composition. In aspects and embodiments where high-diffusivity or low-melting-point particles are used, some significant embodiments may be able to select within this composition range, but as described later in this specification, this is often not the case. As described later in this specification, some components are manufactured using materials containing shaped organic and inorganic portions. In some embodiments, the above composition, with potential limitations discussed in the next paragraph, refers to the overall general composition of the metallic phases contained in the inorganic portion of the material. The above composition, with potential limitations discussed in the next paragraph, refers to the overall general composition of all metallic phases contained in the inorganic portion of the material. Some embodiments also include %Mg>12%, %Mg>22%, and %Mg>62% by weight. In another embodiment, the above composition, with the potential limitations described in the next paragraph, refers to particles of the metal phase that have the highest volume fraction at the moment when the polymer (where the organic portion of the material includes the polymer) is filled with the metal phase. In one embodiment, the above composition, with the potential limitations described in the next paragraph, refers primarily to particles of the metal that have the highest volume fraction at the moment when the organic portion of the material is filled with different particles and reinforcements. Unless otherwise specified, trace elements refer to several elements, including, but not limited to, H, He, Xe, F, Ne, Na, P, S, Cl, Ar, K, Br, Kr, Sr, Tc, Ru, Rh, Pd, Ag, I, Ba, Pm, Eu, Re, Os, Ir, Pt, Au, Hg, Tl, Po, At, Rn, Fr, Ra, Ac, Pa, U, Np, Pu, Am, Cm, Bk, Cf, Es, Fm, Md, No, Lr, Rf, Db, Sg, Bh, Hs, and Mt, unless the context clearly indicates otherwise. For some applications, we have found it important to limit the trace element content, singly or compositionally, to less than 1.8%, 0.8%, 0.1%, or even 0.03% by weight. In some embodiments, an element present as an undesirable impurity is a trace element. Trace elements may be intentionally added to an alloy to achieve a specific function, such as reducing the cost of producing the alloy, or their presence may be unintentional and primarily related to the presence of impurities in the alloying elements and scrap used in producing the alloy. In some applications, the presence of trace elements is detrimental to the overall properties of the magnesium-based alloy. In other embodiments, the combined content of all trace elements is preferably less than 2.0%, less than 1.4%, less than 0.8%, less than 0.2%, less than 0.1%, or even less than 0.06% by weight. In other embodiments, for some applications, the absence of trace elements in the magnesium alloy (which is generally referred to herein as a magnesium alloy, even if magnesium is not the primary alloying element of the alloy) is desirable. In some applications, the presence of alkali or halogen elements may adversely affect mechanical properties. In another embodiment, the content of %F, %Cl, %Br, or %At, individually or in total, is preferably less than 210 ppm by weight, less than 140 ppm by weight, less than 110 ppm by weight, less than 90 ppm by weight, less than 40 ppm by weight, or absent. In another embodiment, the content of %Na, %K, %Rb, or %Cs, individually or in total, is preferably less than 180 ppm by weight, less than 74 ppm by weight, less than 36 ppm by weight, less than 12 ppm by weight, less than 8 ppm by weight, less than 2.8 ppm by weight, less than 0.7 ppm by weight, less than 0.4 ppm by weight, less than 0.009 ppm by weight, less than 0.001 ppm by weight, or absent. Magnesium alloys benefit from a high magnesium (%Mg) content, but magnesium need not be the major component of the alloy to balance mechanical properties. In other embodiments, %Mg greater than 12 wt%, 21 wt%, 33 wt%, 42 wt%, 52 wt%, 69 wt%, 78 wt%, or even 87 wt% is recommended. In other embodiments, it is necessary to control the total %Mg content to ensure it is not excessive. It has been discovered that excessive total %Mg can result in an undesirable compromise between corrosion resistance and mechanical properties. In other embodiments, %Mg less than 94 wt%, 88 wt%, 79 wt%, 68 wt%, 48 wt%, 41 wt%, 38 wt%, 24 wt%, or even 18 wt% is recommended. Some applications of magnesium alloys can benefit from a high lithium (%Li) content. In some embodiments, %Li can help improve some of the alloy's mechanical properties. Surprisingly, when properly combined with other alloying elements, %Li contributes to an increase in the ratio of (elastic modulus * elongation at break / density). Even more surprisingly, this is a simultaneous increase in elastic modulus and elongation at break. As discussed below, this ultimately determines whether the aspect is properly implemented. In some embodiments, %Li may be the dominant element in the alloy. Therefore, the alloy should ultimately be considered strictly a lithium alloy, rather than a magnesium alloy or magnesium-lithium alloy. As discussed below, %Li contents greater than 10 wt.% are typically used only to at least partially cube the alloy for improved formability. For this reason, it generally makes no sense to produce powders with such high %Li contents due to the near-net-shape nature of the powder metallurgy process. However, as discussed below, surprisingly, in some embodiments, it makes perfect sense to produce particulate magnesium alloys with high %Li contents. In other embodiments, %Li is recommended to be greater than 0.6 wt%, 1.2 wt%, 2.3 wt%, 4.2 wt%, 5.2 wt%, 6.9 wt%, 7.8 wt%, or even 8.7 wt%. Higher %Li contents are recommended in some embodiments to further emphasize the aforementioned properties and in some applications where special care is taken to further minimize corrosion. In other embodiments, %Li is recommended to be greater than 9.6 wt%, 10.2 wt%, 11.2 wt%, 12.2 wt%, 14.2 wt%, 16 wt%, 18 wt%, or even 26 wt%. As mentioned above, %Li can be the majority element in some embodiments. In other embodiments, %Li is recommended to be greater than 36 wt%, 42 wt%, 52 wt%, or even 62 wt%. In some embodiments, it is necessary to control to ensure that the total amount of %Li is not excessive. It has been discovered that if the total amount of %Li is excessive, an undesirable compromise between corrosion resistance and mechanical properties may occur.In other embodiments, it is recommended that %Li be less than 44 wt%, less than 18 wt%, less than 14.8 wt%, less than 11.9 wt%, less than 9.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.8 wt%, or even less than 0.9 wt%. In certain embodiments, it has been discovered that in embodiments optimizing alloy properties when %Li is between 6.9 wt% and 25.1 wt%, it is recommended that at least one of %Ca, %Zr, %Al, or %Zn be present in the alloy. In certain other embodiments, it has been discovered that in embodiments optimizing alloy mechanical properties when %Li is between 4.9 wt% and 16.1 wt%, it is recommended that at least one of %Al, %Zr, %Zn, or %Ca be present in the alloy. In some embodiments, when %Li is less than 5.1 wt%, it is recommended that at least one of %Ca or %Zr be present in the alloy. It has been discovered that in embodiments optimizing the mechanical properties of alloys when %Li is between 10.4 wt% and 16.1 wt%, it is recommended that at least one of %Zr, %Zn, or %Ca be present in the alloy. In some embodiments, in embodiments optimizing the mechanical properties of alloys when %Li is between 1.9 wt% and 20.1 wt%, it is recommended that at least one of %Al or %Zr be present in the alloy, or that %REE be greater than 600 ppm by weight. In some embodiments, in embodiments optimizing the mechanical properties of alloys when %Li is less than 12.1 wt%, it is recommended that at least one of %Al, %Zr, or %Ca be present in the composition. In some embodiments, in embodiments optimizing the mechanical properties of alloys when %Li is less than 7.1 wt%, it is recommended that at least one of %Ca or %Zr be present in the composition. In embodiments where an optimum compromise in mechanical properties of the alloy is sought when %Li is less than 10.1 wt%, it is recommended that at least one of %Ca, %Zr, %Al, %Zn, or %REE be present in the alloy.It has also been discovered that in other applications, when %Li is less than 55.6 wt%, at least one of %Y or %Sc is included as a compositional element of the alloy in separate embodiments, and is recommended to be greater than 0.006 wt%, 0.01 wt%, 0.3 wt%, or even 1.1 wt% individually or in total. In embodiments related to mechanical properties when %Li is less than 30.6 wt%, it is recommended that at least one of %Y, %Sc, or %Zr be present in the alloy. In yet another embodiment, it is recommended that they be greater than 0.08 wt%, 0.6 wt%, or even 1.1 wt% individually or in total. In another embodiment, when %Li is less than 26.6 wt%, the above values for %Y, %Sc, or %Zr are preferred. In embodiments related to mechanical properties when %Li is less than 26.6 wt%, it is recommended that at least one of %Ca, %Y, or %Sc be present in the alloy. In other embodiments, it is recommended that they be present individually or in total in amounts greater than 0.01%, greater than 0.1%, greater than 0.6%, or even greater than 1.2% by weight. Rare earth elements (%REE) refer to the set of 17 chemical elements, 15 lanthanides, and scandium and yttrium in the periodic table. In some embodiments, it has been discovered that the inclusion of %REE in the alloy is recommended. In other embodiments, it is recommended that the %REE be greater than 600 ppm by weight, greater than 0.01% by weight, or even greater than 0.1% by weight. In other embodiments, it is recommended that the %REE be included in the alloy when %Li is less than 5.1% by weight. In other embodiments, it is recommended that the %REE be included in the alloy when %Li is less than 30.6% by weight, or when %Li is less than 26.6% by weight. In other embodiments, it is recommended that the %REE be at least 10 ppm by weight, at least 100 ppm by weight, at least 0.01% by weight, at least 0.16% by weight, or even at least 0.6% by weight. In some embodiments, it has been discovered that the presence of at least one of %Ce, %La, and %Y among the %REE is desirable to improve mechanical properties. It has been discovered that in some embodiments, it is desirable to have at least one of the %Nd or %Gd present in the %REE to improve mechanical properties. In embodiments where %Li is between 6.9% and 25.1%, it is recommended that at least one of the %REE be present in the alloy to improve mechanical properties. In some embodiments, at least one of the %REE %Gd, %Nd, or %Y is included. In other embodiments, at least %Gd, or at least %Y, or at least %Nd is included in the %REE. Some applications of magnesium alloys benefit from a high aluminum (%Al) content. In some embodiments, %Al helps increase the cost-effectiveness of the alloy. In other embodiments, %Al helps enhance the alloy's mechanical properties. In some embodiments, %Al contributes to improved creep resistance, especially when properly formulated with other alloying elements. In some embodiments, %Al contributes to improved corrosion resistance, especially when properly formulated with other alloying elements. %Al may contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Al is the major element in the alloy. This may ultimately result in the alloy being strictly considered an aluminum alloy or an aluminum-lithium alloy. In other embodiments, %Al is recommended to be greater than 0.06 wt%, greater than 0.6 wt%, greater than 1.2 wt%, greater than 2.2 wt%, greater than 3.2 wt%, greater than 5.3 wt%, greater than 7.8 wt%, or even greater than 10.1 wt%. Higher %Al contents are recommended in some embodiments to further enhance the aforementioned properties. In other embodiments, %Al is recommended to be greater than 11.2 wt%, greater than 12.2 wt%, greater than 14.2 wt%, greater than 15.2 wt%, greater than 16 wt%, greater than 18 wt%, or even greater than 26 wt%. As previously mentioned, %Al can be the major element in the alloy in some embodiments. In other embodiments, %Al is recommended to be greater than 36 wt%, greater than 42 wt%, or even greater than 52 wt%. In some embodiments, it is necessary to control the total %Al to ensure that it is not excessive. It has been discovered that excessive total %Al can result in an undesirable compromise between corrosion resistance and mechanical properties. In other embodiments, %Al is recommended to be less than 44 wt%, less than 18 wt%, less than 14.8 wt%, less than 11.9 wt%, less than 9.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.2 wt%, or even less than 0.8 wt%. In other embodiments, %Al is absent or present as an undesirable impurity. There are applications in which magnesium alloys benefit from a high lanthanum (%La) content. %La helps facilitate strengthening of the alloy. This result is surprising, especially since the same is true for some alloys containing %Y. Therefore, alloys containing %La in particulate form, which is generally not very meaningful, can be meaningful in some embodiments. In fact, we have discovered that if the particles are metal powders and properly manufactured with a high %La content, it is possible to find it in solid solution more than in bulk alloys of the same composition. This is a major obstacle for many applications, but it can also be very useful for some magnesium alloy applications. Magnesium-based alloys containing %La are manufactured in particulate form. In another embodiment, the alloy contains 5 wt.% or more more %La in solid solution than the equilibrium solid solubility of %La in the alloy at room temperature (23°C and 1 atm) (e.g., if the maximum equilibrium solid solubility of %La in a magnesium alloy at room temperature, 23°C, and 1 atm is 0.01 wt.%, then the alloy in particulate form will have at least 0.0105 wt.% %La in solid solution). Alternatively, the %La content may be 12 wt.% or more, 26 wt.% or more, 36 wt.% or more, 56 wt.% or more, 116 wt.% or more, or 216 wt.% or more (methods for appropriately preparing alloys in particle form to achieve higher values of alloying elements in solid solution are described herein). In some alloys, it may be more appropriate for some applications to control the %La in solid solution in constant terms. In other embodiments, the %La content in solid solution of alloys prepared in particle form may be 0.001 wt.% or more, 0.006 wt.% or more, 0.015 wt.% or more, or even 0.03 wt.% or more. In some embodiments, the %La contributes to improved mechanical properties. In some embodiments, especially when properly combined with other alloying elements, the %La contributes to improved mechanical resistance. In some embodiments, especially when properly combined with other alloying elements, the %La contributes to improved corrosion resistance. In some applications, the %La may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, the %La has a positive effect on the %Li.In other embodiments, %La is greater than 0.06 wt%, greater than 0.6 wt%, greater than 1.2 wt%, greater than 2.2 wt%, greater than 3.2 wt%, greater than 5.3 wt%, greater than 7.8 wt%, or even greater than 10.1 wt%. Higher %La contents are recommended in different embodiments to further enhance the aforementioned properties. In other embodiments, %La is greater than 11.2 wt%, greater than 12.2 wt%, or even greater than 13.2 wt%. In some embodiments, it is necessary to ensure that the total %La content is not excessive. It has been discovered that excessive total %La can result in an undesirable compromise between corrosion resistance and mechanical properties. In other embodiments, it is recommended that %La be less than 11.9 wt%, less than 9.8 wt%, less than 8.8 wt%, less than 6.9 wt%, less than 5.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.2 wt%, or even less than 0.8 wt%. In other embodiments, %La is absent or present as an undesirable impurity. There are applications in magnesium alloys that benefit from a high scandium (%Sc) content. %Sc helps facilitate alloy strengthening. This result is surprising, especially since this is also the case for some alloys containing %Y. Therefore, alloys containing %Sc in particulate form, which is generally not meaningful, can be meaningful in some embodiments. In fact, we have discovered that if the particulates are metal powders and properly manufactured with a high %Sc content, they can be found in solid solution more than in bulk alloys of the same composition. While this presents a significant obstacle for many applications, it can also be very useful for some magnesium alloy applications. Magnesium-based alloys containing %Sc are manufactured in particulate form. In other embodiments, the %Sc content in solid solution is 5% or more higher than the equilibrium solubility of %Sc in the alloy at room temperature, 23°C, and 1 atm, or 12% or more, 26% or more, 56% or more, 116% or more, or 216% or more. In some alloys, controlling the %Sc in solid solution with a constant term may be more appropriate for some applications. In other embodiments, the %Sc content in the solid solution of the alloy produced in particle form is 12.2 wt.% or more, 12.6 wt.% or more, 14.4 wt.% or more, or even 17.5 wt.% or more. In some embodiments, %Sc contributes to improving some mechanical properties. In other embodiments, %Sc contributes to improving mechanical resistance. In some embodiments, %Sc contributes to improving creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Sc contributes to improving corrosion resistance, especially when properly combined with other alloying elements. %Sc may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Sc has a positive effect on %Li. In other embodiments, %Sc is greater than 0.06 wt.%, greater than 0.6 wt.%, greater than 1.2 wt.%, greater than 2.2 wt.%, greater than 3.2 wt.%, greater than 5.3 wt.%, greater than 7.8 wt.%, or even greater than 10.1 wt.%. Higher %Sc contents are recommended in different embodiments to further enhance the aforementioned properties. In other embodiments, %Sc is greater than 11.2 wt%, greater than 12.2 wt%, greater than 13.2 wt%, greater than 15.2 wt%, or even greater than 17.2 wt%.In some embodiments, it is necessary to ensure that the total %Sc is not excessive. It has been discovered that excessive %Sc can lead to undesirable compromises between corrosion resistance and mechanical properties. The use of %Sc, while potentially achieving significant mechanical properties, is an example of many other high-cost alloying elements (in some embodiments, this is considered high cost according to the following examples: >23$ / Kg, >102$ / Kg, >252$ / Kg, >520$ / Kg, or even >1020$ / Kg). However, this cost must be considered from an economic perspective to use the amount required for the desired application. In other embodiments, it is recommended that %Sc be less than 14.8wt%, 11.9wt%, 9.8wt%, 8.8wt%, 6.9wt%, 5.8wt%, 4.1wt%, 2.8wt%, 1.2wt%, or even 0.8wt%. In other embodiments, %Sc is absent or present as an undesirable impurity. There are applications in magnesium alloys that benefit from a high lanthanum and scandium (%La + %Sc) content. %La + %Sc helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. Therefore, alloys containing %La + %Sc in particle form, which is generally not meaningful, can be meaningful in certain embodiments. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %La + %Sc content, they can be found in solid solution more easily than bulk alloys of the same composition. %La + %Sc contributes to improved mechanical properties. In certain embodiments, %La + %Sc contributes to improved creep resistance, especially when properly formulated with other alloying elements. In certain embodiments, %La + %Sc contributes to improved corrosion resistance, especially when properly formulated with other alloying elements. %La + %Sc may also contribute as a ternary element to many of the properties mentioned for other alloying elements. In certain embodiments, %La + %Sc has a favorable effect on %Li. In other embodiments, %La + %Sc is comprised greater than 0.06 wt%, greater than 0.6 wt%, greater than 1.2 wt%, greater than 2.2 wt%, greater than 3.2 wt%, greater than 5.3 wt%, greater than 7.8 wt%, or even greater than 10.1 wt%. Even higher %La + %Sc contents are recommended in different embodiments to further enhance the aforementioned properties. In other embodiments, %La + %Sc is comprised greater than 11.2 wt%, greater than 16.2 wt%, greater than 21.2 wt%, greater than 25.2 wt%, or even greater than 31.2 wt%. In some embodiments, it is necessary to ensure that the total amount of %La + %Sc is not excessive. It has been discovered that if the total amount of %La + %Sc is excessive, an undesirable compromise between corrosion resistance and mechanical properties may occur. In other embodiments, it is recommended that %La+%Sc be less than 28.8 wt%, less than 18.9 wt%, less than 9.8 wt%, less than 8.8 wt%, less than 6.9 wt%, less than 5.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.2 wt%, or even less than 0.8 wt%. In other embodiments, %La+%Sc is either absent or present as an undesired impurity. Magnesium alloys have applications that benefit from a high calcium (%Ca) content. In some embodiments, %Ca contributes to improved mechanical properties. In some embodiments, %Ca contributes to improved creep resistance, especially when properly formulated with other alloying elements. In some embodiments, %Ca contributes to improved corrosion resistance, especially when properly formulated with other alloying elements. %Ca may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Ca has a positive effect on %Li. In other embodiments, %Ca is greater than 0.06 wt%, greater than 0.1 wt%, greater than 0.6 wt%, greater than 1.2 wt%, greater than 2.2 wt%, greater than 3.2 wt%, greater than 5.3 wt%, greater than 7.8 wt%, or even greater than 10.1 wt%. Even higher %Ca contents are recommended in different embodiments to further enhance the aforementioned properties. In other embodiments, %Ca is greater than 11.2 wt%, greater than 12.2 wt%, or even greater than 13.2 wt%. In some embodiments, it is necessary to ensure that the total amount of %Ca is not excessive. It has been discovered that excessive %Ca can lead to undesirable compromises between corrosion resistance and mechanical properties. In other embodiments, it is recommended that %Ca be less than 11.9 wt%, less than 9.8 wt%, less than 8.8 wt%, less than 6.9 wt%, less than 5.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.2 wt%, or even less than 0.8 wt%. In some embodiments, it has been discovered that the presence of at least one of %Ca, %Zr, %Al, or %Zn in the alloy is recommended for improved mechanical properties. When %Li is less than 56.6 wt%, in other embodiments, it is recommended that the presence of %Ca be greater than 0.01 wt%, greater than 0.2 wt%, or even greater than 0.9 wt%. When %Li is less than 30.6 wt%, it is recommended that the presence of %Ca be greater than 100 ppm by weight, greater than 0.16 wt%, or even greater than 0.8 wt%. Also, in some embodiments, %Ca is either absent or present as an undesirable impurity. Some applications of magnesium alloys benefit from a high beryllium (%Be) content. %Be helps facilitate alloy strengthening. This result is surprising, especially since this is also the case for some alloys containing %Y. Therefore, alloys containing %Be in particulate form, which is generally not very meaningful, can be meaningful in some embodiments. In fact, we have discovered that if the particles are metal powders and properly manufactured with a high %Be content, they can be found in solid solution more easily than in bulk alloys of the same composition. While this presents a significant obstacle for many applications, it can also be very useful for some magnesium alloy applications. Magnesium-based alloys containing %Be are manufactured in particulate form. In other embodiments, the %Be content in solid solution is 5% or more higher than the equilibrium solubility of %Be in the alloy at room temperature (23°C) and 1 atm, or 12% or more, 26% or more, 56% or more, 116% or more, or 216% or more. In some applications, controlling the %Be in solid solution with a constant term is more appropriate for some alloys. In other embodiments, the %Be contributes to improving certain mechanical properties. In some embodiments, %Sc contributes to improved creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Be contributes to improved corrosion resistance, especially when properly combined with other alloying elements, in some applications. %Be may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Be has a positive effect on %Li. In other embodiments, %Be is greater than 0.06 wt%, greater than 0.6 wt%, greater than 1.2 wt%, greater than 2.2 wt%, greater than 3.2 wt%, greater than 5.3 wt%, greater than 7.8 wt%, or even greater than 10.1 wt%. Even higher %Be contents are recommended in different embodiments to further enhance the aforementioned properties. In other embodiments, %Be is greater than 11.2 wt%, greater than 12.2 wt%, or even greater than 13.2 wt%. In some embodiments, it is necessary to ensure that the total %Be content is not excessive. It has been discovered that excessive total %Be can result in an undesirable compromise between corrosion resistance and mechanical properties.In other embodiments, %Be is recommended to be less than 11.9 wt%, less than 9.8 wt%, less than 8.8 wt%, less than 6.9 wt%, less than 5.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.2 wt%, or even less than 0.8 wt%. In other embodiments, %Be is absent or present as an undesirable impurity. There are applications in which magnesium alloys benefit from a high yttrium (%Y) content. In some embodiments, %Y contributes to improved mechanical properties. In other applications, %Y contributes to improved corrosion resistance, especially when properly combined with other alloying elements. %Y may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Y has a positive effect on %Li. In other embodiments, %Y is greater than 0.06 wt%, greater than 0.6 wt%, greater than 1.2 wt%, greater than 2.2 wt%, greater than 3.2 wt%, greater than 5.3 wt%, greater than 7.8 wt%, or even greater than 10.1 wt%. Even higher %Y contents are recommended in different embodiments to further enhance the aforementioned properties. In other embodiments, %Y is greater than 11.2 wt%, greater than 16.2 wt%, greater than 21.2 wt%, or even greater than 25.2 wt%. In some embodiments, it is necessary to control the total amount of %Y to ensure it is not excessive. It has been discovered that excessive total %Y can result in an undesirable compromise between corrosion resistance and mechanical properties. In another embodiment, it is recommended that %Y be less than 28.8 wt%, less than 18.8 wt%, less than 14.9 wt%, less than 9.8 wt%, less than 8.8 wt%, less than 6.9 wt%, less than 5.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.2 wt%, or even less than 0.8 wt%. It has been discovered that when producing magnesium alloys in particulate form containing %Y, if the particles are metal powders and properly manufactured, it is possible to find a higher percentage of %Y in solid solution than in bulk alloys of the same composition. While this is a major obstacle for many applications, it can also be very beneficial for some applications of magnesium alloys. Magnesium-based alloys containing %Y are manufactured in particulate form. In other embodiments, the %Y in solid solution is 5 wt.% or more greater than the equilibrium solid solubility of %Y in the alloy at room temperature, 23° C. and 1 atm, or 12 wt.% or more, 26 wt.% or more, 56 wt.% or more, 116 wt.% or more, 216 wt.% or more. In some alloys, controlling the %Y in solid solution in constant terms may be more appropriate for some applications.In other embodiments, the %Y content in the solid solution of the alloy produced in particulate form is 1.8 wt.% or greater, 2.1 wt.% or greater, 2.6 wt.% or greater, 3.2 wt.% or greater, 4.6 wt.% or greater, 6.1 wt.% or greater, or even 8.1 wt.% or greater. In other embodiments, %Y is absent or present as an undesirable impurity. Some applications of magnesium alloys benefit from high lanthanum, calcium, beryllium, yttrium, and scandium (%Y+%Ca+%Be+%La+%Sc) contents. %Y+%Ca+%Be+%La+%Sc helps facilitate strengthening of the alloy. In some embodiments, %Y+%Ca+%Be+%La+%Sc contributes to improved mechanical properties. In some embodiments, %Y+%Ca+%Be+%La+%Sc contributes to improved creep resistance, especially when properly formulated with other alloying elements. In some embodiments, %Y+%Ca+%Be+%La+%Sc contributes to improved corrosion resistance, especially when properly formulated with other alloying elements. %Y+%Ca+%Be+%La+%Sc may also contribute as a ternary element to many of the properties mentioned for the other alloying elements. In some embodiments, the total amount of %Y+%Ca+%Be+%La+%Sc has a positive effect on %Li. In other embodiments, %Y+%Ca+%Be+%La+%Sc is greater than 0.06 wt%, greater than 0.6 wt%, greater than 1.2 wt%, greater than 2.2 wt%, greater than 3.2 wt%, greater than 5.3 wt%, greater than 7.8 wt%, or even greater than 10.1 wt%. In different embodiments, even higher %Y+%Ca+%Be+%La+%Sc contents are recommended to further enhance the aforementioned properties. In other embodiments, %Y+%Ca+%Be+%La+%Sc is greater than 11.2 wt%, greater than 16.2 wt%, greater than 21.2 wt%, greater than 25.2 wt%, or even greater than 31.2 wt%. In some embodiments, it is necessary to ensure that the total amount of %Y+%Ca+%Be+%La+%Sc is not excessive. It has been discovered that an excessive total amount of %Y+%Ca+%Be+%La+%Sc can result in an undesirable compromise between corrosion resistance and mechanical properties. In other embodiments it is recommended that %Y+%Ca+%Be+%La+%Sc be less than 28.8 wt%, less than 18.9 wt%, less than 9.8 wt%, less than 8.8 wt%, less than 6.9 wt%, less than 5.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.2 wt%, or even less than 0.8 wt%. In other embodiments %Y+%Ca+%Be+%La+%Sc is either absent or present as an undesired impurity. There are applications in magnesium alloys that benefit from a high ytterbium (%Yb) content. %Yb helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Yb content, it is possible to find more solid solution in %Yb, as shown in the applicable %Sc case. In some alloys, it is more appropriate to control the %Yb in solid solution with a constant term. In other embodiments, the %Yb content in solid solution for alloys manufactured in particle form is 0.01 wt% or more, 0.1 wt% or more, 0.4 wt% or more, 1.1 wt% or more, 1.6 wt% or more, 2.1 wt% or more, or even 3.1 wt% or more. In some embodiments, %Yb contributes to improved mechanical properties. In other embodiments, %Yb contributes to improved mechanical resistance. In some embodiments, %Yb contributes to improved creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Yb may contribute to improved corrosion resistance in some applications, especially when properly combined with other alloying elements. %Yb may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Yb may have a positive effect on %Li. The weight percentages for %Be disclosed above are also applicable to the %Yb content. Also, in some embodiments, %Yb may be absent or present as an undesirable impurity. There are applications in magnesium alloys that benefit from a high dysprosium (%Dy) content. %Dy helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Dy content, it is possible to find more solid solution, as shown in the applicable %La case, even in %Dy. In some alloys, controlling the %Dy in solid solution with a constant term is more appropriate. In other embodiments, the %Dy content in solid solution for alloys manufactured in particle form is 5.6 wt% or more, 6.6 wt% or more, 8.6 wt% or more, 12.6 wt% or more, 16 wt% or more, or even 22 wt% or more. In some embodiments, %Dy contributes to improved mechanical properties. In other embodiments, %Dy contributes to improved mechanical resistance. In some embodiments, %Dy contributes to improved creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Dy may also contribute to improved corrosion resistance. %Dy may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Dy has a positive effect on %Li. The weight percentages for %La disclosed above are also applicable to the %Dy content. Also, in some embodiments, %Dy is absent or present as an undesirable impurity. There are applications in magnesium alloys that benefit from a high thorium (%Th) content. %Th helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Th content, they can be found in more solid solution, as shown in the applicable %La case, even for %Th. In some alloys, controlling the %Th in solid solution with a constant term is more appropriate. In some embodiments, %Th contributes to improving some mechanical properties. In other embodiments, %Th contributes to improving mechanical resistance. In some embodiments, %Th contributes to improving creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Th may also contribute to improving corrosion resistance. %Th may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Th has a positive effect on %Li. The weight percentages for %La disclosed above also apply to the %Th content. In other embodiments, %Th is either absent or present as an undesirable impurity. There are applications in magnesium alloys that benefit from a high total ytterbium, dysprosium, and thorium (%Yb + %Dy + %Th) content. %Yb + %Dy + %Th helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. Therefore, alloys containing %Yb + %Dy + %Th in a particulate form that is generally not meaningful, can be meaningful in some embodiments. In some embodiments, %Yb + %Dy + %Th contributes to improved mechanical properties. In some embodiments, %Yb + %Dy + %Th contributes to improved creep resistance, especially when properly formulated with other alloying elements. In some embodiments, %Yb + %Dy + %Th contributes to improved corrosion resistance, especially when properly formulated with other alloying elements. %Yb + %Dy + %Th may also contribute as a ternary element to many of the properties mentioned for other alloying elements. In some embodiments, the total amount of %Yb + %Dy + %Th has a positive effect on %Li. In other embodiments, %Yb + %Dy + %Th is greater than 0.06 wt%, greater than 0.6 wt%, greater than 1.2 wt%, greater than 2.2 wt%, greater than 3.2 wt%, greater than 5.3 wt%, greater than 7.8 wt%, or even greater than 10.1 wt%. In different embodiments, even higher %Yb + %Dy + %Th contents are recommended to further enhance the aforementioned properties. In other embodiments, %Yb + %Dy + %Th is greater than 11.2 wt%, greater than 16.2 wt%, greater than 21.2 wt%, greater than 25.2 wt%, or even greater than 31.2 wt%. In some embodiments, it is necessary to ensure that the total amount of %Yb + %Dy + %Th is not excessive. It has been discovered that an excessive total amount of %Yb + %Dy + %Th can lead to an undesirable compromise between corrosion resistance and mechanical properties. In other embodiments, it is recommended that %Yb+%Dy+%Th be less than 28.8 wt%, less than 18.9 wt%, less than 9.8 wt%, less than 8.8 wt%, less than 6.9 wt%, less than 5.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.2 wt%, or even less than 0.8 wt%. In other embodiments, %Yb+%Dy+%Th is absent or present as undesirable impurities. There are applications in magnesium alloys that benefit from a high total ytterbium, beryllium, dysprosium, and thorium (%Yb+%Be+%Dy+%Th) content. %Yb+%Be+%Dy+%Th helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. Therefore, alloys containing %Yb+%Be+%Dy+%Th in a particulate form that is generally not meaningful, can be meaningful in some embodiments. In some embodiments, %Yb+%Be+%Dy+%Th contribute to improved mechanical properties. In some embodiments, %Yb+%Be+%Dy+%Th contribute to improved creep resistance, especially when properly formulated with other alloying elements. In some embodiments, %Yb+%Be+%Dy+%Th contribute to improved corrosion resistance, especially when properly formulated with other alloying elements. %Yb+%Be+%Dy+%Th may also contribute as a ternary element to many of the properties mentioned for other alloying elements. In some embodiments, the total amount of %Yb+%Be+%Dy+%Th has a positive effect on %Li. In other embodiments, %Yb+%Be+%Dy+%Th is greater than 0.06 wt%, greater than 0.6 wt%, greater than 1.2 wt%, greater than 2.2 wt%, greater than 3.2 wt%, greater than 5.3 wt%, greater than 7.8 wt%, or even greater than 10.1 wt%. In different embodiments to further emphasize the aforementioned properties, even higher %Yb+%Be+%Dy+%Th contents are recommended. In other embodiments, %Yb+%Be+%Dy+%Th is greater than 11.2 wt%, greater than 16.2 wt%, greater than 21.2 wt%, greater than 25.2 wt%, or even greater than 31.2 wt%. In some embodiments, it is necessary to control the total amount of %Yb+%Be+%Dy+%Th to ensure that it is not excessive. It has been discovered that an excessive total amount of %Yb+%Be+%Dy+%Th can result in an undesirable compromise between corrosion resistance and mechanical properties. In another embodiment, it is recommended that %Yb+%Be+%Dy+%Th be less than 28.8 wt%, less than 18.9 wt%, less than 9.8 wt%, less than 8.8 wt%, less than 6.9 wt%, less than 5.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.2 wt%, or even less than 0.8 wt%.Also, in some embodiments, %Yb+%Be+%Dy+%Th are either absent or present as undesirable impurities. Magnesium alloys may benefit from high total ytterbium, beryllium, dysprosium, calcium, yttrium, lanthanum, scandium, and thorium (%Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc) contents in some applications. %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc aid in facilitating alloy strengthening. In some embodiments, %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc contribute to improved mechanical properties. In some embodiments, %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc contribute to improved creep resistance, especially when properly formulated with other alloying elements. In some embodiments, %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc contribute to improved corrosion resistance, especially when properly formulated with other alloying elements. %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc may also contribute as a three-dimensional element to many of the properties described for the other alloying elements. In some embodiments, the total amount of %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc favorably impacts %Li. In other embodiments, %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc includes greater than 0.06 wt%, greater than 0.6 wt%, greater than 1.2 wt%, greater than 2.2 wt%, greater than 3.2 wt%, greater than 5.3 wt%, greater than 7.8 wt%, and even greater than 10.1 wt%. Even higher %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc contents are recommended in different embodiments to further enhance the aforementioned properties. In other embodiments, %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc is greater than 11.2 wt%, greater than 16.2 wt%, greater than 21.2 wt%, greater than 25.2 wt%, or even greater than 31.2 wt%. In some embodiments, it is necessary to control to ensure that the total amount of %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc is not excessive. It has been discovered that if the total amount of %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc is excessive, an undesirable compromise between corrosion resistance and mechanical properties may occur.In other embodiments it is recommended that %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc be less than 28.8 wt%, less than 18.9 wt%, less than 9.8 wt%, less than 8.8 wt%, less than 6.9 wt%, less than 5.8 wt%, less than 4.1 wt%, less than 2.8 wt%, less than 1.2 wt%, or even less than 0.8 wt%. In other embodiments %Yb+%Be+%Dy+%Th+%Ca+%Y+%La+%Sc is either absent or present as an undesired impurity. There are applications in which magnesium alloys benefit from a high gadolinium (%Gd) content. %Gd helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Gd content, they can be found in more solid solution, as shown in the applicable %La case, even in %Gd. In some applications, it is more appropriate to control the %Gd in solid solution with a constant term. In other embodiments, the %Gd content in solid solution for alloys manufactured in particle form is 0.01 wt% or more, 0.05 wt% or more, 0.1 wt% or more, 1.1 wt% or more, 3.1 wt% or more, 5.1 wt% or more, 10.5 wt% or more, or even 14 wt% or more. In some embodiments, %Gd contributes to improved mechanical properties. In other embodiments, %Gd contributes to improved mechanical resistance. In some embodiments, %Gd contributes to improved creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Gd may contribute to improved corrosion resistance in some applications, especially when properly combined with other alloying elements. %Gd may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Gd may have a positive effect on %Li. The weight percentages for %Sc disclosed above are also applicable to the %Gd content. In other embodiments, %Gd may be absent or present as an undesirable impurity. There are applications in magnesium alloys that benefit from a high neodymium (%Nd) content. %Nd helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Nd content, it is possible to find more solid solution, as shown in the applicable %La case, even in %Nd. In some alloys, it is more appropriate to control the %Nd content in solid solution with a constant term. In other embodiments, the %Nd content in solid solution for alloys manufactured in particle form is 0.001 wt% or more, 0.01 wt% or more, 0.055 wt% or more, 0.12 wt% or more, 0.22 wt% or more, 0.6 wt% or more, 1.1 wt% or more, or even 2.1 wt% or more. In some embodiments, %Nd contributes to improving some mechanical properties. In other embodiments, %Nd contributes to improving mechanical resistance. In some embodiments, %Nd contributes to improved creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Nd also has applications in improving corrosion resistance, especially when properly combined with other alloying elements. %Nd may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Nd positively influences %Li. The weight percentages for %Sc disclosed above also apply to the %Nd content. In other embodiments, %Nd is absent or present as an undesirable impurity. Some applications of magnesium alloys benefit from a high samarium (%Sm) content. %Sm helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Sm content, it is possible to find more solid solution, as shown in the applicable %La case, even for %Sm. In some applications, it is more appropriate to control the %Sm in solid solution with a constant term. In other embodiments, the %Sm content in solid solution for alloys manufactured in particle form is 0.001 wt% or more, 0.01 wt% or more, 0.055 wt% or more, 0.12 wt% or more, 0.22 wt% or more, 0.6 wt% or more, 1.1 wt% or more, or even 2.1 wt% or more. In some embodiments, %Sm contributes to improved mechanical properties. In other embodiments, %Sm contributes to improved mechanical resistance. In some embodiments, %Sm contributes to improved creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Sm also has applications in improving corrosion resistance, especially when properly combined with other alloying elements. %Sm may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Sm positively influences %Li. The weight percentages for %La disclosed above also apply to the %Sm content. In other embodiments, %Sm is either absent or present as an undesirable impurity. There are applications in which magnesium alloys benefit from a high praseodymium (%Pr) content. %Pr helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Pr content, they can be found in more solid solution, as shown in the applicable %La case, even in %Pr. In some alloys, controlling the %Pr in solid solution with a constant term is more appropriate. In other embodiments, the %Pr content in solid solution for alloys manufactured in particle form is 0.001 wt% or more, 0.005 wt% or more, 0.01 wt% or more, 0.055 wt% or more, 0.12 wt% or more, 0.22 wt% or more, 0.42 wt% or more, or even 0.6 wt% or more. In some embodiments, %Pr contributes to improved mechanical properties. In other embodiments, %Pr contributes to improved mechanical resistance. In some embodiments, %Pr contributes to improved creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Pr may contribute to improved corrosion resistance in some applications, especially when properly combined with other alloying elements. %Pr may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Pr may have a positive effect on %Li. The weight percentages for %La disclosed above are also applicable to the %Pr content. In other embodiments, %Pr may be absent or present as an undesirable impurity. There are applications in which magnesium alloys benefit from a high holmium (%Ho) content. %Ho helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Ho content, it is possible to find more solid solution, as shown by the applicable %La case, even in %Ho. In some alloys, controlling the %Ho in solid solution with a constant term is more appropriate. In other embodiments, the %Ho content in solid solution for alloys manufactured in particle form is 10.6 wt% or more, 12.2 wt% or more, 14 wt% or more, 16 wt% or more, 18 wt% or more, 20.5 wt% or more, 21.1 wt% or more, or even 22.1 wt% or more. In some embodiments, %Ho contributes to improved mechanical properties. In other embodiments, %Ho contributes to improved mechanical resistance. In some embodiments, %Ho contributes to improved creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Ho may contribute to improved corrosion resistance in some applications, especially when properly combined with other alloying elements. %Ho may also contribute as a third element to many of the properties noted for other alloying elements. In some embodiments, %Ho may have a positive effect on %Li. The weight percentages for %La disclosed above are also applicable to the %Ho content. In other embodiments, %Ho may be absent or present as an undesirable impurity. Some applications of magnesium alloys benefit from a high terbium (%Tb) content. %Tb helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Tb content, it is possible to find more solid solution, as shown in the applicable %La case, even in %Tb. In some alloys, it is more appropriate to control the %Tb in solid solution with a constant term. In other embodiments, the %Tb content in solid solution for alloys manufactured in particle form is 2.1 wt% or more, 2.6 wt% or more, 3.2 wt% or more, 5.2 wt% or more, 8.2 wt% or more, 10.6 wt% or more, 11.1 wt% or more, or even 13.1 wt% or more. In some embodiments, %Tb contributes to improving some mechanical properties. In other embodiments, %Tb contributes to improving mechanical resistance. In some embodiments, %Tb contributes to improved creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Tb also has applications in improving corrosion resistance, especially when properly combined with other alloying elements. %Tb may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Tb positively influences %Li. The weight percentages for %La disclosed above also apply to the %Tb content. In other embodiments, %Tb is absent or present as an undesirable impurity. There are applications in magnesium alloys that benefit from a high thulium (%Tm) content. %Tm helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Tm, it is possible to find more solid solution, even at high %Tm, as shown in the applicable %La case. In some alloys, controlling the %Tm of the solid solution in constant terms is more appropriate. In other embodiments, the %Tm content in the solid solution of alloys manufactured in particle form is 10.6 wt% or more, 12.2 wt% or more, 14 wt% or more, 16 wt% or more, 18 wt% or more, 20.5 wt% or more, 21.1 wt% or more, or even 22.1 wt% or more. In some embodiments, %Tm contributes to improved mechanical properties. In other embodiments, %Tm contributes to improved mechanical resistance. In some embodiments, %Tm contributes to improved creep resistance, especially when properly combined with other alloying elements. In some embodiments, %Tm may contribute to improved corrosion resistance in some applications, especially when properly combined with other alloying elements. %Tm may also contribute as a third element to many of the properties noted for other alloying elements. In some embodiments, %Tm may have a positive effect on %Li. The weight percentages for %La disclosed above are also applicable to the %Tm content. In other embodiments, %Tm may be absent or present as an undesirable impurity. There are applications in which magnesium alloys benefit from a high erbium (%Er) content. %Er helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Er content, they can be found in more solid solution, as shown in the applicable %La case. In some alloys, it may be more appropriate to control the %Er content in solid solution with a constant term, similar to the level disclosed above for %Ho, which is also applicable to the %Er content. In some embodiments, %Er contributes to the improvement of some mechanical properties. In other embodiments, %Er contributes to improved mechanical resistance. In some embodiments, especially when properly combined with other alloying elements, %Er contributes to improved creep resistance. In some applications, especially when properly combined with other alloying elements, %Er contributes to improved corrosion resistance. %Er may also contribute as a third element to many of the properties mentioned for other alloying elements. In some embodiments, %Er has a positive effect on %Li. The weight percentages for %La disclosed above are also applicable to the %Er content, and in some embodiments %Er is either absent or present as an undesirable impurity. There are applications in which magnesium alloys benefit from a high lutetium (%Lu) content. %Lu helps facilitate strengthening of the alloy. This result is surprising, especially since this is also the case for some alloys containing %Y. In fact, we have discovered that when the particles are metal powders and properly manufactured with a high %Lu content, they can be found in more solid solution, as shown in the applicable %La case, even in %Lu. In some applications, it may be more appropriate to control the %Lu content in solid solution with a constant term, similar to the level disclosed for %Ho above, which is also applicable to the %Lu content. In some embodiments, %Lu contributes to the improvement of some mechanical properties. In other embodiments, %Lu contributes to improved mechanical resistance. In some embodiments, especially when properly combined with other alloying elements, %Lu contributes to improved creep resistance. In some applications, especially when properly combined with other alloying elements, %Lu contributes to improved corrosion resistance. %Lu may also contribute as a ternary element to many of the properties mentioned for other alloying elements. In some embodiments, %Lu has a positive effect on %Li. The weight percentages of %La disclosed above also apply to the %Lu content. In some embodiments, %Lu is absent or present as an undesirable impurity. In some embodiments, lutetium (%Lu) can be partially or completely substituted with europium (%Eu). In some embodiments, lutetium (%Lu) can be partially or completely substituted with promethium (%Pr). It has been discovered that certain relationships between alloying elements are important when considering cost and maximizing structural resistance under fire. It has been discovered that in some embodiments, it is important to have a relationship between %Ca and %Li. It has also been discovered that in some embodiments, it is important to have a relationship between %Ca, %Al, and %Li. Other applications in alloy manufacturing include %Ca greater than 1.2 wt%, or greater than 2.2 wt%, or greater than 3.2 wt%, or greater than 5.3 wt%, or greater than 7.8 wt%. Other applications in alloy manufacturing include %Ca less than 11.9 wt%, or less than 9.8 wt%, or less than 8.8 wt%, or even less than 6.9 wt%. This is another embodiment for %Li greater than 2.3 wt%, or greater than 4.2 wt%, or greater than 5.2 wt%, or greater than 6.9 wt%, or greater than 7.8 wt%, or greater than 10.2 wt%, or greater than 11.2 wt%, or greater than 12.2 wt%, or greater than 14.2 wt%, or greater than 16 wt%, or greater than 18 wt%, or greater than 26 wt%. In another embodiment to balance mechanical properties, it is recommended that %Ca / (%Li + %Al) be greater than 0.15, or greater than 0.28, or greater than 0.56, or greater than 0.62, or greater than 0.66, or greater than 0.76, or even greater than 1.1 (where %Ca, %Li, and %Al are the atomic weights of calcium, lithium, and aluminum, respectively). In another embodiment, it is recommended that %Ca / (%Li + %Al) be less than 1.9, or less than 1.4, or less than 0.98, or less than 0.88, or less than 0.74, or even less than 0.68. In other embodiments, %Ca / %Li should be greater than 0.07, greater than 0.22, greater than 0.52, greater than 0.62, greater than 0.66, greater than 0.76, or even greater than 1.1. In still other embodiments, it is recommended that %Ca / %Li be less than 1.4, less than 0.98, less than 0.74, less than 0.68, less than 0.58, or even less than 0.48. It has been discovered that in some applications the sum of %Nd and %Gd should not be zero (at least one must be present, and obviously the general proportions described in the previous paragraph apply).It has also been discovered that there are applications in which %Y must not be absent (as applies throughout this specification, but where a specific weight or atomic percentage is not specified, such as the description of the exact percentages in the previous paragraph, the description in a more general form applies. Also, all of the percentages of the alloying elements listed are not ultimately required. That is, in this embodiment, the alloy cannot be used without %Y because %Y must be present, but in the embodiment described above, it may be useful to include %Sc. That is, an embodiment optimized for an application in which %Sc is useful may include %Sc, but in this embodiment, it is also possible to implement an embodiment in which %Sc is not included). It has also been discovered that there are embodiments in which %Zr must be included. In some embodiments, the inclusion of %Zr may be useful to achieve the required mechanical properties, with the %Zr content being greater than 0.06 wt.%, greater than 0.1 wt.%, greater than 0.31 wt.%, or greater than 0.41 wt.% in other embodiments. When %Li is greater than 11.1 wt.%, the inclusion of %Zr in the alloy is recommended to balance the mechanical properties. While zinc (Zn) content in magnesium alloys is recommended for some applications, it has been found to be an impurity in others. In other embodiments, Zn content levels of at least 0.1 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, at least 6.2 wt%, at least 8.2 wt%, or at least 11 wt% are recommended. Conversely, Zn content levels of less than 12.8 wt%, less than 9.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt% are recommended to achieve the desired mechanical properties. Obviously, all elements can be accommodated in a particular application, but there may be cases where a nominal content of a particular element is required to be 0%. In certain applications, the use of alloys containing %Ga, %Bi, %Rb, %Cd, %Cs, %Sn, %Pb, %Zn, or %In is particularly worthy of consideration. These elements, among others, are used with %Ga contents of greater than 0.8 wt%, 2.2 wt%, 5.2 wt%, 12 wt%, 21 wt%, or 54 wt%. In some embodiments, the %Ga content in the alloy is greater than 32 ppm by weight, 0.0001 wt%, 0.015 wt%, or 0.1 wt%. Depending on the desired properties of the magnesium alloy, in some applications, a %Ga content of less than 30 wt%, 29 wt%, 22 wt%, 16 wt%, 9 wt%, 6.4 wt%, 4.1 wt%, 3.2 wt%, 2.4 wt%, or even less than 1.2 wt% is recommended. In some applications, %Ga may be detrimental or not optimal for some reason. For such applications, it is recommended that the magnesium alloy be free of %Ga. It has been found that in some applications, %Ga can be replaced in whole or in part with %Bi in the amounts specified for %Ga + %Bi. In some applications, total substitution, i.e., the absence of %Ga, is effective. In some applications, partial substitution of %Ga or %Bi with %Cd, %Cs, %Sn, %Pb, %Zn, %Rb, or %In in the amounts stated above may be considered. In some applications, the absence of any of the above elements may be considered, and in such cases, the alloy may be considered as %Ga + %Bi + %Cd + %Cs + %Sn + %Pb + %Zn + %Rb + %In (i.e., the sum matches the given value, but a particular element may not be present and its nominal content may be 0%. This is useful for certain applications where the element in question is detrimental or not optimal for some reason). These elements do not necessarily need to be in their pure state. The use of alloys of these elements is often economical given that the melting points of the alloys in question are sufficiently low. In some applications, it is advantageous to directly use alloys containing these elements rather than formulating them separately. In other applications, the use of particles primarily composed of these elements is worth considering. In these cases, the sum of %Ga + %Bi + %Cd + %Cs + %Sn + %Pb + %Zn + %Rb + %In is greater than 52 wt.%, or greater than 76 wt.%, or greater than 86 wt.%, or greater than 98 wt.% in other embodiments. The final content of these elements in the component depends on the volume fractions used, but in some applications it can vary within the above ranges. A typical example is when a %Sn and %Ga alloy is used for liquid phase sintering at low temperatures, which is likely to destroy oxide films that may contain other particles (usually majority particles). The %Sn and %Ga contents are adjusted with reference to the equilibrium phase diagram to control the volume content of the liquid phase required at various post-processing temperatures and the volume fraction of the particles of this alloy. For specific applications, %Sn or %Ga can be partially or completely replaced by other elements from the list (i.e. the alloy can contain no %Sn or %Ga), even in the case of significant inclusion of other elements not included in this list, such as in the case of %Mg, or the recommended alloying elements for the required alloy for a specific application. While manganese (%Mn) is considered an impurity in some applications, it has been discovered that its inclusion is required in other applications. To improve mechanical properties, %Mn of at least 0.1 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, at least 6.2 wt%, at least 8.2 wt%, or at least 11 wt% is recommended. Conversely, in some applications, %Mn is highly detrimental. In other embodiments, to balance mechanical properties, %Mn contents of less than 12.8 wt%, less than 9.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt% are recommended. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. It has been discovered that while zirconium (%Zr) is considered an impurity in some applications, its inclusion is required in others. To improve mechanical properties, %Zr is recommended to be at least 0.02 wt%, at least 0.1 wt%, at least 0.26 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, or at least 6.2 wt%. Conversely, in some applications, %Zr is highly detrimental. In other embodiments, to balance mechanical properties, %Zr is recommended to be less than 7.8 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 1.8 wt%, less than 0.8 wt%, less than 0.48 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt%. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. While boron (%B) is considered an impurity in some applications, it has been discovered that its presence is desirable in other applications. It has also been discovered that the presence of %B affects the melting point and mechanical properties of the alloy. In this regard, in another embodiment, a %B content of 12 wt ppm or more, greater than 37 wt ppm, 73 wt ppm or more, or even 130 wt ppm or more is recommended. In another embodiment, a %B content of 0.002 wt% or more, 0.01 wt% or more, 0.1 wt% or more, 0.26 wt% or more, 0.3 wt% or more, 0.6 wt% or more, 1.2 wt% or more, 2.2 wt% or more, or 4.2 wt% or more is recommended. Conversely, in some applications, the presence of %B is highly detrimental. In other embodiments to balance the mechanical properties, contents of less than 3.8 wt%, less than 2.8 wt%, less than 1.8 wt%, less than 0.8 wt%, less than 0.48 wt%, less than 0.18 wt%, less than 0.08 wt%, less than 0.02 wt%, or even less than 0.002 wt% are recommended. Obviously, all optional elements can be accommodated in specific applications, but there may be cases where a nominal content of a particular element is required to be 0%. The inclusion of at least one of %Al, %Zr, %Zn, %Cd, and %Ca contributes to improving mechanical properties, and in another embodiment, it is recommended that the content be greater than 0.01 wt%, greater than 0.1 wt%, or greater than 0.7 wt%, individually or in total. The magnesium alloy contains at least one of %Ca, %Zr, or %Al, and in another embodiment, it is recommended that the content be greater than 0.01 wt%, greater than 0.1 wt%, or greater than 0.7 wt%. This is an individual or total numerical value. In another embodiment, it is recommended that the alloy contains at least one of %Ca or %Zr, and in another embodiment, it is recommended that the content be greater than 0.01 wt%, greater than 0.1 wt%, or greater than 0.7 wt%, individually or in total. While copper (%Cu) is considered an impurity in some applications, it has been discovered that its inclusion is required in other applications. To improve mechanical properties, %Cu is recommended to be at least 0.1 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, at least 6.2 wt%, at least 8.2 wt%, at least 11 wt%, at least 16.2 wt%, or at least 21.2 wt%. Conversely, %Cu is highly detrimental in some applications. In other embodiments, to balance mechanical properties, %Cu is recommended to be less than 18.8 wt%, less than 14.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt%. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. It has been discovered that while tantalum (%Ta) is considered an impurity in some applications, its inclusion is required in others. To improve mechanical properties, %Ta is recommended to be 0.02 wt.%, 0.1 wt.%, 0.26 wt.%, 0.6 wt.%, 1.2 wt.%, 2.2 wt.%, or 4.2 wt.% or greater. Conversely, %Ta is highly detrimental in some applications. In other embodiments, to balance mechanical properties, %Ta is recommended to be less than 3.8 wt.%, 2.8 wt.%, 1.8 wt.%, 0.8 wt.%, 0.48 wt.%, 0.18 wt.%, 0.08 wt.%, 0.02 wt.%, or even less than 0.002 wt.%. Obviously, all optional elements are acceptable for certain applications, but a nominal 0% content of a particular element may be required. While vanadium (%V) is considered an impurity in some applications, it has been discovered that vanadium inclusion is required in other applications. To improve mechanical properties, %V of at least 0.02 wt%, at least 0.1 wt%, at least 0.26 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, or at least 6.2 wt% is recommended. Conversely, in some applications, %V inclusion is highly detrimental. In other embodiments, to balance mechanical properties, vanadium inclusions of less than 7.8 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 1.8 wt%, less than 0.8 wt%, less than 0.48 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt% are recommended. Obviously, all optional elements are acceptable for certain applications, but a nominal 0% content of a particular element may be required. It has been discovered that while nitrogen (%N) is considered an impurity in some applications, its inclusion is required in others. To improve mechanical properties, %N of 0.002 wt.%, 0.01 wt.%, 0.1 wt.%, 0.26 wt.%, 0.6 wt.%, or 1.2 wt.% is recommended. Conversely, %N is highly detrimental in some applications. In other embodiments, to balance mechanical properties, %N of less than 3.8 wt.%, 2.8 wt.%, 1.8 wt.%, 0.8 wt.%, 0.48 wt.%, 0.18 wt.%, 0.08 wt.%, or even less than 0.02 wt.% is recommended. Obviously, all optional elements are acceptable for certain applications, but a nominal 0% content of a particular element may be required. While silicon (%Si) is considered an impurity in some applications, it has been discovered that its inclusion is required in other applications. To improve mechanical properties, %Si is recommended to be at least 0.1 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, at least 6.2 wt%, at least 8.2 wt%, and even at least 11 wt%. Conversely, in some applications, %Si is highly detrimental. In other embodiments, to balance mechanical properties, %Si is recommended to be less than 12.8 wt%, less than 9.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt%. Obviously, all optional elements are acceptable for certain applications, but a nominal 0% content of a particular element may be required. It has been discovered that while iron (%Fe) is considered an impurity in some applications, in others, its inclusion is required. To improve mechanical properties, %Fe is recommended to be at least 0.1 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, at least 6.2 wt%, at least 8.2 wt%, at least 11 wt%, at least 16.2 wt%, or at least 21.2 wt%. Conversely, in some applications, %Fe is highly detrimental. In other embodiments, to balance mechanical properties, %Fe contents of less than 18.8 wt%, less than 14.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt% are recommended. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. While nickel (%Ni) is considered an impurity in some applications, it has been discovered that in other applications, nickel inclusion is desirable. To improve mechanical properties, %Ni of at least 0.1 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, at least 6.2 wt%, at least 8.2 wt%, at least 11 wt%, at least 16.2 wt%, at least 21.2 wt%, or at least 31.2 wt% is recommended. Conversely, in some applications, %Ni inclusion is highly detrimental. In other embodiments to balance mechanical properties, %Ni inclusions of less than 28.8 wt%, less than 18.8 wt%, less than 14.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt% are recommended. Obviously, any optional element can be accommodated in a particular application, but there may be cases where a nominal content of a particular element is required to be 0%. It has been discovered that while chromium (%Cr) is considered an impurity in some applications, in others the inclusion of chromium is required. To improve mechanical properties, %Cr is recommended to be greater than or equal to 0.1 wt%, greater than or equal to 0.6 wt%, greater than or equal to 1.2 wt%, greater than or equal to 4.2 wt%, greater than or equal to 6.2 wt%, greater than or equal to 8.2 wt%, and even greater than or equal to 11 wt%. Conversely, in some applications, %Cr is highly detrimental. In other embodiments to balance mechanical properties, inclusions of less than 12.8 wt%, less than 9.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, and even less than 0.02 wt% are recommended. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. While titanium (%Ti) is considered an impurity in some applications, it has been discovered that its inclusion is required in other applications. To improve mechanical properties, %Ti is recommended to be greater than or equal to 0.1 wt%, greater than or equal to 0.6 wt%, greater than or equal to 1.2 wt%, greater than or equal to 4.2 wt%, greater than or equal to 6.2 wt%, greater than or equal to 8.2 wt%, greater than or equal to 11 wt%, and even greater than or equal to 16.2 wt%. Conversely, %Ti is highly detrimental in some applications. In other embodiments, to balance mechanical properties, %Ti is recommended to be less than 18.8 wt%, less than 14.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, and even less than 0.02 wt%. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. While niobium (%Nb) is considered an impurity in some applications, it has been discovered that its inclusion in other applications is required. To improve mechanical properties, %Nb is recommended to be at least 0.02 wt%, at least 0.1 wt%, at least 0.26 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, or at least 6.2 wt%. Conversely, in some applications, %Nb is highly detrimental. In other embodiments, to balance mechanical properties, %Nb contents of less than 7.8 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 1.8 wt%, less than 0.8 wt%, less than 0.48 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt% are recommended. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. While cobalt (%Co) is considered an impurity in some applications, it has been discovered that its inclusion is required in other applications. To improve mechanical properties, %Co is recommended to be at least 0.1 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, at least 6.2 wt%, at least 8.2 wt%, at least 11 wt%, at least 16.2 wt%, or at least 21.2 wt%. Conversely, %Co is highly detrimental in some applications. In other embodiments, to balance mechanical properties, %Co is recommended to be less than 18.8 wt%, less than 14.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt%. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. While molybdenum (%Mo) is considered an impurity in some applications, it has been discovered that its inclusion is required in other applications. To improve mechanical properties, %Mo is recommended to be greater than or equal to 0.1 wt%, greater than or equal to 0.6 wt%, greater than or equal to 1.2 wt%, greater than or equal to 4.2 wt%, greater than or equal to 6.2 wt%, greater than or equal to 8.2 wt%, and even greater than or equal to 11 wt%. Conversely, in some applications, %Mo is highly detrimental. In other embodiments, to balance mechanical properties, %Mo is recommended to be less than 12.8 wt%, less than 9.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, and even less than 0.02 wt%. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal content of a particular element is required to be 0%. While tungsten (%W) is considered an impurity in some applications, it has been discovered that its inclusion is required in other applications. To improve mechanical properties, %W of at least 0.1 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, at least 6.2 wt%, at least 8.2 wt%, at least 11 wt%, at least 16.2 wt%, at least 21.2 wt%, or at least 31.2 wt% is recommended. Conversely, in some applications, %W is highly detrimental. In other embodiments, to balance mechanical properties, %W less than 18.8 wt%, less than 14.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt% is recommended. Obviously, all optional elements are acceptable for certain applications, but a nominal 0% content of a particular element may be required. While hafnium (%Hf) is considered an impurity in some applications, it has been discovered that in some magnesium alloy applications, its inclusion is required. To improve mechanical properties, %Hf is recommended to be at least 0.02 wt%, at least 0.1 wt%, at least 0.26 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 2.2 wt%, or at least 4.2 wt%. Conversely, in some applications, %Hf is highly detrimental. In other embodiments, to balance mechanical properties, %Hf contents of less than 3.8 wt%, less than 2.8 wt%, less than 1.8 wt%, less than 0.8 wt%, less than 0.48 wt%, less than 0.18 wt%, less than 0.08 wt%, less than 0.02 wt%, or even less than 0.002 wt% are recommended. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. While germanium (%Ge) is considered an impurity in some applications, it has been discovered that its inclusion is required in other applications. To improve mechanical properties, %Ge of at least 0.1 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, at least 6.2 wt%, at least 8.2 wt%, at least 11 wt%, and even at least 16.2 wt% are recommended. Conversely, in some applications, %Ge is highly detrimental. In other embodiments, to balance mechanical properties, inclusions of less than 18.8 wt%, less than 14.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, and even less than 0.02 wt% are recommended. Obviously, all optional elements are acceptable for certain applications, but a nominal 0% content of a particular element may be required. While cerium (%Ce) is considered an impurity in some applications, it has been discovered that in other applications, its inclusion is required. To improve mechanical properties, %Ce is recommended to be greater than or equal to 0.1 wt%, greater than or equal to 0.6 wt%, greater than or equal to 1.2 wt%, greater than or equal to 4.2 wt%, greater than or equal to 6.2 wt%, greater than or equal to 8.2 wt%, and even greater than or equal to 11 wt%. Conversely, in some applications, %Ce is highly detrimental. In other embodiments, to balance mechanical properties, inclusions of less than 12.8 wt%, less than 9.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, and even less than 0.02 wt% are recommended. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. While selenium (%Se) is considered an impurity in some applications, it has been discovered that its inclusion is required in other applications. To improve mechanical properties, %Se is recommended to be greater than or equal to 0.02 wt%, greater than or equal to 0.1 wt%, greater than or equal to 0.26 wt%, greater than or equal to 0.6 wt%, greater than or equal to 1.2 wt%, greater than or equal to 4.2 wt%, or greater than or equal to 6.2 wt%. Conversely, %Se is highly detrimental in some applications. In other embodiments, to balance mechanical properties, %Se contents less than 7.8 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 1.8 wt%, less than 0.8 wt%, less than 0.48 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt% are recommended. Obviously, all optional elements are acceptable for certain applications, but a nominal 0% content of a particular element may be required. While tellurium (%Te) is considered an impurity in some applications, it has been discovered that selenium is required in other applications. To improve mechanical properties, %Te is recommended to be greater than or equal to 0.02 wt%, greater than or equal to 0.1 wt%, greater than or equal to 0.26 wt%, greater than or equal to 0.6 wt%, greater than or equal to 1.2 wt%, greater than or equal to 4.2 wt%, or greater than or equal to 6.2 wt%. Conversely, %Te is highly detrimental in some applications. In other embodiments, to balance mechanical properties, %Te less than 7.8 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 1.8 wt%, less than 0.8 wt%, less than 0.48 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt% is recommended. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. While arsenic (%As) is considered an impurity in some applications, it has been discovered that its inclusion in other applications is desirable. To improve mechanical properties, %As of at least 0.02 wt%, at least 0.1 wt%, at least 0.26 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, or at least 6.2 wt% is recommended. Conversely, in some applications, %As is highly detrimental. In other embodiments, %As of less than 7.8 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 1.8 wt%, less than 0.8 wt%, less than 0.48 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt% is recommended. Obviously, all optional elements are acceptable for certain applications, but a nominal 0% content of a particular element may be required. While antimony (%Sb) is considered an impurity in some applications, it has been discovered that its inclusion is required in other applications. To improve mechanical properties, %Sb is recommended to be greater than or equal to 0.1 wt%, greater than or equal to 0.6 wt%, greater than or equal to 1.2 wt%, greater than or equal to 4.2 wt%, greater than or equal to 6.2 wt%, greater than or equal to 8.2 wt%, greater than or equal to 11 wt%, and even greater than or equal to 16.2 wt%. Conversely, in some applications, %Sb is highly detrimental. In other embodiments, to balance mechanical properties, inclusions of less than 18.8 wt%, less than 14.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, and even less than 0.02 wt% are recommended. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal content of a particular element is required to be 0%. It has been discovered that while oxygen (%O) is considered an impurity in some applications, its inclusion is required in others. It is recommended that %O be at least 0.002 wt%, at least 0.1 wt%, at least 0.6 wt%, at least 1.2 wt%, at least 4.2 wt%, at least 6.2 wt%, at least 8.2 wt%, or even at least 11 wt%. Conversely, in some applications, %O is highly detrimental. In other embodiments, to balance mechanical properties, it is recommended that the content be less than 12.8 wt%, less than 9.6 wt%, less than 9.4 wt%, less than 6.3 wt%, less than 4.2 wt%, less than 2.3 wt%, less than 1.8 wt%, less than 0.2 wt%, less than 0.08 wt%, or even less than 0.02 wt%. Obviously, all optional elements are acceptable for certain applications, but a nominal 0% content of a particular element may be required. While carbon (%C) is considered an impurity in some applications, it has been discovered that in other magnesium alloy applications, its inclusion is required. To improve mechanical properties, %C is recommended to be greater than or equal to 0.002 wt%, greater than or equal to 0.01 wt%, greater than or equal to 0.1 wt%, greater than or equal to 0.26 wt%, greater than or equal to 0.6 wt%, greater than or equal to 1.2 wt%, greater than or equal to 2.2 wt%, or greater than or equal to 4.2 wt%. Conversely, in some applications, %C is highly detrimental. In other embodiments, to balance mechanical properties, %C less than 3.8 wt%, less than 2.8 wt%, less than 1.8 wt%, less than 0.8 wt%, less than 0.48 wt%, less than 0.18 wt%, less than 0.08 wt%, less than 0.02 wt%, or even less than 0.002 wt% is recommended. Obviously, all optional elements are acceptable for certain applications, but there are cases where a nominal 0% content of a particular element is required. It has been discovered that in some embodiments, the microstructure of the alloy is important. In some embodiments, the microstructure of the magnesium alloy includes a beta phase. In some embodiments, the microstructure is composed of beta phase and HPC (hexagonal close packed). In other embodiments, the microstructure is predominantly beta phase. The alloy microstructure includes 52% or more by volume of beta phase. In other magnesium alloy embodiments, less than 48%, less than 37%, less than 28%, less than 16%, or less than 8% by volume of the HPC microstructure. In other embodiments, the microstructure is beta phase. The magnesium alloys disclosed above can be used to manufacture lightweight components. It has been discovered that the use of the magnesium alloys disclosed above, in some embodiments, enables the manufacture of structural components with high environmental resistance and high resistance to combustion. In some embodiments, the magnesium alloys disclosed herein are characterized by high structural resistance under combustion. Further embodiments of the magnesium alloys disclosed above are detailed below: In one set of embodiments, lightweight structures can be obtained using magnesium alloys having the following compositions, all percentages being by weight: %Mg>12%. %Li:1.1‐29; %Ca+%Y+%Al=0.5‐24; %Be+%Sc=0‐2.5; %Zr+%Hf+%Ti=0‐2.5; %Cu+%Ni+%Co+%Zn+%Mn+%Si+%Cr+%Nb=0‐12; %Ge+%Ce+%Fe+%Pb+%V+%Mo+%W+%Ta=0‐10; %B+%N+%O+%C=0‐2.5; %Bi+%Ga+%Cd+%In+%Sn+%Cs+%Rb=0‐9; %Se+%Te+%As+%Sb=0‐2.4; %Nd+%Gd+%La=0‐9; %Tm+%Tb+%Dy+%Yb+%Er+%Sm+%Pr+%Ho+%Lu+%Th=0‐9; The remainder is made up of %Mg and trace elements. In one embodiment, when using the disclosed magnesium alloy for lightweight construction, the disclosed composition describes the overall composition of the inorganic portion of the material. This also applies when different phases or powders are present in different compositions. In some embodiments, only the composition of the powders that can ultimately be mixed with other powders to form a powder mixture is described. In other embodiments, only the phases of the material are described. For some applications, the sum of %Ca + %Y + %Al may be important for balancing mechanical properties, and different levels are recommended in different embodiments. While the values above for each individual element should always be respected, in some embodiments, the sum of the elements must be considered. In other embodiments, it is recommended that %Ca + %Y + %Al be 0.5 wt.% or more, 1.1 wt.% or more, 2.2 wt.% or more, 5.2 wt.% or more, 8.2 wt.% or more, 11 wt.% or more, or 16 wt.% or more. As expected, this also applies to each individual element, and in some applications, an excessively high sum of these elements may have a negative impact on the overall properties. In other embodiments, it is recommended that %Ca+%Y+%Al be 44% by weight or less, 34% by weight or less, 24% by weight or less, 18% by weight or less, 14% by weight or less, 9% by weight or less, or 4% by weight or less. In some applications, the sum of %Be + %Sc may be important, and different levels are recommended in different embodiments to balance mechanical properties. While the above values for each individual element should always be respected, in some embodiments the sum of the elements must be considered. In other embodiments, it is recommended that %Be + %Sc be ≥ 0.005 wt%, ≥ 0.05 wt%, ≥ 0.2 wt%, ≥ 1.2 wt%, or ≥ 1.4 wt%. As expected, this also applies to each individual element, so in some applications, excessively high sums of these elements may have a detrimental effect. In other embodiments, it is recommended that %Be + %Sc be ≤ 8 wt%, ≤ 4 wt%, ≤ 2.5 wt%, ≤ 1.9 wt%, ≤ 1.4 wt%, ≤ 0.9 wt%, or ≤ 0.4 wt%. For some applications, the sum of %Cu + %Ni + %Co + %Zn + %Mn + %Si + %Cr + %Nb may be important, and different levels are recommended for different embodiments of improved mechanical properties. While the values above for each individual element should always be respected, in some embodiments the sum of the elements must be taken into account. In other embodiments, it is recommended that %Cu + %Ni + %Co + %Zn + %Mn + %Si + %Cr + %Nb be ≥ 0.05 wt%, ≥ 0.6 wt%, ≥ 1.1 wt%, ≥ 2.2 wt%, ≥ 5.2 wt%, ≥ 8.2 wt%, or ≥ 11 wt%. As expected, as is true for each individual element, excessively high sums of these elements may have a detrimental effect in some applications. In other embodiments it is recommended that %Cu+%Ni+%Co+%Zn+%Mn+%Si+%Cr+%Nb be equal to or less than 29% by weight, equal to or less than 19% by weight, equal to or less than 2% by weight, equal to or less than 9% by weight, equal to or less than 4% by weight, equal to or less than 2% by weight, or equal to or less than 0.4% by weight. In different embodiments, the sum of %Ge + %Ce + %Fe + %Pb + %V + %Mo + %W + %Ta may be important, and different levels are recommended. While the values above for each individual element should always be respected, in some embodiments the sum of the elements should be taken into account. In other embodiments, it is recommended that %Ge + %Ce + %Fe + %Pb + %V + %Mo + %W + %Ta be ≥ 0.05 wt%, ≥ 0.6 wt%, ≥ 1.1 wt%, ≥ 2.2 wt%, ≥ 5.2 wt%, ≥ 8.2 wt%, or ≥ 11 wt%. As expected, as is true for each individual element, excessively large sums of these elements may have adverse effects in some applications. In other embodiments, it is recommended that %Ge + %Ce + %Fe + %Pb + %V + %Mo + %W + %Ta be 29 wt% or less, 19 wt% or less, 14 wt% or less, 10 wt% or less, 4 wt% or less, 2 wt% or less, or 0.4 wt% or less. In some applications, the sum of %Zr + %Hf + %Ti may be important, and different levels are recommended in different embodiments. While the values above for each individual element should always be respected, in some embodiments the sum of the elements must be considered. In other embodiments, it is recommended that %Zr + %Hf + %Ti be 0.005 wt.% or more, 0.05 wt.% or more, 0.2 wt.% or more, 1.2 wt.% or more, or 1.4 wt.% or more. As expected, this also applies to each individual element, so in some applications, excessively high sums of these elements may have a negative effect. In other embodiments, it is recommended that %Zr + %Hf + %Ti be 8 wt.% or less, 4 wt.% or less, 2.5 wt.% or less, 1.9 wt.% or less, 1.4 wt.% or less, 0.9 wt.% or less, or 0.4 wt.% or less. In some applications, the sum of %B + %N + %O + %C may be important, and different levels are recommended in different embodiments to balance mechanical properties. While the values above for each individual element should always be respected, in some embodiments, the sum of the elements must be considered. In other embodiments, it is recommended that %B + %N + %O + %C be ≥ 0.005 wt%, ≥ 0.05 wt%, ≥ 0.2 wt%, ≥ 1.2 wt%, or ≥ 1.4 wt%. As expected, this also applies to each individual element, so in some applications, excessively high sums of these elements may have a detrimental effect. In other embodiments, it is recommended that %B + %N + %O + %C be ≤ 8 wt%, ≤ 4 wt%, ≤ 2.5 wt%, ≤ 1.9 wt%, ≤ 1.4 wt%, ≤ 0.9 wt%, or ≤ 0.4 wt%. For some applications, the sum of %Bi + %Ga + %Cd + %In + %Sn + %Cs + %Rb may be important, and different levels are recommended in different embodiments to balance mechanical properties. While the values above for each individual element should always be respected, in some embodiments the sum of the elements should be considered. In other embodiments, it is recommended that %Bi + %Ga + %Cd + %In + %Sn + %Cs + %Rb be ≥ 0.05 wt%, ≥ 0.6 wt%, ≥ 1.1 wt%, ≥ 2.2 wt%, ≥ 5.2 wt%, ≥ 8.2 wt%, or ≥ 11 wt%. As expected, as is true for each individual element, excessively large sums of these elements may have a detrimental effect in some applications. In another embodiment, it is recommended that %Bi+%Ga+%Cd+%In+%Sn+%Cs+%Rb be 29 wt% or less, 19 wt% or less, 14 wt% or less, 9 wt% or less, 4 wt% or less, 2 wt% or less, or 0.4 wt% or less. In some applications, the sum of %Se + %Te + %As + %Sb may be important, and different levels are recommended in different embodiments to balance mechanical properties. While the above values for each individual element should always be respected, in some embodiments, the sum of the elements must be considered. In other embodiments, it is recommended that %Se + %Te + %As + %Sb be 0.005 wt.% or more, 0.05 wt.% or more, 0.2 wt.% or more, 1.2 wt.% or more, or 1.4 wt.% or more. As expected, this also applies to each individual element, so in some applications, excessively large sums of these elements may have a negative effect. In other embodiments, it is recommended that %Se + %Te + %As + %Sb be 8 wt.% or less, 4 wt.% or less, 2.4 wt.% or less, 1.9 wt.% or less, 1.4 wt.% or less, 0.9 wt.% or less, or 0.4 wt.% or less. In some embodiments, the sum of %Nd + %Gd + %La can be important, and different levels are recommended for different embodiments to balance mechanical properties. While the values above for each individual element should always be respected, in some embodiments the sum of the elements must be considered. In other embodiments, it is recommended that %Nd + %Gd + %La be 0.05 wt.% or more, 0.6 wt.% or more, 1.1 wt.% or more, 2.2 wt.% or more, 5.2 wt.% or more, 8.2 wt.% or more, or 11 wt.% or more. As expected, this also applies to each individual element, and in some applications, excessively high sums of these elements may have adverse effects. In other embodiments, it is recommended that %Nd + %Gd + %La be 29 wt.% or less, 19 wt.% or less, 14 wt.% or less, 9 wt.% or less, 4 wt.% or less, 2 wt.% or less, or 0.4 wt.% or less. In some embodiments, the sum of %Tm + %Tb + %Dy + %Yb + %Er + %Sm + %Pr + %Ho + %Lu + %Th may be important, and different levels are recommended for different embodiments. While the values above for each individual element should always be respected, in some embodiments the sum of the elements should be considered. In other embodiments, it is recommended that %Tm + %Tb + %Dy + %Yb + %Er + %Sm + %Pr + %Ho + %Lu + %Th be 0.05 wt.% or more, 0.6 wt.% or more, 1.1 wt.% or more, 2.2 wt.% or more, 5.2 wt.% or more, 8.2 wt.% or more, or 11 wt.% or more. As expected, as is true for each individual element, excessively large sums of these elements may have adverse effects in some applications. In another embodiment, it is recommended that %Tm+%Tb+%Dy+%Yb+%Er+%Sm+%Pr+%Ho+%Lu+%Th be 29 wt% or less, 19 wt% or less, 14 wt% or less, 9 wt% or less, 4 wt% or less, 2 wt% or less, or 0.4 wt% or less. Further embodiments of the magnesium alloys disclosed above are detailed below: In one set of embodiments, lightweight structures can be obtained using magnesium alloys having the following compositions, all percentages being by weight: %Li:2.2‐29 %Ca + %Al = 0‐14; %Nd+%Gd+%La+%Y+%Be+%Sc=2.1‐19; %Zr+%Hf+%Ti=0‐3.5; %Cu+%Ni+%Co+%Zn+%Mn+%Si+%Cr+%Nb=0‐9; %Ge+%Ce+%Fe+%Pb+%V+%Mo+%W+%Ta=0‐9; %B+%N+%O+%C=0‐1.5; %Bi+%Ga+%Cd+%In+%Sn+%Cs+%Rb=0‐12; %Se+%Te+%As+%Sb=0‐1.5; %Tm+%Tb+%Dy+%Yb+%Er+%Sm+%Pr+%Ho+%Lu+%Th=0‐14; The remainder is made up of %Mg and trace elements. In some embodiments, the composition describes the overall composition of the material, and may include different phases or powders in different compositions. In some embodiments, the composition describes only the composition of the powder as it ultimately becomes when mixed with other powders. In some embodiments, the composition describes only the phases of the material. For some applications, the sum of %Ca + %Al may be important, and different levels are recommended in different embodiments to balance mechanical properties. While the values above for each individual element should always be respected, in some embodiments the sum of the elements must be considered. In other embodiments, it is recommended that %Ca + %Al be ≥ 0.05 wt%, ≥ 0.6 wt%, ≥ 1.1 wt%, ≥ 2.2 wt%, ≥ 5.2 wt%, ≥ 8.2 wt%, or ≥ 11 wt%. As expected, this also applies to each individual element, so for some applications, excessively high sums of these elements may have a detrimental effect. In other embodiments, it is recommended that %Ca + %Al be ≤ 29 wt%, ≤ 19 wt%, ≤ 14 wt%, ≤ 9 wt%, ≤ 4 wt%, ≤ 2 wt%, or ≤ 0.4 wt%. In some applications for balancing mechanical properties, the sum of %Nd + %Gd + %La + %Y + %Be + %Sc may be important, and different levels are recommended for different embodiments for balancing mechanical properties. While the above values for each individual element should always be respected, in some embodiments, the sum of the elements must be considered. In other embodiments, it is recommended that %Nd + %Gd + %La + %Y + %Be + %Sc be 0.5 wt% or more, 1.1 wt% or more, 2.1 wt% or more, 5.2 wt% or more, 8.2 wt% or more, 11 wt% or more, or 16 wt% or more. As expected, this also applies to each individual element, so in some applications, excessively large sums of these elements may have a negative effect. In other embodiments, it is recommended that %Nd + %Gd + %La + %Y + %Be + %Sc be 44 wt% or less, 34 wt% or less, 24 wt% or less, 19 wt% or less, 14 wt% or less, 9 wt% or less, or 4 wt% or less. In some applications, the sum of %Zr + %Hf + %Ti may be important, and different levels are recommended in different embodiments to balance mechanical properties. While the values above for each individual element should always be respected, in some embodiments the sum of the elements must be considered. In other embodiments, it is recommended that %Zr + %Hf + %Ti be 0.005 wt.% or more, 0.05 wt.% or more, 0.2 wt.% or more, 1.2 wt.% or more, or 1.4 wt.% or more. As expected, this also applies to each individual element, so in some applications, excessively high sums of these elements may have a detrimental effect. In other embodiments, it is recommended that %Zr + %Hf + %Ti be 8 wt.% or less, 3.5 wt.% or less, 2.5 wt.% or less, 1.9 wt.% or less, 1.4 wt.% or less, 0.9 wt.% or less, or 0.4 wt.% or less. In some embodiments, the sum of %Cu + %Ni + %Co + %Zn + %Mn + %Si + %Cr + %Nb can be important, and different levels are recommended for different embodiments. While the values above for each individual element should always be respected, in some embodiments the sum of the elements should be taken into account. In other embodiments, it is recommended that %Cu + %Ni + %Co + %Zn + %Mn + %Si + %Cr + %Nb be ≥ 0.05 wt%, ≥ 0.6 wt%, ≥ 1.1 wt%, ≥ 2.2 wt%, ≥ 5.2 wt%, ≥ 8.2 wt%, or ≥ 11 wt%. As expected, as is true for each individual element, excessively high sums of these elements may have a detrimental effect in some applications. In another embodiment it is recommended that %Cu+%Ni+%Co+%Zn+%Mn+%Si+%Cr+%Nb be equal to or less than 29% by weight, equal to or less than 19% by weight, equal to or less than 14% by weight, equal to or less than 9% by weight, equal to or less than 4% by weight, equal to or less than 2% by weight, or equal to or less than 0.4% by weight. In some embodiments, the sum of %Ge + %Ce + %Fe + %Pb + %V + %Mo + %W + %Ta can be important, with different levels recommended for different embodiments to balance mechanical properties. While the values above for each individual element should always be respected, in some embodiments the sum of the elements should be considered. In other embodiments, it is recommended that %Ge + %Ce + %Fe + %Pb + %V + %Mo + %W + %Ta be ≥ 0.05 wt%, ≥ 0.6 wt%, ≥ 1.1 wt%, ≥ 2.2 wt%, ≥ 5.2 wt%, ≥ 8.2 wt%, or ≥ 11 wt%. As expected, as is true for each individual element, excessively large sums of these elements may have a detrimental effect in some applications. In other embodiments, it is recommended that %Ge+%Ce+%Fe+%Pb+%V+%Mo+%W+%Ta be 29 wt% or less, 19 wt% or less, 14 wt% or less, 9 wt% or less, 4 wt% or less, 2 wt% or less, or 0.4 wt% or less. In some applications, the sum of %B + %N + %O + %C may be important, and different levels are recommended in different embodiments to balance mechanical properties. While the values above for each individual element should always be respected, in some embodiments, the sum of the elements must be considered. In other embodiments, it is recommended that %B + %N + %O + %C be ≥ 0.005 wt%, ≥ 0.05 wt%, ≥ 0.2 wt%, ≥ 1.2 wt%, or ≥ 1.4 wt%. As expected, this also applies to each individual element, so in some applications, excessively high sums of these elements may have a detrimental effect. In other embodiments, it is recommended that %B + %N + %O + %C be ≤ 8 wt%, ≤ 4 wt%, ≤ 2.5 wt%, ≤ 1.5 wt%, ≤ 0.9 wt%, ≤ 0.4 wt%, or ≤ 0.09 wt%. For some applications, the sum of %Bi + %Ga + %Cd + %In + %Sn + %Cs + %Rb may be important, and different levels are recommended to balance the mechanical properties. While the values above for each individual element should always be respected, in some embodiments the sum of the elements should be considered. In other embodiments, it is recommended that %Bi + %Ga + %Cd + %In + %Sn + %Cs + %Rb be ≥ 0.05 wt%, ≥ 0.6 wt%, ≥ 1.1 wt%, ≥ 2.2 wt%, ≥ 5.2 wt%, ≥ 8.2 wt%, or ≥ 11 wt%. As expected, as is true for each individual element, excessively high sums of these elements may have a detrimental effect in some applications. In another embodiment, it is recommended that %Bi+%Ga+%Cd+%In+%Sn+%Cs+%Rb be 29 wt% or less, 19 wt% or less, 12 wt% or less, 9 wt% or less, 4 wt% or less, 2 wt% or less, or 0.4 wt% or less. In some applications, the sum of %Se + %Te + %As + %Sb may be important, and different levels are recommended in different embodiments to balance mechanical properties. While the values above for each individual element should always be respected, in some embodiments, the sum of the elements must be considered. In other embodiments, it is recommended that %Se + %Te + %As + %Sb be 0.005 wt.% or more, 0.05 wt.% or more, 0.2 wt.% or more, 2 wt.% or more, or 1.4 wt.% or more. As expected, this also applies to each individual element, so in some applications, excessively large sums of these elements may have a negative effect. In other embodiments, it is recommended that %Se + %Te + %As + %Sb be 8 wt.% or less, 4 wt.% or less, 2.5 wt.% or less, 1.5 wt.% or less, 0.9 wt.% or less, 0.4 wt.% or less, or 0.09 wt.% or less. In some applications, the sum of %Tm + %Tb + %Dy + %Yb + %Er + %Sm + %Pr + %Ho + %Lu + %Th may be important for balancing mechanical properties, and different levels are recommended in different embodiments. While the values above for each individual element should always be respected, in some embodiments the sum of the elements should be considered. In other embodiments, it is recommended that %Tm + %Tb + %Dy + %Yb + %Er + %Sm + %Pr + %Ho + %Lu + %Th be ≥ 0.05 wt%, ≥ 0.6 wt%, ≥ 1.1 wt%, ≥ 2.2 wt%, ≥ 5.2 wt%, ≥ 8.2 wt%, or ≥ 11 wt%. As expected, as is true for each individual element, excessively high sums of these elements may have a detrimental effect in some applications. In another embodiment, it is recommended that %Tm+%Tb+%Dy+%Yb+%Er+%Sm+%Pr+%Ho+%Lu+%Th be 29 wt% or less, 19 wt% or less, 14 wt% or less, 9 wt% or less, 4 wt% or less, 2 wt% or less, or 0.4 wt% or less. In some embodiments, the sum of %Ca + %Al + %Ti can be important, and different levels are recommended for different applications to balance mechanical properties. While the values above for each individual element should always be respected, in some embodiments the sum of the elements must be considered. In other embodiments, it is recommended that %Ca + %Al + %Ti be ≥ 0.05 wt%, ≥ 0.6 wt%, ≥ 1.1 wt%, ≥ 2.2 wt%, ≥ 5.2 wt%, ≥ 8.2 wt%, or ≥ 11 wt%. As expected, this also applies to each individual element, so in some applications, excessively high sums of these elements may have a detrimental effect. In other embodiments, it is recommended that %Ca + %Al + %Ti be ≤ 29 wt%, ≤ 19 wt%, ≤ 14 wt%, ≤ 9 wt%, ≤ 4 wt%, ≤ 2 wt%, or ≤ 0.4 wt%. It has been discovered that certain applications require specific types of corrosion resistance. This is insufficient if magnesium alloys contain nominal 0% or are completely devoid of certain elements, such as %Fe, %Ni, and %Cu. However, special measures must be taken to ensure that these trace elements are present at sufficiently low levels. Unfortunately, even in magnesium alloys without intentionally added %Cu, %Fe, or %Ni, residual trace elements are present. While this is not a problem for many applications, in some applications the adverse effects can be surprising, necessitating costly measures to prevent excessive trace elements from being present. However, care must be taken to remove excessive trace elements, as excessive removal can impair the alloy's functionality for the application. In some embodiments, %Fe is recommended to be between 0.00001 and 0.005% by weight. In other embodiments, %Fe is recommended to be less than 0.19%, less than 0.09%, less than 0.009%, less than 0.004%, less than 0.0009%, or even less than 0.0004% by weight. In other embodiments, it is recommended that %Fe be greater than 0.0000012 wt%, or greater than 0.000006 wt%, or greater than 0.00001 wt%, or greater than 0.00006 wt%, or greater than 0.00012 wt%, or greater than 0.0012 wt%, or greater than 0.012 wt%. In some embodiments, it is recommended that %Ni be between 0.00001 wt% and 0.005 wt%. In some embodiments, it is recommended that %Ni be less than 0.19 wt%, less than 0.09 wt%, less than 0.009 wt%, less than 0.004 wt%, less than 0.0009 wt%, or even less than 0.0004 wt%. In other embodiments, it is recommended that %Ni be greater than 0.0000012 wt%, or greater than 0.000006 wt%, or greater than 0.00001 wt%, or greater than 0.00006 wt%, or greater than 0.00012 wt%, or greater than 0.0012 wt%, or greater than 0.012 wt%. In one embodiment, it is recommended that %Cu be between 0.00001 wt% and 0.005 wt%.In some embodiments, it is recommended that %Cu be less than 0.19 wt%, less than 0.09 wt%, less than 0.009 wt%, less than 0.004 wt%, less than 0.0009 wt%, or even less than 0.0004 wt%. In other embodiments, it is recommended that %Cu be greater than 0.0000012 wt%, or greater than 0.000006 wt%, or greater than 0.00001 wt%, or greater than 0.00006 wt%, or greater than 0.00012 wt%, or greater than 0.0012 wt%, or greater than 0.012 wt%. In some embodiments, it is recommended that %Fe+%Cu+%Ni be between 0.00001 wt% and 0.005 wt%. In some embodiments it is recommended that %Fe+%Cu+%Ni be less than 0.19 wt%, less than 0.09 wt%, less than 0.009 wt%, less than 0.004 wt%, less than 0.0009 wt%, or even less than 0.0004 wt%, and in other embodiments it is recommended that %Fe+%Cu+%Ni be greater than 0.0000012 wt%, or greater than 0.000006 wt%, or greater than 0.00001 wt%, or greater than 0.00006 wt%, or greater than 0.00012 wt%, or greater than 0.0012 wt%, or greater than 0.012 wt%. Further embodiments of the magnesium alloys disclosed above are detailed below: In one set of embodiments, lightweight structures can be obtained using magnesium alloys having the following compositions, all percentages being by weight: %Li:1.3‐16 %Ca+%Y+%Al=2.5‐19; %Be+%Sc:0‐0.5; %Zr+%Hf+%Ti=0‐1.5; %Cu+%Ni+%Co+%Zn+%Mn+%Si+%Cr+%Nb=0‐6; %Ge+%Ce+%Ni+%Pb+%V+%Mo+%W+%Ta=0‐3; %B+%N+%O+%C=0‐1.5; %Bi+%Ga+%Cd+%In+%Sn+%Cs+%Rb=0‐8; %Se+%Te+%As+%Sb=0‐1.4; %Nd+%Gd+%La=0‐4; %Tm+%Tb+%Dy+%Yb+%Er+%Sm+%Pr+%Ho+%Lu+%Th=0‐3; The remainder is made up of %Mg and trace elements. In some embodiments, the composition describes the overall composition of the material, and may include different phases or powders in different compositions. In some embodiments, the composition describes only the composition of the powder as it ultimately becomes when mixed with other powders. In some embodiments, the composition describes only the phases of the material. Further embodiments of the magnesium alloys disclosed above are detailed below: In one set of embodiments, lightweight structures can be obtained using magnesium alloys having the following compositions, all percentages being by weight: %Li:4‐20 %Ca+%Y+%Al=2‐15; %Be+%Sc:0‐0.3; %Zr+%Hf+%Ti=0‐1.2; %Cu+%Ni+%Co+%Zn+%Mn+%Si+%Cr+%Nb=0‐5; %Ge+%Ce+%Ni+%Pb+%V+%Mo+%W+%Ta=0‐2; %B+%N+%O+%C=0‐1.1; %Bi+%Ga+%Cd+%In+%Sn+%Cs+%Rb=0‐6; %Se+%Te+%As+%Sb=0‐1.1; %Nd+%Gd+%La=0‐3; %Tm+%Tb+%Dy+%Yb+%Er+%Sm+%Pr+%Ho+%Lu+%Th=0‐2.5; The remainder is made up of %Mg and trace elements. In some embodiments, the composition describes the overall composition of the material, and may include different phases or powders in different compositions. In some embodiments, the composition describes only the composition of the powder as it ultimately becomes when mixed with other powders. In some embodiments, the composition describes only the phases of the material. Further embodiments of the magnesium alloys disclosed above are detailed below. In this case, the alloys can be considered aluminum-lithium alloys. In one set of embodiments, lightweight structures can be obtained using magnesium alloys having the following compositions, where all percentages are by weight: %Li:2.3‐28 %Ca+%Y+%Mg+%Zn+%Cu=4.5‐25; %Be+%Sc:0‐0.5; %Zr+%Hf+%Ti=0‐1.5; %Ni+%Co+%Mn+%Si+%Cr+%Nb=0‐6; %Ge+%Ce+%Ni+%Pb+%V+%Mo+%W+%Ta=0‐3; %B+%N+%O+%C=0‐1.5; %Bi+%Ga+%Cd+%In+%Sn+%Cs+%Rb=0‐8; %Se+%Te+%As+%Sb=0‐1.4; %Nd+%Gd+%La=0‐4; %Tm+%Tb+%Dy+%Yb+%Er+%Sm+%Pr+%Ho+%Lu+%Th=0‐3; The remainder is made up of %Al and trace elements. In some embodiments, the composition describes the overall composition of the material, and may include different phases or powders in different compositions. In some embodiments, the composition describes only the composition of the powder as it ultimately becomes when mixed with other powders. In some embodiments, the composition describes only the phases of the material. Further embodiments of the magnesium alloys disclosed above are detailed below. In this case, the alloys can be considered aluminum-lithium alloys. In one set of embodiments, lightweight structures can be obtained using magnesium alloys having the following compositions, where all percentages are by weight: %Li:5.5‐30 %Ca+%Y+%Mg+%Zn+%Cu=4.0‐28; %Be+%Sc:0‐0.3; %Zr+%Hf+%Ti=0‐1.2; %Ni+%Co+%Mn+%Si+%Cr+%Nb=0‐5; %Ge+%Ce+%Ni+%Pb+%V+%Mo+%W+%Ta=0‐2; %B+%N+%O+%C=0‐1.1; %Bi+%Ga+%Cd+%In+%Sn+%Cs+%Rb=0‐6; %Se+%Te+%As+%Sb=0‐1.1; %Nd+%Gd+%La=0‐3; %Tm+%Tb+%Dy+%Yb+%Er+%Sm+%Pr+%Ho+%Lu+%Th=0‐2.5; The remainder is made up of %Al and trace elements. In some embodiments, the composition describes the overall composition of the material, and may include different phases or powders in different compositions. In some embodiments, the composition describes only the composition of the powder as it ultimately becomes when mixed with other powders. In some embodiments, the composition describes only the phases of the material. Any of the above magnesium alloy embodiments can be combined in any combination with any other embodiment described herein, to the extent that the characteristics of each are compatible. Use of terms such as "less than," "greater than," "greater than or equal to," "less than or equal to," "from," "to," "at least," "greater than," "less than," and the like, expresses a range that is inclusive of the recited numbers and that can be divided into subranges. One embodiment refers to the use of a magnesium alloy to manufacture a metallic or at least partially metallic component. In some embodiments, the alloy is used in particulate form. In another embodiment, the alloys disclosed herein are microstructurally defined by a grain size of 400 micrometers or less, 190 micrometers or less, 90 micrometers or less, 40 micrometers or less, 18 micrometers or less, 8 micrometers or less, 4 micrometers or less, 0.9 micrometers or less, or 0.4 micrometers or less, as measured by ASTM E112-13. In another embodiment, the alloys disclosed herein are microstructurally defined by at least 11 volume percent, at least 28 volume percent, at least 42 volume percent, at least 52 volume percent, at least 72 volume percent, at least 82 volume percent, or at least 96 volume percent of a cubic structure. In another embodiment, the percentage of cubic structure disclosed above is by weight. In another embodiment, the alloys disclosed herein are microstructurally defined by having a strengthening phase. A reinforcing phase is a particle that is harder than the macrohardness of the alloy, taking into account the matrix reinforcing phase and all other components. The reinforcing phase is also harder than the matrix, precipitates, intermetallic compounds, secondary phases, and even Laves phases. In another embodiment, the reinforcing phase has an equivalent diameter of at least 400 micrometers, 190 micrometers, 90 micrometers, 40 micrometers, 18 micrometers, 8 micrometers, 4 micrometers, 1.9 micrometers, 900 nm, 400 nm, 190 nm, or 90 nm. Unless otherwise specified, the equivalent diameter is the diameter of a particle that imparts the same geometric, optical, electrical, or aerodynamic behavior to a spherical particle under investigation. In some embodiments, the material is characterized by a high structural resistance to fire. This affects all material types for this application, and therefore also the individual metal alloys. Existing magnesium alloys with fire resistance are characterized by a higher density than pure magnesium at certain temperatures. In fact, the density of magnesium is 1.74 g / cm at 20 °C and 1 atm. 3whereas the density of existing improved refractory magnesium alloys is 1.8 g / cm at this temperature. 3 This was believed to be the only possible way, since refractory properties were only related to increased oxidation resistance at high temperatures due to reduced reactivity, which in the case of magnesium had an implicit density increase relative to pure magnesium. One way to parameterize some of the novelty of the alloys disclosed herein is by density. In another embodiment, the density of the alloys disclosed in this document is 1.79 g / cm (at 20°C and 1 atm). 3 Below, 1.74g / cm 3 Below, 1.72g / cm 3 Below, 1.68g / cm 3 Below, 1.62g / cm 3 Below, 1.58g / cm 3 Below, 1.52g / cm 3 or less, or 1.44 g / cm 3 Any of the above-disclosed alloys having any of the densities disclosed in this paragraph are, in some embodiments, alloys that exhibit good fire resistance. What is understood to be good fire resistance varies depending on the application. In one group of embodiments, significant resistance to combustion is greater than 10.5 Btu / ft as described in FAR 25.853 Part 25 Appendix F Part 2. 2This is expected for combustion at 1900°F with a heat flux of 1 / sec. In some embodiments, the results of testing are that the alloy does not burn when melted, and in some embodiments, the alloy self-extinguishes. In other embodiments, testing has shown that the ignition temperature is greater than 582°C, greater than 592°C, greater than 602°C, greater than 622°C, greater than 652°C, greater than 682°C, greater than 692°C, greater than 702°C, greater than 712°C, greater than 752°C, greater than 782°C, or greater than 802°C. The alloys disclosed herein achieve excellent ignition temperatures despite their very low density. In other embodiments, testing has shown that the ignition temperature is greater than 852°C, greater than 912°C, greater than 952°C, greater than 1012°C, greater than 1122°C, or greater than 1222°C. In one set of embodiments, good fire resistance is considered to be the result of the flammability tests set forth in IGC 04.24.106, which corresponds to US FAA, CS25 / JAR 25 / FAR 25 §25-853. In one embodiment, the alloys disclosed herein pass all tests. The challenge of having a highly fire-resistant structure can be solved by the right composition and the right microstructure. Fire-resistant structures appear to be achievable if the associated components also have good thermal shock resistance. This is because structural components are often exposed to high thermal shocks when heated or extinguished. Since thermal shock exposure is inversely proportional to the thermal conductivity (1-Poisson's coefficient) and directly proportional to the coefficient of thermal expansion and Young's modulus (also referred to herein as the elastic modulus), in a comparison between materials, thermal shock resistance can be expressed as: [Brief explanation of the drawings]
[0003] [Figure 1] This is one embodiment of the present invention. [Figure 2] This is one embodiment of the present invention. [Figure 3] It is a 1:2 scale representation of the b-pillar with its four main tubular parts.
[0004]
number
[0005]
number
[0006] Another aspect refers to a material comprising organic and inorganic portions, which may be molded into elements using molding techniques, such as any of the methods disclosed later herein. The inventors have discovered that in some embodiments, it is possible to mold a mixture of organic and inorganic elements as long as certain characteristic temperatures are appropriately selected. In one embodiment, the glass transition temperature, removal temperature, or degradation temperature, particularly in the case of a relationship between the melting point of at least one element of the inorganic portion and the characteristic temperature of at least one element of the organic portion, such as the heat deflection temperature, are appropriately selected as disclosed later herein. In one embodiment, the material is a moldable material. In one embodiment, the material is a material to be molded. In some embodiments, the organic portion is only transient until the desired shape is reached, and is then at least partially removed. In some embodiments, the organic portion is functional in the molded material and is therefore at least partially retained. The organic portion of the material to be molded may comprise one or more phases and / or elements. In one embodiment, the organic portion comprises an organic phase. In various embodiments, the organic portion of the material comprises at least one element, at least two elements, at least one related element, and even at least two related elements. In one embodiment, the organic phase comprises at least a polymer. In various embodiments, the polymer is a photopolymer, a thermosetting polymer, a thermoplastic polymer, and even an elastomeric polymer. The inventors have discovered that in some embodiments, to obtain the desired mechanical properties of the molded material, the polymer should not be a crystalline polymer. In one embodiment, the molding method comprises at least one step of additively manufacturing the organic portion of the material comprising elements that "harden" when exposed to "suitable radiation," as disclosed later herein. Furthermore, in various embodiments, the "hardenable" material may further comprise a reaction accelerator, a photochromic compound (e.g., azobenzene, spiropyran, stilbene, fulgites, diarylethene, etc.) that can be sensitized when exposed to "suitable radiation," a chromophore that can generate heat when exposed to "suitable radiation," and even a thermal initiator. In some embodiments, as for example when some elements are fabricated in which the organic portion is at least partially retained, and also as for another example in some elements in which the lowest melting point metallic phase among the associated phases has a metallic phase with a slightly higher melting point, the inventors have discovered that it is crucial to select an organic phase that has a deflection temperature in different embodiments greater than 120°C, greater than 185°C, greater than 230°C, greater than 260°C, greater than 282°C, greater than 305°C, greater than 355°C, greater than 410°C, greater than 430°C, and even greater than 505°C, as measured according to American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi]. In one alternative embodiment, the deflection temperature values disclosed above are measured according to ISO 75-1, 2013 Method B testing at a load of 0.45 MPa. The inventors have discovered that in some applications it is crucial to select an organic phase comprising components that have deflection temperatures in different embodiments greater than 81°C, greater than 123°C, greater than 153°C, greater than 173°C, greater than 188°C, greater than 203°C, greater than 237°C, greater than 273°C, greater than 287°C, and even greater than 320°C as measured according to ASA D648-07 at a load of 1.82 MPa. In an alternative embodiment, the organic phase has a deflection temperature of greater than 40°C, greater than 61°C, greater than 76°C, greater than 94°C, greater than 102°C, greater than 118°C, greater than 137°C, greater than 143°C, and even greater than 168°C obtained by either ASA D648-07 test conditions at a load of 1.82 MPa, ASA D648-07 test conditions at a load of 5.0 MPa, ASA D648-07 test conditions at a load of 8.0 MPa, or by ISO 75-1:2013 Method A testing at a load of 1.8 MPa. In some applications, the inventors have found it is crucial to select an organic phase comprising elements that have a Vicat softening temperature above 120°C, above 185°C, above 230°C, above 260°C, above 282°C, above 305°C, above 355°C, above 410°C, above 430°C, and even above 505°C.The test conditions for deflection temperature and Vicat softening temperature are disclosed at the end of this document. In some materials, certain elements or phases may be present in very small amounts within the organic portion of the material; in some instances, their presence is unintended and therefore irrelevant, while in other instances, their presence has a distinct functionality and therefore is relevant for some properties but not others. In some embodiments, it is possible to define the relevance of a phase or element of the organic portion in terms of the amount of such a type within the organic portion. Relevant elements or phases within the organic portion of a material are, in different embodiments, elements or phases that are at least 0.06%, at least 0.6%, at least 1.2%, at least 2.6%, at least 6%, at least 11%, at least 21%, and even 36% by weight of the organic portion of the material. In alternative embodiments, the percentages disclosed above refer to weight percentages relative to the weight of the material. In an alternative embodiment, the percentages disclosed above are by volume. In some embodiments, the above is a product of several elements, where the organic portion of the material is at least partially retained after the material is molded. Alternatively, in some manufactured elements having a metallic phase in the inorganic portion of the material, the lowest melting point metallic phase among the associated phases has a slightly higher melting point compared to the other associated metallic phases. The inventors have discovered that in some applications, it is crucial to select an organic phase with an associated element that has a deflection temperature (HDT) in different embodiments greater than 120°C, greater than 185°C, greater than 230°C, greater than 260°C, greater than 282°C, greater than 305°C, greater than 355°C, greater than 410°C, greater than 430°C, and even greater than 505°C, as measured according to the American Society for Testing and Materials (ASTM) D648-07 method at a load of 0.46 MPa (66 psi). Test conditions for determining deflection temperatures are disclosed at the end of this document. In an alternative embodiment, the deflection temperature values disclosed above are measured according to ISO 75-1:2013 Method B test at a load of 0.45 MPa. The inventors have discovered that in some applications it is crucial to select an organic phase with associated components that have a deflection temperature in different embodiments greater than 81°C, greater than 123°C, greater than 153°C, greater than 173°C, greater than 188°C, greater than 203°C, greater than 237°C, greater than 273°C, greater than 287°C, and even greater than 320°C, measured according to ASATM D648-07 at a load of 1.82 MPa. Test conditions for specifying deflection temperatures are disclosed at the end of this document. In alternative embodiments, preferred are organic phases with associated components having deflection temperatures of greater than 40°C, greater than 61°C, greater than 76°C, greater than 94°C, greater than 102°C, greater than 118°C, greater than 137°C, greater than 143°C, and even greater than 168°C obtained according to either ASATM D648-07 test conditions at a load of 1.82 MPa, ASATM D648-07 test conditions at a load of 5.0 MPa, ASATM D648-07 test conditions at a load of 8.0 MPa, or according to ISO 75-1:2013 Method A testing at a load of 1.8 MPa.The inventors have proposed, in different embodiments for some applications, polyphenylene sulfone (PPS), aromatic polyimide (PI), polyether sulfone (PES), polyetherimide (PEI), polyether ketone (PEK), polyether ketone ketone (PEKK), ethylene propylene diene monomer (EPDM), polysulfone (PSU), polyacrylamide (PAM), polycarbonate (PC), polyether ether ketone (PEEK), polytetrafluoroethylene (PTFE), polyimide (PI), polyethylene naphthalate (PEN), ABS resin (ABS), polymethyl methacrylate (PMMA), polyphenylene sulfide (PPS), polyethylene terephthalate (PET), polybutylene The inventors have found that it is crucial to select an organic phase comprising related elements such as polybutylene terephthalate (PBT), polyamides (PA66, PA610, PA6, PA12), polypropylene (PP), phenol formaldehyde resins (PF), epoxy resins (EP), polyurethanes (PUR), polyester resins (UP), polymethylsiloxane (PDMS), polybenzimidazole (PBI), aromatic derivatives of polybenzimidazole, methacrylic acid with polyhydroxy groups, poly(hydroxybutyl) methacrylic acid, and in different embodiments, it is beneficial to select an organic phase comprising cyclic butylene terephthalate (CBT) and also anionic polyamides (APA-6). In some applications, particularly when manufacturing wind turbine blades and other large components, it is beneficial to use polymeric materials such as thermosetting polymers (such as epoxy resins) or powdered thermoplastic polymers. In the manufacture of large components, the inventors have discovered that when using thermoplastic polymers that can be joined by ultrasound, resistance or induction, etc., it is surprisingly possible to reach continuity, including continuous bonding between the metallic phases at the joint, when using molded materials obtained in accordance with the disclosures of this document.Examples include polyhydroxyethyl methacrylate (PHEMA), phthalonitrile, benzoxazine, bismaleimide, cyanate esters, polyester fiberglass systems, molding compounds, bulk molding compounds, polyurethanes, insulation, mattresses, coatings, adhesives, printing rollers, shoe soles, flooring, synthetic fibers, polyurethane polymers, vulcanized rubber, bakelite, phenol formaldehyde resins used in electrical insulators and plastic products, Duroplast, urea formaldehyde materials used in plywood, particle board and medium density fiberboard, melamine resins, diallyl phthalate (DAP), epoxy resins, polyimides, polycyanurates, molds or mold runners, and also polyester resins. For manufacturing purposes, the inventors have discovered that in some applications it is crucial to select an organic phase with associated components that have degradation temperatures in different embodiments greater than 120°C, greater than 185°C, greater than 230°C, greater than 260°C, greater than 282°C, greater than 305°C, greater than 355°C, greater than 410°C, greater than 430°C, and even greater than 505°C. Test conditions for identifying degradation temperatures are disclosed at the end of this document. In alternative embodiments, degradation temperatures can alternatively refer to temperatures obtained according to the test conditions of ASATM E1131-08 corresponding to a mass loss of 10%, 20%, 25%, 45%, 65%, and even greater than 65% by weight. The inventors have discovered that in some applications it is crucial to select an organic phase with associated components that has a removal temperature in different embodiments above 120°C, above 185°C, above 230°C, above 260°C, above 282°C, above 305°C, above 355°C, above 410°C, above 430°C, and even above 505°C. Test conditions specifying the removal temperature are disclosed at the end of this document. In alternative embodiments, the removal temperature can alternatively refer to the temperature obtained according to the test conditions of ACSTM E1131-08, but at a heating / cooling rate of 0.5°C / min, and with respect to the initial weight, the remaining organic phase weight in different embodiments is less than 49%, less than 34%, less than 24%, less than 14%, less than 9%, less than 4%, less than 2%, and even less than 0.4% by weight.In an alternative embodiment, the percentages disclosed above are by volume and refer to the volume loss in the organic phase. The inventors have discovered that in some applications, it is crucial to select an organic phase with associated components that has a deflection temperature well above 0.45 times the melting point (0.45*Tm, where temperature is in degrees Celsius) of the phase or component with the lowest melting point among the associated components / phases in the inorganic portion of the material in different embodiments, well above 0.65*Tm, well above 0.75*Tm, well above 0.85*Tm, and even well above Tm (Tm is the absolute temperature at which the initial liquid forms under equilibrium conditions; in the remainder of this document, equilibrium conditions apply as well unless otherwise indicated or clear). Deflection temperatures are measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi]. The inventors have found that in some applications it is crucial to select an organic phase with an associated component that has a glass transition temperature in different embodiments above 42° C., above 86° C., above 106° C., above 128° C., above 164° C., above 192° C., above 221° C., above 260° C., above 292° C., and even above 320° C. The inventors have found that in some applications it is crucial to select an organic phase with an associated component that is a thermoplastic polymer with a melting point in different embodiments above 165° C., above 196° C., above 218° C., above 236° C., above 254° C., above 286° C., above 319° C., above 354° C., above 386° C., and even above 410° C. In some applications, the inventors have discovered that it is crucial to select organic phases with associated components that have Vicat softening temperatures above 120° C., above 185° C., above 230° C., above 260° C., above 282° C., above 305° C., above 355° C., above 410° C., above 430° C., and even above 505° C. Test conditions for identifying Vicat softening temperatures are disclosed at the end of this document. In some embodiments, the inventors have discovered that what has been described above for phases also applies to moieties.More embodiments of organic phases / components that can be included in the material are disclosed later in this document, and test conditions are disclosed at the end of this document. A person will decide what type of molding technique to use for a given type of plastic or polymer system depending on the elements he wants to produce, as well as the number of such elements and other issues related to economy, which will also relate to the shape of the elements, other economic aspects and some other conditions, as well as the functionality and dimensional tolerances of the part he needs, and in this scenario it will be clear to him that he will have one or several possible molding techniques, and when these are clear to him he will have one or several possible molding techniques, and within this range he will have one or several molding techniques, and he can use several possible polymers, so through the molding technique he chooses, and with all the other conditions he understands, when he knows what is the relevant temperature for the polymer to give it the shape, he will therefore know what type of molding technique he should use and what is relevant for the degradation of the polymer, and so he will know without any doubt what temperature is relevant, and when he has decided that he will know what type of relationship to temperature he should require for the material by the means explained in this document, according to this disclosure. In some embodiments, it is very important that the organic portion of the material is not excessive. In various embodiments, the organic portion should be 68% or less, 48% or less, 38% or less, 34% or less, 28% or less, 24% or less, 18% or less, 14% or less, and even 8% or less by weight relative to the weight of the material. In other embodiments, the organic portion of the material should be sufficient to ensure functionality after molding, especially in applications where a high percentage of the organic portion remains in the molded material. In various embodiments, the organic portion of the material should be 12% or more, 16% or more, 22% or more, 26% or more, 32% or more, 42% or more, 52% or more, 62% or more, 72% or more, 82% or more, and even 92% or more by weight relative to the weight of the material. In alternative embodiments, it is the volume fraction that is relevant. In some embodiments, it is very important that the organic portion of the material is not excessive. In different embodiments, the organic portion should be 68% or less, 48% or less, 38% or less, 34% or less, 28% or less, 24% or less, 18% or less, 14% or less, 8% or less by volume relative to the volume of the material. In different embodiments, the organic portion of the material should be 12% or more, 16% or more, 22% or more, 26% or more, 32% or more, 42% or more, 52% or more, 62% or more, 72% or more, 82% or more, and even 92% or more by volume relative to the volume of the material. The inorganic portion of the material may comprise one or more phases and / or elements, and in some embodiments, the material may comprise only inorganic portions. In different embodiments, the inorganic portion of the material comprises at least one element, at least two elements, at least one related element, and even at least two related elements. In different embodiments, the inorganic portion comprises a metal, a metal alloy, at least one intermetallic phase, an alloy disclosed herein, such as any magnesium-based alloy, any magnesium-lithium alloy, and / or any aluminum-lithium alloy, and / or any low melting point magnesium-lithium alloy, and / or any low melting point aluminum-lithium alloy previously disclosed herein, ceramic, particles, hard particles, and even reinforcing fibers. In different embodiments, the inorganic portion is predominantly metal, predominantly any alloy disclosed herein, such as any magnesium-based alloy, and / or any magnesium-lithium alloy, and / or any aluminum-lithium alloy, and / or any low melting point magnesium-lithium alloy, and / or any low melting point aluminum-lithium alloy previously disclosed herein, and even predominantly ceramic. In different embodiments, the inorganic portion of the material is a metal matrix composite, an intermetallic compound, and even an intermetallic matrix composite. Any embodiment of the magnesium-based alloy and / or low melting point magnesium-lithium alloy disclosed herein can be combined with any embodiment referring to the inorganic portion of the material in any combination provided, and they are not mutually exclusive. In this document, unless otherwise indicated, the term "majority" refers to the predominant element in the described portion (organic portion, inorganic portion, metallic portion, ceramic portion, etc.; i.e., for example, a material may be comprised of 90% organic portion and 10% inorganic portion, and the inorganic portion may have 25% ceramic, 25% intermetallic compound, 30% metal alloy of any alloy disclosed herein such as any magnesium-based alloy previously disclosed herein and / or any low melting point magnesium-lithium alloy previously disclosed herein, and 20% other metallic elements, such as a material that may in some embodiments be described as having an inorganic portion having a majority of an alloy disclosed herein such as any magnesium-based alloy previously disclosed herein and / or any low melting point magnesium-lithium alloy previously disclosed herein; however, the total number of such metals may amount to only 3% of the material and still be the predominant element within the inorganic portion). In different embodiments, the percentages disclosed above may be by weight. While not sufficient to be the major component of the recited portion, they must be present in at least 35%, at least 46%, at least 52%, at least 62%, at least 77%, at least 86%, and even at least 96% by volume. In an alternative embodiment, the percentages disclosed above are by weight. The relevant component or phase among the inorganic portion of the material is an component or phase that is at least 0.06%, at least 0.6%, at least 1.2%, at least 2.6%, at least 6%, at least 11%, at least 21%, and even 36% by weight with respect to the inorganic portion of the material in different embodiments. In an alternative embodiment, the percentages disclosed above refer to percentages by weight with respect to the weight of the material. In an alternative embodiment, the percentages disclosed above are by volume. The inventors have discovered that in some embodiments, it is beneficial for the inorganic portion of the material to comprise at least one of the magnesium-based alloys disclosed herein, in one embodiment one of the magnesium-lithium alloys disclosed herein, in one embodiment any of the aluminum-lithium alloys disclosed herein, in one embodiment a low melting point aluminum-lithium alloy disclosed herein, or in one embodiment at least one of the low melting point magnesium-lithium alloys disclosed herein. In one embodiment, the magnesium-based alloy is in particulate form. In one embodiment, particulate form refers to powder form. In one embodiment, the low melting point lithium-magnesium alloy is in particulate form. In one embodiment, particulate form refers to powder form. In one particular aspect, the inventors have discovered that it is beneficial for the inorganic portion of the material to comprise at least two different magnesium alloys in the inorganic portion of the material. In different embodiments, at least one of the magnesium alloys has a lithium content of greater than 21%, greater than 36%, greater than 42%, greater than 52%, greater than 62%, greater than 72%, and even greater than 81% by weight. In an alternative embodiment, the percentages disclosed above are by volume. In some embodiments, particularly when the inorganic portion of the material comprises low melting point metal powders, the inventors have discovered that a certain relationship should be satisfied between the melting temperature and density of at least one of the metal powders in the inorganic portion of the material. In different embodiments, the density (g / cm) of those metal powders should be 3 The melting temperatures (on the Kelvin scale) of metal powders multiplied by their densities (at 20°C and 1 atmosphere) are less than 2790, less than 2490, less than 1900, less than 1400, less than 900, and even less than 400 [K*(g / cm 3 ) in the text. The test conditions are disclosed at the end of this document. Other different alloys can also be used for the inorganic portion of the material. The inventors have found that in some embodiments it is beneficial for the inorganic portion of the material to comprise any of the alloys disclosed in PCT / EP2016 / 076895, which is incorporated herein by reference. In one embodiment, the inorganic portion of the material comprises one of the aluminum-based alloys disclosed in PCT / EP2016 / 076895. In one embodiment, the inorganic portion of the material comprises one of the aluminum-based alloys disclosed in PCT / EP2016 / 076895, although the %Li content relative to the magnesium-based alloy is described in this application. In one embodiment, the inorganic portion of the material comprises one of the aluminum-based alloys disclosed in PCT / EP2016 / 076895 and at least one of the low-melting-point magnesium-lithium alloys disclosed herein. In one embodiment, the inorganic portion of the material comprises one of the aluminum-based alloys disclosed in PCT / EP2016 / 076895, but with a %Li content for the magnesium-based alloy as disclosed in this application, and at least one low-melting magnesium-lithium alloy as disclosed herein. In one embodiment, the inorganic portion of the material comprises one of the titanium-based alloys disclosed in PCT / EP2016 / 076895. In one embodiment, the inorganic portion of the material comprises one of the titanium-based alloys in PCT / EP2016 / 076895, but with a %Li content for the magnesium-based alloy as disclosed in this application. In one embodiment, the inorganic portion of the material comprises one of the titanium-based alloys disclosed in PCT / EP2016 / 076895 and at least one low-melting magnesium-lithium alloy as disclosed herein. In one embodiment, the inorganic portion of the material comprises one of the titanium-based alloys disclosed in PCT / EP2016 / 076895 but with a %Li content as disclosed herein for magnesium-based alloys, and at least one low melting point magnesium-lithium alloy as described herein.In one embodiment, the inorganic portion of the material comprises as the low melting point alloy one of the titanium-based alloys disclosed in PCT / EP2016 / 076895 having a high %Li content and the melting temperature of the low melting point magnesium-lithium alloys disclosed herein. Quite surprisingly, in some embodiments, it has been discovered that when using a titanium-lithium alloy as the low melting point alloy, even a low %Li content can be used, as long as a somewhat higher pressure (at the levels described herein) is subsequently used in the cold isostatic pressing (CIP), warm isostatic pressing (WIP) or equivalent process applied during forming. In one embodiment, the inorganic portion of the material comprises at least two different metal alloys having a sufficiently large difference between their melting temperatures. A sufficiently large difference between their melting temperatures may be, in different embodiments, 20°C or more, 55°C or more, 82°C or more, 105°C or more, 155°C or more, 205°C or more, 255°C or more, 310°C or more, 410°C or more, 610°C or more, 820°C or more, or even 1050°C or more. In one embodiment, any magnesium-based alloy and / or any low-melting-point magnesium-lithium alloy previously disclosed herein has the highest melting point among the different metal alloys in the inorganic portion. In one embodiment, the two different metal alloys having a sufficiently large difference between their melting temperatures are the alloys disclosed herein. In one embodiment, a metal alloy, such as any of the alloys disclosed in PCT / EP2016 / 076895, has the highest melting point among the different metal alloys in the inorganic portion. In one embodiment, the metal alloy, such as any of the alloys disclosed in PCT / EP2016 / 076895, has the lowest melting point among the different metal alloys of the inorganic portion. In one embodiment, the two different metal alloys having a sufficiently large difference between their melting temperatures are alloys disclosed in PCT / EP2016 / 076895. In one embodiment, both alloys are in particulate form. In one embodiment, the two different metal alloys having a sufficiently large difference between their melting temperatures are in powder form. In one embodiment, the alloy with the higher melting point has a higher D50 than the alloy with the lower melting point. In various embodiments, the difference in D50 between the two different metal alloys having a sufficiently large difference between their melting temperatures is 5 times or more, 6 times or more, 7 times or more, 8 times or more, and even 11 times or more. Test conditions are disclosed at the end of this document. The inventors have discovered that in some applications, particularly when the powder is a magnesium-lithium alloy and / or an aluminum-lithium alloy, at least one powder in the inorganic portion of the material comprises a beta phase, thereby facilitating molding of the material while significantly reducing molding input time. In one embodiment, the inorganic portion of the material comprises at least one metal powder comprising magnesium and / or lithium having at least a portion of beta phase, and in different embodiments, the inorganic portion of the material comprises a metal powder comprising lithium having at least 22%, at least 42%, at least 52%, at least 62%, and even all of the beta phase by volume. In one embodiment, the volume refers to the volume of the metal powder or the like. In different embodiments, the inorganic portion of the material comprises a metal powder comprising magnesium having at least 22% beta phase by volume, at least 52%, at least 52%, at least 62%, and even all of the beta phase by volume. In one embodiment, the volume refers to the volume of the metal powder or the like. Considering all metal particles in the inorganic portion of the material, in different embodiments, all metal particles comprise at least 42% beta phase by volume, at least 52%, at least 62%, at least 72%, and even all of the particles comprise beta phase. In various embodiments, the metal particles comprise at least 0.6%, at least 2.2%, at least 6%, at least 11%, and even at least 21% beta phase by volume. In this aspect for some embodiments, it is very important that the material is not sosoloid, as this will cause mixing during processing before forming is confirmed, significantly reducing formability. In various embodiments, the above disclosure occurs even when greater than 35%, greater than 52%, and even greater than 62% of the metal particles by volume have a low lithium content, and when the lithium-containing alloy is a magnesium-based alloy, a low lithium content in various embodiments refers to less than 19%, less than 14%, less than 9%, less than 6%, and even less than 3% by weight of such particles.In the case of aluminum-based alloys comprising lithium, what has been disclosed above in one embodiment occurs even when more than 35%, more than 52%, and even more than 62% of the metal particles by volume have a low lithium content, which in different embodiments refers to less than 49%, less than 39%, less than 19%, less than 14%, less than 8%, and even less than 3% by weight with respect to the weight of such particles. In some applications, the powder is more compactable when the inorganic portion of the material comprises an alloy of various embodiments having %Li greater than 16%, 18%, 32%, 38%, 46%, 54%, or 67% by weight, based on the weight of the alloy. The alloy may further comprise at least 0.12% by weight of an element selected from %As, %Sc, %Y, %La, %Th, %Ce, and %Ca. In various embodiments, the alloy may further comprise %Gd+%Nd+%Sm+%Y+%Pr+%Sc+%Pm+%Eu+%Tb+%Dy+%Ho+%Er+%Tm+%Yb+%Lu+%Th greater than 0.28%, 0.56%, or 0.78% by weight, based on the weight of the alloy. In one embodiment the alloy may further comprise at least two elements selected from %Ca, %Y, %Al, %Be, %Sc, %Zr, %Hf, %Ti, %La, %Ce, %As and / or %Y with a total content of at least 0.52%, at least 1.1%, at least 1.64%, and even at least 2.18% by weight with respect to the weight of the alloy in different embodiments. In different embodiments the alloy may further comprise %Mg of at least 12%, at least 16%, at least 22%, at least 26%, and even at least 62% by weight with respect to the weight of the alloy. In some embodiments this alloy is an element involved within the inorganic part of the material. In some applications, the powder is more compactable when the inorganic portion of the material in different embodiments comprises a powder mix having %Mg greater than 12% by weight and less than 18% by weight of lithium. Furthermore, the powder mix may further comprise one element selected from %As, %Sc, %Y, %La, %Th, %Ce, and / or %Ca, which in different embodiments are at least 0.12%, 0.28%, 1.12%, and even 2.2% by weight of the powder mix. In one embodiment, at least two of these elements are comprised in the powder mix. In one embodiment, the powder mix further comprises %Gd+%Nd+%Sm+%Y+%Pr+%Sc+%Pm+%Eu+%Tb+%Dy+%Ho+%Er+%Tm+%Yb+%Lu+%Th greater than 0.16%, greater than 0.38%, greater than 0.61%, and even greater than 1.1% by weight of the powder mix in different embodiments. In some embodiments, this powder mixture is the relevant element within the inorganic portion of the material. In some applications, the powder is more compactible if the inorganic portion of the material comprises a metallic phase having, in different embodiments, %Li by weight relative to the weight of such alloy, greater than 32%, greater than 39%, greater than 49%, greater than 56%, and even greater than 71%. In other applications, the metallic phase further comprises %Mg by weight of at least 12%, at least 16%, and even at least 24% in different embodiments, and in one embodiment the metallic phase further comprises at least two elements selected from %Ca, %Al, %Be, %Sc, %Zr, %Hf, %Ti, %La, %Ce, %As and / or %Y by total weight. In some embodiments, this metallic phase is the relevant phase within the inorganic portion of the material. In some applications, the powder is more compactible if the inorganic portion of the material comprises a metallic phase having, in different embodiments, %Mg by weight relative to the weight of such metallic phase of at least 12%, at least 16%, at least 22%, at least 26%, at least 27%, at least 32%, and even at least 62%, which in some embodiments is the relevant phase within the inorganic portion of the material. In some applications, the powder is more compactible if the inorganic portion of the material comprises a metallic phase having, in different embodiments, %Al by weight relative to the weight of such metallic phase of at least 1.6%, at least 2.8%, at least 3.6%, at least 4.2%, at least 6.3%, at least 18.6%, and even at least 32.1%, in some embodiments, this metallic phase is the relevant phase within the inorganic portion of the material. In some applications, the powder is more compactable if the inorganic portion of the material comprises a metallic phase having, in different embodiments, %Li of at least 32% by weight, %Li less than 18% by weight and %Mg greater than 12% by weight with respect to the weight of all metallic phases when all metallic phases present in the inorganic portion of the material are summed together, in some embodiments this metallic phase is the relevant phase within the inorganic portion of the material. In some applications, the powder is more compactible if the inorganic portion of the material comprises a metallic phase having, in different embodiments, %Ga by weight of at least 6%, at least 8%, at least 12%, and even at least 16% with respect to the weight of such metallic phase, which in some embodiments is the relevant phase within the inorganic portion of the material. In some applications, the powder is more compactible if the inorganic portion of the material comprises a metallic phase having, in different embodiments, %Ga+%Bi by weight of at least 12%, at least 16%, at least 19%, and even at least 23% with respect to the weight of such metallic phase. In some applications, the powder is more compactible if the inorganic portion of the material comprises a metallic phase in which the sum of %Ga+%Bi+%Rb+%Cd+%Cs+%Sn+%Pb+%Zn+%In by weight of such metallic phase is at least 12%, at least 16%, at least 19%, and even at least 23% by weight in different embodiments, and in some embodiments this metallic phase is the relevant phase within the inorganic portion of the material. In some applications, powder performance is improved when the inorganic portion of the material comprises a blend of metallic phases with %Li less than 18%, less than 16%, or less than 12% by weight, in different embodiments, relative to the total weight of such metallic phases. In different embodiments, the blend of metallic phases further comprises %Mg greater than 12%, greater than 16%, greater than 24%, and even greater than 31% by weight, relative to the total weight of such metallic phases. In different embodiments, the blend of metallic phases further comprises %Ca of at least 1.2%, at least 1.6%, at least 2.1%, and even at least 3.6% by weight, relative to the total weight of such metallic phases. In some embodiments, this metallic phase is the relevant phase within the inorganic portion of the material. The inventors have discovered that for some applications, it is preferable for the inorganic portion of the material to comprise at least one magnesium-lithium alloy in particulate form having a low melting point. For some applications, it is disclosed herein that at least one low melting point magnesium-lithium alloy is in particulate form having a melting temperature of less than 390°C, less than 340°C, less than 290°C, less than 240°C, and even less than 190°C, in different embodiments. In different embodiments, the inorganic portion of the material comprises associated elements having a melting temperature of less than 645°C, less than 580°C, less than 495°C, less than 445°C, less than 395°C, less than 345°C, less than 285°C, less than 245°C, less than 195°C, less than 145°C, and even less than 95°C. Test conditions are disclosed at the end of this document. In some embodiments, it is beneficial to have a very high inorganic fraction in the material. For some embodiments, this is often the case when the organic phase is largely, largely, or completely removed within the formed material. When the organic phase is largely or completely retained, a somewhat lower inorganic fraction is desirable in some embodiments, and a somewhat higher inorganic fraction is beneficial in some embodiments. In various embodiments, the powder mix provided in the inorganic fraction fill of the material should have a relative density of 52% or greater, 62% or greater, 67% or greater, 72% or greater, 76% or greater, 82% or greater, 86% or greater, and even 92% or greater. Relative density is defined as the ratio of tapped density to bulk density, expressed as a percentage (relative density = [tapped density / theoretical density] * 100), where tapped density is measured according to ACSTM B527-15 and theoretical density is measured according to ACSTM B962-08. In one embodiment, the powder mix provided in the filler of the inorganic portion of the material should have an apparent specific gravity of 52% or more, 62% or more, 67% or more, 72% or more, 76% or more, 82% or more, 86% or more, and even 92% or more. Apparent specific gravity is defined as the ratio of apparent density to bulk density expressed as a percentage (apparent specific gravity = [apparent density / theoretical density] * 100), where apparent density (at 20°C and 1 atmosphere) is measured according to ASTM B329-06 and theoretical density (at 20°C and 1 atmosphere) is measured according to ASTM B962-08. In some embodiments, it is the percentage by volume that matters (the percentage by volume of the inorganic portion relative to the volume of the material). In different embodiments, the inorganic portion loading of the material should be 52% or more, 62% or more, 67% or more, 72% or more, 76% or more, 82% or more, 86% or more, 92% or more by volume. In one embodiment, the percentages disclosed above are by weight and refer to the percentage by weight of the inorganic portion relative to the weight of the material. In one embodiment, the inorganic portion of the material comprises a powdered metal, which in one embodiment comprises a powder blend (in this document, a powder blend refers to a powder made by mixing two or more powders of different chemical composition, particle size distribution, particle shaping, or a combination of these properties, per ASATM B243-16a). In this document, when referring to powders, D3 refers to the particle size at which 3% of the volume of the sample is made up of smaller particles in the cumulative particle size distribution, D5 refers to the particle size at which 5% of the volume of the sample is made up of smaller particles in the cumulative particle size distribution, D10 refers to the particle size at which 10% of the volume of the sample is made up of smaller particles in the cumulative particle size distribution, D50 refers to the particle size at which 50% of the volume of the sample is made up of smaller particles in the cumulative particle size distribution, and D85 refers to the particle size at which 50% of the volume of the sample is made up of smaller particles in the cumulative particle size distribution. D90 refers to the particle size of 85% of the volume of a sample consisting of smaller particles in the cumulative particle size distribution, D95 refers to the particle size of 90% of the volume of a sample consisting of smaller particles in the cumulative particle size distribution, D97 refers to the particle size of 97% of the volume of a sample consisting of smaller particles in the cumulative particle size distribution, and D98 refers to the particle size of 98% of the volume of a sample consisting of smaller particles in the cumulative particle size distribution. The values D3, D5, D10, D50, D95, D97, and D98 are obtained by laser diffraction in accordance with ISO 13320-2009. In alternative embodiments, the percentages disclosed above are by weight and are designated D3m, D5m, D10m, D50m, D85m, D95m, D97m, and D98m. In this document, particle size of metal powders refers to D50 unless otherwise stated. For some applications, fine powders are preferred. In different embodiments, the powder should have a D50 of 78 micrometers or less, 48 micrometers or less, 28 micrometers or less, 18 micrometers or less, or 8 micrometers or less. For some applications, slightly coarser powders are acceptable or advantageous.In various embodiments, the powder should have a D50 of 1900 micrometers or less, 800 micrometers or less, 780 micrometers or less, 380 micrometers or less, 210 micrometers or less, 200 micrometers or less, 190 micrometers or less, 180 micrometers or less, 120 micrometers or less, 90 micrometers or less, and even 45 micrometers or less. In some applications, fine powders are even disadvantageous. In various embodiments, the powder should have a D50 of 2 micrometers or more, 6 micrometers or more, 8 micrometers or more, 12 micrometers or more, 22 micrometers or more, 42 micrometers or more, 72 micrometers or more, 122 micrometers or more, 222 micrometers or more, or 312 micrometers or more. In various embodiments, what is stated in this paragraph applies, but D50 is replaced by D90, D95, D97, D98, D10, D5, and even D3. When one or more powders are mixed to form a powder blend, in some embodiments, reference is made to the particle size of the powder blend (in this document, when one or more powders are mixed, particle size refers to the particle size of a homogeneous mixture of such powders considered as a single powder). In one embodiment, any of the above references to D3, D5, D10, D50, D90, D95, D97, or D98 can also apply to the size of the powder blend. Even more surprisingly, in some cases, it is beneficial to have a mixture of small and large particles, and it is sufficient to ensure that the overall D98 of all particles used together is sufficiently large. In different embodiments, it is 210 micrometers or more, 310 micrometers or more, 410 micrometers or more, 510 micrometers or more, 610 micrometers or more, 810 micrometers or more, or 1010 micrometers or more. In different embodiments, what is said about D98 should also apply to D95, D85, and even D50. When one or more powders are mixed to form a powder blend, in some embodiments the particle size values D5, D10, D50, D90, D95, D97 or D98 disclosed above refer to the size of the powder blend.In an alternative embodiment, the values of D5, D10, D50, D90, D95, D97 and D98 disclosed above can be replaced by D5m, D10m, D50m, D95m, D97m and D98m, respectively. In this document, when a high packing ratio is desired, a special blend of inorganic fractions or powders is used. This works surprisingly well for surprisingly high packing values, even when organic fractions are present. In one embodiment, powder blends with two or more modes are preferred, in one embodiment, powder blends with three or more modes are preferred, and in one embodiment, powder blends with four or more modes are preferred. The mode refers to the size value occurring most frequently. In powder blends, the mode is defined as the size value occurring most frequently among uniform test samples produced by blending powders with each unique mode. In the case of a bimodal blend, the coarsest fraction has a volume fraction (considering only the inorganic fraction) between 60% and 85%, between 65% and 78%, between 70% and 75%, and even between 71.5% and 73% by volume in different embodiments. In one embodiment, the coarsest fraction refers to the powder fraction with the largest D90, and in one embodiment, the powder fraction with the highest D90 / D50 ratio. In the case of a three-mode mixture, the coarsest fraction has a volume fraction (considering only the inorganic portion) between 50% and 80%, between 55% and 72%, between 60% and 68%, and even between 63.5% and 66% by volume in different embodiments. In one embodiment, the coarsest fraction refers to the powder fraction with the greatest D90, and in an alternative embodiment, the powder fraction with the highest D90 / D50 ratio, and the finest fraction has a volume fraction (considering only the inorganic portion) between 2% and 25%, between 5% and 20%, between 7% and 15%, and even between 10% and 12% by volume in different embodiments. In one embodiment, the finest fraction refers to the powder fraction with the smallest D50, and in an alternative embodiment, the powder fraction with the lowest D50 / D10 ratio. In the case of the four-mode mixture, the coarsest fraction has a volume fraction (considering only the inorganic part) between 45% and 75% by volume, between 50% and 70%, between 60% and 68%, and even between 58.5% and 63% in different embodiments.In one embodiment, the coarsest fraction refers to the powder fraction with the largest D90, and in an alternative embodiment, the powder fraction with the highest D90 / D50 ratio, with the second finest fraction having a volume fraction (considering only the inorganic portion) between 2% and 25%, between 5% and 20%, between 6% and 14%, and even between 9% and 11% by volume in different embodiments. In one embodiment, the second finest fraction refers to the powder fraction with the second smallest D50, and in an alternative embodiment, the powder fraction with the second lowest D50 / D10 ratio, with the finest fraction having a volume fraction (considering only the inorganic portion) between 12% and 0.5%, between 9% and 3%, between 7% and 5%, and between 6.5% and 5.5% by volume in different embodiments. In one embodiment, the finest fraction refers to the powder fraction with the smallest D50, and in an alternative embodiment, the powder fraction with the lowest D50 / D10 ratio. In one embodiment, the inventors discovered that a certain relationship should be considered between the D10 fraction and the D90 fraction of the nearest smaller fraction. In one embodiment, the inventors discovered that a certain relationship should be considered between the D5 fraction and the D95 fraction of the nearest smaller fraction. In one embodiment, the inventors discovered that a certain relationship should be considered between the D3 fraction and the D97 fraction of the nearest smaller fraction. In different embodiments, the relationship should be 7.1 times or more, 8.1 times or more, 9.1 times or more, or 10.6 times or more. Regarding the narrowness of the distribution of each fraction, the inventors discovered that using the parameter ND = (D90 - D10) / D50 is a good control method. In different embodiments, ND should be less than 0.8, less than 0.58, less than 0.4, less than 0.18, less than 0.08, and even less than 0.038. In one embodiment, within the definition of ND, D90 is replaced by D97 and D10 is replaced by D3.A very surprising observation is that the achievable relative density is higher when the smallest size fraction is not centered on the target D50 but just smaller than the desired D50 because it is not a narrow normal distribution but a cut tail of the normal distribution (for example, a mixture of fraction 1: 600 + / - 25 micrometers and fraction 2: < 45 micrometers can achieve a higher relative density than a mixture of fraction 1: 600 + / - 25 micrometers and fraction 2: 45 + / - 5 micrometers). Therefore, in such cases, ND control is performed for all fractions except the finest, and the D97 criterion applies, but not the ND criterion, but rather NDS = (D97 - D50) / (D50 - D3). In different embodiments, NDS should be less than 0.9, less than 0.8, less than 0.68, and even less than 0.49. What has been described here extends to all mixtures of fine powders or materials in this document where a high relative density is advantageous. Surprisingly, for some materials, when the finest fraction contains very fine particles, the density of the packing decreases sharply. Therefore, for some applications, the finest fraction should limit the finest particle size. In various embodiments, the D5 of the finest fraction should be greater than 0.6 micrometers, greater than 1.2 micrometers, greater than 3.2 micrometers, greater than 5.3 micrometers, greater than 8.1 micrometers, greater than 11 micrometers, greater than 16 micrometers, and even greater than 21 micrometers. In various embodiments, D5 in the above sentence should be replaced by D10, and in other embodiments, by D3. In one embodiment, the finest fraction refers to the powder fraction with the smallest D50, and in an alternative embodiment, the powder fraction with the lowest D50 / D10 ratio. When one or more powders are blended to form a powder blend, in some embodiments, the particle size values ND, NDS, D3, D5, D10, D50, D95, and D97 disclosed above refer to the size of the powder blend.In alternative embodiments, the values of D3, D5, D10, D50, D95, and D97 disclosed above can be replaced by D3m, D5m, D10m, D50m, D95m, and D97m, respectively. In some applications, the powder should be highly spherical and the particle size distribution should be very narrow. The sphericity of a powder is a dimensionless parameter defined as the ratio between the surface area of a sphere having the same volume as the particle and the surface area of the particle. Sphericity is determined by dynamic image analysis. In various embodiments, it is desirable for the powder to have a sphericity greater than 0.53, greater than 0.76, greater than 0.86, and even greater than 0.92. When high compaction of metal particulates is desired, metal powders with high sphericity, greater than 0.92, greater than 0.94, greater than 0.98, and even 1, are often desirable. When referring to sphericity, for some applications, the average sphericity of the most spherical particles can be evaluated for the majority of the powder; in various embodiments, 60% or more, 78% or more, 83% or more, and even 96% or more of the volume of the powder used should be considered as the average calculation. In one embodiment, the metal powder is spherical. In one embodiment, spherical powders having any of the particle size values in this paragraph (D3, D5, D10, D50, D85, D90, D95, D97, D98, ND, or NDS) are disclosed above. In some embodiments, the values disclosed above refer to the sphericity and particle size of the powder blend. For some applications, excessive sphericity can be disadvantageous, for example, by hindering sinterability or for other reasons. In various embodiments, preferred sphericities of less than 0.94%, less than 0.88%, less than 0.68%, and even less than 0.48% can be advantageous. In one embodiment, the particles are irregular. In one embodiment, the metal powder is random (random means any particle with corners, sharp edges, and angular protrusions). In one embodiment, the powder is random with any of the particle size values disclosed above in this paragraph (D3, D5, D10, D50, D85, D90, D95, D97, D98, ND, or NDS). In some embodiments, the values disclosed above refer to the size of the randomly shaped powder mix. In some embodiments, it has been discovered that as important as particle size is the cooling rate of the powder that should be controlled. In different embodiments, the cooling rate of the powder during production should be set to 11 K / s or higher, 110 K / s or higher, 1100 K / s or higher, 11,000 K / s or higher, 110,000 K / s or higher, or 1,100,000 K / s or higher. In this document, there are some embodiments comprising an organic portion and a particulate inorganic portion, and in some embodiments, special care must be taken with regard to the fraction of one of the components. In most embodiments, volume fractions are used, while in some embodiments, weight fractions are used. For those embodiments where reference is made to weight fractions, parallel embodiments automatically exist in which the same restrictions apply but the expressed fractions should be interpreted as volume fractions. This is particularly true for different embodiments in which the density of the particulate material or powder to which the restrictions apply is 1.4 times or more, 2.2 times or more, 3.2 times or more, 5.2 times or more, and even 6.4 times or more higher than the density of the organic portion when considered as a whole. There are several applications that benefit from lightweight construction. Structural elements or parts that are subject to some type of movement, such as moving parts of transportation vehicles or machinery, are well known. Additionally, stationary structural elements can also benefit from lightweight construction. Among the many elements that benefit from lightweight construction, the list of performance specifications is highly diverse. Most elements share the requirement of not failing under applied loads, but given the highly variable nature of those loads, the concept of not failing can be very different for different elements, such as not being bulky, strain limited, not cracking, etc., all of which are combined with the lowest possible associated weight. Beyond this roughly shared requirement, every application has many additional requirements or lists of specifications. Some require specific electrical or magnetic behavior, others have several temperature requirements regarding heat transport, temperature requirements (high or low), temperature distribution requirements, etc., many have appearance requirements such as roughness and color, and the list continues to grow. The inventors have discovered that observing certain rules and constraints, such as those described herein, allows for the advantages described herein for lightweight construction molded elements. The rules and constraints set out in this document take away some freedom from the designer using the invention to manufacture specific elements for specific applications, but some freedom remains for the designer / user of the invention to provide the best compromise of the remaining requirements for a given application. Some freedom is provided to accommodate other related requirements through some flexibility in the specific choices of organic parts of materials, inorganic parts of materials, manufacturing methods, etc., but always within the guidelines of this document to obtain the associated benefits. Some embodiments are as follows: In one embodiment, the inorganic portion of the material comprises an alloy disclosed herein, such as any magnesium-based alloy previously disclosed herein and / or any low melting point magnesium-lithium alloy previously disclosed herein having powdered %Li greater than 32% by weight and a D50 of 800 micrometers or less. In one embodiment, the inorganic portion of the material comprises an alloy disclosed herein, such as any magnesium-based alloy previously disclosed herein and / or any low melting point magnesium-lithium alloy previously disclosed herein having %Li greater than 32% by weight and %Mg is not absent and having a D50 of 120 micrometers or less with respect to the weight of the low melting point magnesium-lithium alloy. In one embodiment, the inorganic portion of the material comprises a powder blend having a D50 of 800 micrometers or less, comprising an alloy having %Li by weight of at least 32% with respect to the weight of the alloy, the powder blend having %Li less than 18% by weight and %Mg greater than 12% by weight with respect to the weight of the powder blend. In one embodiment, the inorganic portion of the material comprises a powder mix having a D50 of 800 microns or less comprising an alloy having %Li by weight of at least 32% by weight relative to the weight of the alloy, the powder mix having %Li less than 18% by weight and %Mg greater than 12% by weight relative to the weight of the powder mix, and wherein one powder type is present within the powder mix having a D50 at least three times greater than the D50 of another powder type within the powder mix. Due to the densification mechanism often used during molding, the inventors have discovered that for some applications it is beneficial to use materials with hard particles or reinforcing fibers to impart specific tribological behavior and / or increase mechanical properties. In this sense, some applications benefit from the use of materials with hard particles or reinforcing fibers, the volume of hard particles relative to the volume of the material being, in different embodiments, 2% or more by volume, 5.5% or more, 11% or more, and even 22% or more. These hard particles are not necessarily incorporated separately, but may be incorporated in a separate step or synthesized during the process. Typically, hard particles are of high hardness. In various embodiments, the hard particles used are diamond, cubic boron nitride (cBN), oxides (aluminum, zirconium, iron, etc.), nitrides (titanium, vanadium, chromium, molybdenum, etc.), carbides (titanium, vanadium, tungsten, iron, etc.), borides (titanium, vanadium, etc.), or mixtures thereof, with any particle typically having a hardness of 11 GPa or greater, 21 GPa or greater, 26 GPa or greater, and even 36 GPa or greater in various embodiments. The inventors have discovered that the use of whiskers and other ceramic fibers in the material can also be beneficial for some applications of the molded materials disclosed herein. For some applications, recycled chopped carbon fiber reinforced plastic (usually in a polyurethane matrix) can also be advantageously used in place of fibers in one embodiment. In some embodiments comprising powders, the inventors have discovered that some of the powders behave very differently depending on whether they are exposed to oxygen. In some embodiments, it is a different gas that makes the difference. In one embodiment, the powder is exposed to an oxidizing atmosphere. In one embodiment, the organic moiety also has functionality that prevents the powder surface from direct contact with air. In one embodiment, the organic moiety also has functionality that prevents the powder surface from direct contact with oxygen. In one embodiment, upon heating, the organic moiety liberates a gas that at least partially reacts with at least one of the incorporated powder surfaces. In one embodiment, during debinding, the organic moiety at least partially reacts with at least one of the incorporated powder surfaces. In one embodiment, upon decomposition, the organic moiety liberates a gas that at least partially reduces at least one of the incorporated powder surfaces. In one embodiment, at least one of the powder species is surface modified prior to mixing with the organic moiety. In one embodiment, at least one of the powder species is reduced prior to mixing with the organic moiety. In one embodiment, the protective or protected atmosphere has a noble gas or mixture thereof as a primary component. In one embodiment, the protective or protected atmosphere has a noble gas or mixture thereof as a primary component. In one embodiment, the protective or protected atmosphere has a noble gas or mixture thereof as a primary component. In one embodiment, the protective or protective atmosphere has a gaseous hydrocarbon as its primary component. In one embodiment, the protective or protective atmosphere has a carbon dioxide as its primary component. In one embodiment, the protective or protective atmosphere has a carbon-bridged gas as its primary component. In one embodiment, the protective or protective atmosphere has a hydrogen as its primary component. In one embodiment, the protective or protective atmosphere has a halogen-containing gas as its primary component. In a different embodiment, the halogen comprises fluorine, chlorine, or bromine, and in one embodiment, the halogen-containing gas is FS6. In one embodiment, the protective or protective atmosphere has a sulfur-containing gas as its primary component, and in one embodiment, a phosphorus-containing gas. In a different embodiment, the protective or protective atmosphere comprises nitrogen, a gaseous hydrocarbon, carbon dioxide, a carbon-bridged gas, hydrogen, and a halogen-containing gas.In different embodiments, the halogen comprises fluorine, chlorine, or bromine. In one embodiment, the halogen-containing gas is FS6. In another embodiment, the protective or protected atmosphere comprises a sulfur- and phosphorus-containing gas. In another embodiment, the reducing atmosphere comprises a gas containing nitrogen, a gaseous hydrocarbon, carbon dioxide, a carbon-bridged gas, hydrogen, and a halogen-containing gas as its main components. In another embodiment, the halogen comprises fluorine, chlorine, or bromine. In one embodiment, the halogen-containing gas is FS6. In another embodiment, the reducing atmosphere comprises a gas containing sulfur, a gas containing phosphorus, nitrogen, a gaseous hydrocarbon, carbon dioxide, a carbon-bridged gas, or hydrogen, and in one embodiment, a halogen-containing gas. In another embodiment, the halogen comprises fluorine, chlorine, or bromine, and in one embodiment, the halogen-containing gas is FS6. In one embodiment, the reducing atmosphere comprises a gas containing sulfur, and in one embodiment, a gas containing phosphorus. A major component refers to a component that in some embodiments is at least 6% or more, 11% or more, 16% or more, 22% or more, 26% or more, and even 36% or more by volume relative to the total volume of gas. In alternative embodiments, the percentages disclosed above are by weight. More embodiments of inorganic phases / components that can be included in the material are disclosed later in this document. Some of the materials described in this application are to the best knowledge of the inventors not known in the state of the art and are therefore themselves new. They are the result of the combination of different embodiments. Some examples are: The material has an organic portion and an inorganic portion, the organic portion having an associated element with a deflection temperature measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi] at at least 185°C, and the inorganic portion comprises a metallic phase having a %Li by weight of at least 16% with respect to the weight of the metallic phase and similarly having a %Mg by weight of at least 12% with respect to the weight of the metallic phase. The material having an inorganic portion comprises metallic phases having %Li of at least 32% by weight, and when all present metallic phases (including intermetallic phases) are added together, %Li is less than 18% by weight with respect to the total weight of the metallic phases, %Mg is greater than 12% by weight with respect to the total weight of the metallic phases, and %Ca is greater than 1.2% by weight with respect to the total weight of the metallic phases. The material has an organic portion and an inorganic portion, the organic portion having an associated component with a deflection temperature measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi] at at least 185°C, and the inorganic portion comprises a powder blend with a D50 of 800 micrometers or less. The material has an organic portion and an inorganic portion, the organic portion having an associated component with a deflection temperature measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi] at at least 230°C, the inorganic portion comprising a powder blend having a D50 of 120 micrometers or less and at least one intermetallic phase, and the material further comprising fiber reinforcement. Organic materials with relevant elements have a deflection temperature measured in accordance with ACSTM D648-07 at a load of 0.46 MPa [0.66 psi] at at least 185°C, which is at least 0.26 J / cm² at a single dose at frequencies above 0.12 THz. 2 It can polymerize by a conversion factor of 12% or more when exposed to radiation. The material has an organic portion and an inorganic portion, the organic portion having an associated element with a deflection temperature measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi] at at least 185°C, the inorganic portion comprising a powder blend having a D50 of 1900 micrometers or less, and the material further comprising carbon nanotubes stretched by mechanical action. The material has an organic portion and an inorganic portion, the organic portion having an associated component with a deflection temperature measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi] at at least 185°C, the inorganic portion comprising a powder blend having a D50 of 1900 micrometers or less, and the material further comprising fiber reinforcement. The material has an organic portion and an inorganic portion, the inorganic portion being 52% or more by volume, the inorganic portion comprising a powder blend having a D50 of 1900 micrometers or less, the inorganic portion comprising gallium, and the material further comprising fiber reinforcement. The material has an organic portion and an inorganic portion, the organic portion having an associated element with a deflection temperature measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi] at at least 185°C, the inorganic portion comprising a powder mix with a D50 of 1900 micrometers or less, the material further comprising fiber reinforcement, and the inorganic portion comprising a %Ga of 0.6% or more by weight relative to the weight of the inorganic portion. The material has an organic portion and an inorganic portion, the organic portion having an associated element with a deflection temperature measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi] at at least 230°C, the inorganic portion comprising a powder blend having a D50 of 1900 micrometers or less, and the material further comprising fiber reinforcement comprising carbon nanotubes stretched during the manufacturing process of the shaped material. The material comprises an organic portion and an inorganic portion, the organic portion having an associated element with a deflection temperature measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi] at at least 185°C, and the inorganic portion having a metallic phase with a melting temperature of 580°C or less. In alternative embodiments, in the materials disclosed above, the heat deflection temperature of the relevant component of the organic portion of the material can be replaced by either the glass transition temperature, or degradation temperature, or melting temperature of such relevant component of the organic phase. The test conditions for heat deflection temperature are disclosed at the end of this document. Other embodiments are as follows. The material comprises an organic portion and an inorganic portion, the organic portion comprising a component having a deflection temperature, measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi], that is 0.45 times higher than the melting temperature (0.45*Tm) of at least one component in the inorganic portion of the material. Materials are disclosed above in which the relevant component is at least 0.6% by weight of the weight of the material. Materials are disclosed above in which the relevant component is at least 11% by weight of such portion of the material. Materials are disclosed above in which the inorganic portion of the material is at least 52% by weight of the weight of the material. The materials disclosed above have a deflection temperature that is at least 185°C, and the inorganic portion comprises a metallic phase having a melting temperature less than 590°C. In the materials disclosed above, the inorganic portion of the material comprises a metallic phase with %Li of at least 16% by weight relative to the weight of the metallic phase. The inorganic portion of the material comprises more than one metal phase, the inorganic portion comprising a metal phase having at least 32% %Li by weight, where, when all metal phases in the inorganic portion of the material are added together, %Li is less than 18% by weight relative to the weight of the inorganic portion and %Mg is greater than 12% by weight relative to the weight of the inorganic portion. The inorganic portion of the material comprises a metal phase comprising at least 12% %Ga+%Bi by weight relative to the weight of the inorganic portion. The inorganic portion of the material comprises a powder blend having a D50 of 1900 micrometers or less. The inorganic portion of the material comprises a blend of at least two powders, one of which has a D50 at least three times greater than the D50 of another powder in the blend. The material further comprises fiber reinforcement comprising carbon nanotubes stretched during the manufacturing process of the material. In the material disclosed above, the inorganic portion of the material comprises an organic component whose glass transition temperature (Tg) increases by 55° C. or more when subjected to a transformation treatment. In the material disclosed above, the material comprises at least 11% particles by volume.In the above-disclosed materials, the organic material comprises inorganic particles susceptible to polymerization when exposed to radiation at frequencies between 0.32 THz and 19 THz. The above-disclosed materials have a conversion of greater than 12% at 2560 micrometers or greater below the surface of the material when exposed to radiation above 0.82 THz. In alternative embodiments, in the above-disclosed materials, the heat deflection temperature of the relevant component of the organic portion of the material can be replaced in different embodiments by either the glass transition temperature, or degradation temperature, or melting temperature of such relevant component of the organic phase. Any of the materials disclosed herein are particularly suitable in some embodiments for use in the methods disclosed herein to produce molded materials with excellent weight and performance characteristics in an economical manner, particularly for lightweight construction. The inventors have discovered that it is possible to mold the material using additive manufacturing or any other similar method and subject the molded material to pressure and temperature. In some embodiments, the molded material is further subjected to debinding and / or consolidation before obtaining the desired molded material. In yet other embodiments, the molded material is subjected to additional steps, such as thermomechanical processing or machining, before obtaining the desired molded material. The method comprises several steps: Step 1. Gather the materials Step 2. Use molding techniques to shape the material. Step 3. The shaped material obtained in step 2 is subjected to a process involving a pressure greater than 55 MPa and a temperature greater than 0.45*Tm of the phase or element having the lowest melting temperature among the relevant elements / phases of the non-organic part of the material. and optionally Step 4. The shaped material obtained in step 3 is subjected to a debinding process. Step 5. The formed material obtained in step 3 or 4 is subjected to a consolidation process. The method should be considered a separate embodiment for all materials taken that are disclosed herein. In one set of embodiments, the material taken in step 1 comprises a material described in PCT / EP2016 / 076895. In one set of embodiments, the material taken in step 1 is a material described herein, with at least a portion of the inorganic portion replaced by an inorganic material as described in PCT / EP2016 / 076895. In one set of embodiments, the material in step 1 comprises at least one of the alloys disclosed in PCT / EP2016 / 076895, which is incorporated herein by reference in its entirety. In some embodiments, the material comprising an organic portion and an inorganic portion provided in step 1 is any material disclosed herein. In some embodiments, the material comprises at least one magnesium-based alloy disclosed herein. In some embodiments, the material comprises at least one low-melting-point magnesium-lithium alloy disclosed herein. Thus, unless mutually exclusive, any embodiment of the material disclosed herein can be used in this method and can be combined with any embodiment of this method in any combination. As previously disclosed, the inventors have discovered that the same methods described herein can be applied to the materials described in PCT / EP2016 / 076895, which constitute specific embodiments. In one embodiment, at least one of the metal alloys of PCT / EP2016 / 076895 is used as an inorganic component of the inorganic portion of the material. In one embodiment, one of the aluminum-based alloys of PCT / EP2016 / 07689. Considering the remaining percentage relative to the original amount, as explained above, in different embodiments, the remaining organic portion should be less than 49%, less than 34%, less than 24%, less than 14%, less than 9%, less than 4%, less than 2%, and even less than 0.4% by volume. In an alternative embodiment, the percentages disclosed above are by weight. In one embodiment, only trace levels of the organic portion are retained. In one embodiment, the organic portion is completely removed. In some embodiments, sufficient organic portion should be present to ensure functionality. In some embodiments, it is beneficial to reduce the organic portion as little as possible. In different embodiments, at least 35%, at least 45%, at least 56%, at least 66%, at least 76%, and even at least 82% by weight of the organic portion should be retained. In some embodiments, even minor degradation of the organic portion should be prevented. In different embodiments, at least 86%, at least 92%, at least 96%, at least 97%, and even at least 99% by weight of the organic portion should be retained. In some embodiments, the volume percentage is more relevant. In various embodiments, at least 35%, at least 45%, at least 56%, at least 66%, at least 76%, and even at least 82% of the organic portion by volume should be retained. In some embodiments, even minor degradation of the organic portion should be prevented. In various embodiments, at least 86%, at least 92%, at least 96%, at least 97%, and even at least 99% of the organic portion by volume should be retained. In some embodiments, the organic portion is largely or completely removed in the resulting molded material. In some embodiments, the organic portion is largely or completely retained. In one embodiment, the proportion of the portion remaining is calculated as the fraction of the portion remaining, i.e., the amount of the portion divided by the original amount of the portion, expressed as a percentage. In one embodiment, this is done by measuring kilograms of the portion per cubic meter of the element.As an illustrative example, if an element is made of material with 400 kg of organic fraction per cubic meter of material, after the process in question, only 10 kg of organic fraction is left for each cubic meter of element (often weight and volume are measured and converted into other units), thus leaving 2.5% of the organic fraction. The volume control does not have to be 1 m3. In different embodiments, the volume control is in liters, cubic centimeters, cubic inches, cubic millimeters. In one embodiment, the fraction left is calculated by the volume of such fraction out of the total volume of the material, and continues in the same way (divide the final amount by the original amount and express the result as a percentage). In one embodiment, for a method involving a step in which particle injection molding (PIM) is a molding technique (particle injection molding where particles P can be metal M, ceramic C, intermetallic or any other), and a step involving cold isostatic pressing (CIP), warm isostatic pressing (WIP), or similar methods, both steps can be combined into one by using at least one associated element with a metal alloy, such as any of the metal alloys disclosed herein, with a sufficiently low melting temperature (at the levels described herein), ultimately resulting in a slight increase in the processing time of the molding method, whereby cold isostatic pressing, warm isostatic pressing, or similar methods are omitted. In different embodiments, the forming technique is an additive manufacturing (AM) forming technique such as, but not limited to, 3D printing, inkjet printing, S-printing, M-printing techniques, techniques in which focused energy is used to create a molten pool in which the feedstock (powder or wire material) is accumulated using a laser (laser deposition and laser consolidation), arc or E-beam heat sources (direct metal deposition and electron beam direct melting), fused deposition modeling (FDM) material jetting, direct metal laser sintering (DMLS), selective laser melting (SLM), electron beam melting (EBM), selective laser sintering (SLS), stereolithography (SLA), and other or any other advanced additive manufacturing techniques such as digital light processing (DLP). In some embodiments, additive manufacturing comprises techniques capable of printing protruding features without the need for ancillary materials. In different embodiments, the molding technique is a polymer molding technique, metal injection molding (MIM), particle injection molding (PIM), injection molding, compression molding, thermoforming, or any other similar technique. In one embodiment, any method described in this document as applicable to PIM (particle injection molding) technology can be applied to any molded material produced by a similar process, and can be any manufacturing method involving a molding die or tool and applying pressure to the material produced in the die or tool (by injection, by compression, by extrusion, etc.). In one embodiment, any method described in this document as applicable to PIM (particle injection molding) technology can be applied to any molded material produced by a similar process, and can be any manufacturing method involving a molding die or tool and applying pressure to the material produced in the die or tool (by injection, by compression, by extrusion, etc.). In different embodiments, the molding technique used in step 2 is an additive manufacturing (AM) molding technique using wire, rod, filament, or any extrudable shape, which may conceptually be described as fused deposition modeling (FDM). In one embodiment, the material in steps 1 and 2 is in a liquid state (suspension, mixture, etc.). In one embodiment, the material in steps 1 and 2 is in a liquid state and is polymerizable or curable under exposure to one of the wavelengths described herein. In different embodiments, the molding technique used in step 2 is an additive manufacturing (AM) molding technique that uses an activator to promote binding, an additive manufacturing (AM) molding technique that uses a masking material to delay or prevent binding, an additive manufacturing (AM) molding technique that projects several fluids onto a base material through a small opening, an additive manufacturing (AM) molding technique that projects several fluids onto a base material such as a powder through a small opening, an additive manufacturing (AM) molding technique that projects several fluids onto an assembled molded material through a small opening, an additive manufacturing (AM) molding technique based on polymerization or hardening by exposure to radiation of a certain wavelength or combination of wavelengths, an additive manufacturing (AM) molding technique based on stereolithography (SLA), an additive manufacturing (AM) molding technique based on two-photon stereolithography principles, an additive manufacturing (AM) molding technique based on microstereolithography, any additive manufacturing (AM) molding technique, or an additive manufacturing (AM) molding technique that includes a technique capable of printing protruding features without the need for an auxiliary. In one embodiment, the material in steps 1 and 2 comprises an injectable polymer. In different embodiments, the method used in step 2 is a manufacturing method based on the injection of a polymer with the material, a manufacturing method based on a PIM (Particle Injection Molding) method, or a manufacturing method based on a MIM (Metal Injection Molding) method. In one embodiment, additive manufacturing (AM), particle injection molding (PIM), or any other method similar to metal injection molding (MIM) may be used to mold the material. Some embodiments of molding techniques, including additive manufacturing (AM), are disclosed in more detail later in this document.Thus, any embodiment of any additive manufacturing (AM) forming technique disclosed throughout this document may be used within this method and may be combined with any embodiment of this method without restriction, provided they are not incompatible. In one embodiment, the material in steps 1 and 2 is a wire, rod, filament, or any extrudable shape. In one embodiment, the material in steps 1 and 2 is a wire, rod, filament, or any extrudable shape that is mechanically stretched during manufacturing and / or before it is incorporated into the manufactured shaped material. The shaped material obtained in step 2 is subjected to a process involving pressure and temperature. In various embodiments, the shaped material is subjected to a process in step 3 involving temperatures above 0.35*Tm, above 0.45*Tm, above 0.52*Tm, above 0.61*Tm, above 0.69*Tm, above 0.74*Tm, and even above 0.86*Tm, where Tm refers to the melting temperature of the relevant phase or element in the inorganic portion of the material with the lowest melting temperature. The inventors have discovered that in various embodiments where the material comprises a metallic phase and / or elements with a freezing temperature range (liquid and solid coexist), the shaped material is subjected to temperatures above the Tm (melting temperature) of the relevant phase or element in the inorganic portion of the material with the lowest melting temperature, and even above 1.1*Tm. In some applications, when the material comprises a powder with a liquid phase, temperatures above 1.2*Tm and even above 1.5*Tm are used in some embodiments, even if the material does not have a freezing range. Test conditions are disclosed at the end of this document. A very useful process for step 3 is the application of warm isostatic pressing (WIP). Warm isostatic pressing (WIP) generally only makes sense if pressure is applied for a few minutes, as is the case with cold isostatic pressing (CIP). Applying pressure (or temperature, in the case of warm isostatic pressing (WIP)) for longer periods often results in degradation of properties, often rendering the formed material less competitive than others. In some embodiments, longer process times have been found to be surprisingly beneficial, and even essential in some embodiments. In different embodiments, warm isostatic pressing (WIP) process times are 36 minutes or more, 66 minutes or more, 106 minutes or more, 226 minutes or more, 246 minutes or more, and even 506 minutes or more. In one embodiment, pressure is not applied continuously, but rather, cycles of high pressure are applied. In one embodiment, pressure is not applied continuously, but rather, a series of pulsed pressures are applied. In one embodiment, pressure is not maintained continuously. In one embodiment, temperature is applied through temperature regulation of a fluid that acts as a pressure transmitter. In one embodiment, pressure is applied first and then temperature is applied once a certain level is reached. In one embodiment, pressure is applied first once a certain temperature is reached. In one set of embodiments, what is stated for warm isostatic pressing (WIP) can be extended to cold isostatic pressing (CIP) or any other process that applies pressure. In one embodiment, manufacturing step 3 comprises a process where temperature and pressure are simultaneous at some point. In one embodiment, the maximum temperature and maximum applied pressure recited in manufacturing step 3 do not coincide in time. In some embodiments, the shaped material obtained in step 3 is subjected to a process in which the organic moiety is at least partially removed. In some embodiments, the organic moiety is completely removed. In one embodiment, a debinding is used to at least partially remove the organic moiety. In one embodiment, the debinding is a thermal debinding. In some embodiments, the organic moiety is at least partially removed using a thermal process. In different embodiments, the debinding is a non-thermal process selected from non-thermal debinding, chemical debinding, catalysis, wicking, drying, supercritical extraction, organic solvent extraction, aqueous solvent extraction, or freeze-drying, among others. In different embodiments, at least a portion of the organic moiety is removed using a thermal process at temperatures above 0.3*Tm, above 0.45*Tm, above 0.55*Tm, and even above 0.7*Tm, where Tm refers to the melting temperature of the relevant component or phase with the lowest melting temperature within the inorganic portion of the material. Test conditions are disclosed at the end of this document. In one embodiment, the consolidation step comprises sintering. In one embodiment, the consolidation step comprises hot isostatic pressing (HIP). In one embodiment, the consolidation step comprises some type of plastic deformation. In one embodiment, steps 4 and 5 are performed simultaneously. In one embodiment, the method further comprises performing several additional shaping steps involving material removal in certain locations (e.g., trimming, drilling, machining, polishing, etc.). In one embodiment, the method further comprises performing several additional shaping steps involving material buildup (thermal or cold spraying, metal coating, architectural welding or direct energy deposition additive manufacturing (AM), etc.). In one embodiment, the method further comprises heat treating the shaped material. In one embodiment, the method further comprises locally heat treating the shaped material. In one embodiment, the method further comprises applying at least locally a surface heat treatment to the shaped material. In one embodiment, the method further comprises at least locally applying a coating to the shaped material. In one embodiment, the method further comprises at least locally applying a paint to the shaped material. In one embodiment, the method further comprises joining the shaped material to another element, structure, component, part, or any other. In one embodiment, the method further comprises any other method step described herein. In one embodiment, the method further comprises a cleaning or rinsing step. In one embodiment, the method further comprises a shot peening, blasting or similar step. When considering the percentage by weight of the organic portion in the resulting shaped material relative to the weight of the organic portion in the material, in one embodiment, at least 35% of the organic portion by weight should remain. In different embodiments, less than 49%, less than 34%, less than 24%, less than 14%, less than 9%, less than 4%, less than 2%, less than 0.4% of the organic portion by weight should remain, and even no organic portion may remain. In alternative embodiments, the percentages disclosed above are by volume and refer to the volume of the organic portion in the resulting shaped material relative to the volume of the organic portion in the material. In some other embodiments after consolidation, when considering the volume of organic matter in the resulting shaped material relative to the volume of organic matter in the material, in one embodiment, at least 35% organic matter by volume should remain. In different embodiments, less than 49%, less than 34%, less than 24%, less than 14%, less than 9%, less than 4%, less than 2%, less than 0.4% of the organic matter by volume should remain, and even no organic matter will remain. In alternative embodiments, the percentages disclosed above are by weight and refer to the weight of the organic matter in the resulting shaped material relative to the weight of the organic matter in the material. In some cases, the density of the molded material obtained by this method is greater than 96%, greater than 98%, and even greater than 99% of the theoretical density in different embodiments. The density of the resulting element is measured by Archimedes' principle according to American Society for Testing and Materials B962-08. All embodiments of this method can be combined if they are not mutually exclusive. Any embodiment disclosed in this document can be combined with this method in any combination provided and are not mutually exclusive. Methods 1 through 7 disclosed below are some examples of combinations of the method embodiments described in the last paragraph. Thus, any embodiment for any disclosed method step can be combined with any of Methods 1 through 7 in any combination provided and are not mutually exclusive. Furthermore, any other embodiment disclosed in this document can be combined with any of Methods 1 through 7 in any combination provided and are not mutually exclusive. Method 1 The method comprises the following steps: Step 1: Gather the materials Step 2: Use molding techniques to shape the material Step 3: The shaped material obtained in step 2 is subjected to a process involving a pressure greater than 55 MPa and a temperature greater than 0.45*Tm of the phase or element having the lowest melting temperature among the relevant elements / phases of the non-organic part of the material. Step 4: The shaped material obtained in step 3 is subjected to a debinding process, in which at least part of the organic portion is removed. Step 5: The formed material obtained in step 4 is subjected to a consolidation process. Thus, the resulting molded material has a residual organic fraction that is less than 49% by weight relative to the weight of the organic fraction in the material, and the resulting molded material has greater than 96% of the theoretical density. Method 2 The method comprises the following steps: Step 1: Take a material comprising an organic portion and an inorganic portion, wherein the organic portion comprises an associated element having a deflection temperature, measured in accordance with ACSTM D648-07 at a load of 0.46 MPa [66 psi], that is at least 22°C higher than 0.45*Tm of the phase or element having the lowest melting temperature among the associated elements / phases in the inorganic portion of the material, and wherein the inorganic portion comprises a metallic phase having at least 30% %Ga or %Li by weight with respect to the weight of such metallic phase, and where %Li and %Ga are less than 18% by weight with respect to the total weight of the metallic phase when all metallic phases (including intermetallic compounds) are considered. Step 2: Molding the material using polymer molding technology and optionally Step 3: The shaped material obtained in step 2 is subjected to a process involving a pressure greater than 0.6 MPa and a temperature greater than 0.46*Tm of the phase or element having the lowest melting temperature among the relevant elements / phases of the non-organic part of the material. Step 4: The shaped material obtained in step 2 or 3 is subjected to a consolidation process. Thus, the resulting shaped material has a residual organic portion that is less than 49% by weight relative to the weight of the organic portion in the material. Method 3 The method comprises the following steps: Step 1: Take a material comprising an organic portion and an inorganic portion, wherein the organic portion comprises associated elements having a deflection temperature, measured in accordance with ACSTM D648-07 at a load of 0.46 MPa [66 psi], that is at least 22°C higher than 0.45*Tm of the phase or element having the lowest melting temperature among the associated elements / phases in the inorganic portion of the material, and wherein the inorganic portion comprises metallic phases having a %Li of at least 56% by weight with respect to such metallic phases, and when all present metallic phases (including intermetallic compounds) are added together the %Li is less than 18% by weight with respect to the total weight of the metallic phases. Step 2: The material is shaped in an additive manufacturing process based on polymerization or curing by exposure to radiation where the material is cured at wavelengths of 460 nm or greater. Step 3: The shaped material obtained in step 2 is subjected to a process involving a pressure greater than 55 MPa and a temperature greater than 0.45*Tm of the phase or element having the lowest melting temperature among the relevant elements / phases of the non-organic part of the material. Step 4: The shaped material obtained in step 3 is subjected to a debinding process, in which at least part of the organic portion is removed. Step 5: The formed material obtained in step 4 is subjected to a consolidation process. Thus, the resulting shaped material has a residual organic fraction that is less than 49% by weight of the organic fraction in the material, and the resulting shaped material has greater than 96% of the theoretical density. Method 4 The method comprises the following steps: Step 1: Take a material comprising an organic portion and an inorganic portion, wherein the organic portion comprises an associated element having a deflection temperature, measured in accordance with ACSTM D648-07 at a load of 0.46 MPa [66 psi], that is at least 22°C higher than 0.45*Tm of the phase or element having the lowest melting temperature among the associated elements / phases in the inorganic portion of the material, and wherein the inorganic portion comprises one of the materials described in PCT / EP2016 / 076895. Step 2: The material is shaped in an additive manufacturing process based on polymerization or curing by exposure to radiation where the material is cured at wavelengths of 460 nm or greater. Step 3: The shaped material produced in step 2 is subjected to a process involving a pressure greater than 55 MPa and a temperature greater than 0.45*Tm of the phase or element having the lowest melting temperature among the relevant elements / phases of the non-organic part of the material. Step 4: The shaped material obtained in step 3 is subjected to a debinding process, in which at least part of the organic portion is removed. Step 5: The formed material obtained in step 4 is subjected to a consolidation process. Thus, the resulting shaped material has a residual organic portion that is less than 49% by weight relative to the weight of the organic portion in the material. Method 5 The method comprises the following steps: Step 1: Take the materials disclosed in this document Step 2: The material is molded using additive manufacturing, PIM (particle injection molding) or a similar process. Step 3: The material formed in step 2 is subjected to a process involving a pressure greater than 55 MPa and a temperature greater than 0.45*Tm of the phase or element having the lowest melting temperature among the relevant elements / phases of the non-organic part of the material. Test conditions for heat deflection temperature are disclosed at the end of this document. In one embodiment of Methods 1 through 5, when the percentage by weight of the remaining organic portion in the resulting shaped material is considered in terms of the weight of the organic portion in the material, in different embodiments, at least 35%, at least 45%, at least 56%, at least 66%, at least 76%, or at least 82% of the organic portion by weight should be retained. In some embodiments, even minor degradation of the organic portion should be prevented. In different embodiments, at least 86% of the organic portion by weight should be retained, at least 92%, at least 96%, at least 97%, and even at least 99% of the organic portion should be retained. In some other embodiments, after consolidation in Methods 1 through 5, when the volume of organic matter in the resulting shaped material is considered in relation to the volume of organic matter in the material, at least 35%, at least 45%, at least 56%, at least 66%, at least 76%, and even at least 82% of the organic matter by volume should be retained. In some embodiments, even minor degradation of the organic matter should be prevented. In various embodiments, at least 86%, at least 92%, at least 96%, at least 97%, and even at least 99% of the organic matter by volume should be retained. The density of the molded material obtained in this manner is greater than 96%, greater than 98%, and even greater than 99% of the theoretical density in different embodiments, with the density of the resulting element being measured by Archimedes' principle according to American Society for Testing and Materials B962-08. In alternative embodiments of methods 2 to 5, the heat deflection temperature of the relevant element in the organic portion of the material can be replaced in different embodiments by either the glass transition temperature, or degradation temperature, or melting temperature of such relevant element in the organic phase, and the same relationship should be satisfied with respect to the melting temperature of the phase or element with the lowest melting temperature among the relevant elements / phases in the inorganic portion of the material. Test conditions are disclosed at the end of this document. In Method 2, in different embodiments, the organic portion has associated elements that have a deflection temperature, measured according to ACSTM D648-07 at a load of 0.46 MPa [66 psi], that is at least 22°C above 0.52 times the melting temperature of the phase or element having the lowest melting temperature among the associated elements / phases in the inorganic portion of the material (at least 22°C above 0.52*Tm), at least 22°C above 0.76*Tm, and even at least 22°C above 0.82*Tm. The pressure applied in Step 3, if optional, is, in different embodiments, 1.1 MPa or greater, 2.1 MPa or greater, 11 MPa or greater, and / or 26 MPa or greater. In this method for molding an element after step 2, or in embodiments where step 3 is also applied, the melting temperature of the inorganic portion of the molded material after step 3 is at least 20%, at least 34%, at least 48%, at least 61%, and even at least 66% higher than the melting temperature of the metal phase of the material in different embodiments. In different embodiments, the molding technique used in step 2 is a polymer molding technique, metal injection molding (MIM), particle injection molding (PIM), injection molding, compression molding, thermoforming, or any other similar technique. In one embodiment, the metal phase comprises 56% %Li by weight relative to the weight of such metal phase. The inventors have discovered that the correct selection of particle size is very important in some embodiments. In different embodiments, particles having a D50 of less than 50 micrometers, less than 20 micrometers, and even less than 20 micrometers are desirable. Furthermore, in alternative embodiments, any other particle sizes disclosed herein can be combined within this method, provided they are not immiscible.In some embodiments, when carrying out this method 2, the inventors have surprisingly discovered that if step 3 or step 4 is applied, the melting temperature of the inorganic portion of the shaped material (the obtained shaped material) after step 2 or after step 3 or step 4 is increased compared to the melting temperature of the inorganic portion of the material (the inorganic portion of the material taken in step 1 before shaping), and the melting temperature of the inorganic portion of the obtained shaped material is in different embodiments 1.2 times or more, 1.4 times or more, 1.8 times or more, and even 2.1 times or more higher than the melting temperature of the inorganic portion of the material. In some embodiments, when carrying out this method 2, the inventors have surprisingly discovered that if step 3 or step 4 is applied, the melting temperature of the metal portion of the shaped material (obtained shaped material) after step 2 or after step 3 or step 4 increases compared to the melting temperature of the metal portion of the material (metal portion of the material taken in step 1 before shaping), and the melting temperature of the metal portion of the shaped material obtained is in different embodiments 1.2 times or more, 1.4 times or more, 1.8 times or more, and even 2.1 times or more higher than the melting temperature of the metal portion of the material. In Methods 3 and 4, materials that cure at wavelengths of 460 nm or greater refer to materials that respond well to such wavelengths. All embodiments of this method can be combined if they are not mutually exclusive. Some other examples of combinations of method embodiments can also be found in the following paragraphs. Method 6 The method comprises the following steps: Step 1: Take a material comprising an organic portion and an inorganic portion, the organic portion having an associated element with a deflection temperature measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi] at at least 120°C, and the inorganic portion having a metallic phase with a Tm less than 495°C. Step 2: Use molding techniques to shape the material Step 3: The shaped material produced in step 2 is subjected to a process simultaneously involving a pressure greater than 55 MPa and a temperature greater than 0.45*Tm of the phase or element having the lowest melting temperature among the relevant elements / phases of the non-organic part of the material. Method 7 The method comprises the following steps: Step 1: Take a material comprising an organic portion and an inorganic portion, the organic portion having an associated element with a deflection temperature measured in accordance with ACSTM D648-07 at a load of 0.46 MPa [66 psi] at at least 120°C, and the inorganic portion comprising a metallic phase as described in PCT / EP2016 / 076895. Step 2: Use molding techniques to shape the material Step 3: The shaped material obtained in step 2 is subjected to a process simultaneously involving a pressure greater than 55 MPa and a temperature greater than 0.45*Tm of the phase or element having the lowest melting temperature among the relevant elements / phases of the inorganic part of the material. Method 8 The method comprises the following steps: Step 1: Take a material comprising an organic portion and an inorganic portion, wherein the organic portion has an associated element having a deflection temperature measured in accordance with American Society for Testing and Materials D648-07 at a load of 0.46 MPa [66 psi] at at least 120°C, and the inorganic portion comprises a metallic phase having a %Li of at least 16% by weight relative to the weight of such metallic phase. Step 2: Use molding techniques to shape the material Step 3: The shaped material obtained in step 2 is subjected to a process involving a pressure greater than 55 MPa and a temperature greater than 0.45*Tm of the phase or element having the lowest melting temperature among the relevant elements / phases of the non-organic part of the material. Method 9 The method comprises the following steps: Step 1: Take a material comprising an organic portion and an inorganic portion, wherein the organic portion comprises an associated element having a deflection temperature, measured in accordance with ACSTM D648-07 at a load of 0.46 MPa [66 psi], that is at least 22°C higher than 0.45*Tm of the phase or element having the lowest melting temperature among the associated elements / phases in the inorganic portion of the material, and wherein the inorganic portion comprises a metallic phase having at least 30% by weight of %Ga or %Li, relative to the weight of such metallic phase, and when all metallic phases (including intermetallic compounds) present in the inorganic portion are considered, %Li and %Ga are less than 18% by weight relative to the total weight of the metallic phase. Step 2: Molding the material using polymer molding technology and optionally Step 3: The shaped material obtained in step 2 is subjected to a process involving a pressure greater than 0.6 MPa and a temperature greater than 0.46*Tm of the phase or element having the lowest melting temperature among the relevant elements / phases of the non-organic part of the material. Test conditions for heat deflection temperature are disclosed at the end of this document. In Methods 6, 7, 8, and 9, the percentage by weight of the remaining organic portion in the molded material is considered in terms of the weight of the organic portion within the material. In various embodiments, at least 35%, at least 45%, at least 56%, at least 66%, at least 76%, and even at least 82% of the organic portion by weight should be retained. In some embodiments, even minor degradation of the organic portion should be prevented. In various embodiments, at least 86%, at least 92%, at least 96%, at least 97%, and even at least 99% of the organic portion by weight should be retained. In alternative embodiments, the percentages disclosed above are by volume and refer to the volume of the organic portion within the resulting molded material relative to the volume of the organic portion within the material. In some other embodiments of Methods 6, 7, 8, and 9, after consolidation, the volume of the organic portion within the resulting shaped material is considered relative to the volume of the material. In various embodiments, at least 35%, at least 45%, at least 56%, at least 66%, at least 76%, and even at least 82% of the organic portion by volume should be retained. In some embodiments, even minor degradation of the organic portion should be prevented. In various embodiments, at least 86%, at least 92%, at least 96%, at least 97%, and even at least 99% of the organic portion by volume should be retained. In alternative embodiments, the percentages disclosed above are by weight and refer to the weight of the organic portion within the resulting shaped material relative to the weight of the organic portion within the material. In alternative embodiments of Methods 6 to 8, the heat deflection temperature of the relevant component of the material can be replaced in different embodiments by either the glass transition temperature, or degradation temperature, or melting temperature of such relevant component of the organic phase. In Method 9, in different embodiments, the organic portion has associated elements that have a deflection temperature, measured according to ACSTM D648-07 at a load of 0.46 MPa [66 psi], that is at least 22°C above 0.52 times the melting temperature of the phase or element having the lowest melting temperature among the associated elements / phases in the inorganic portion of the material (at least 22°C above 0.52*Tm), at least 22°C above 0.76*Tm, and even at least 22°C above 0.82*Tm. The applied pressure in Step 3, if optional, if applied, is, in different embodiments, 1.1 MPa or greater, 2.1 MPa or greater, 11 MPa or greater, and / or 26 MPa or greater. In this method for molding an element after step 2, or in embodiments where step 3 is also applied, the melting temperature of the inorganic part of the molded material after step 3 is in different embodiments at least 20%, at least 34%, at least 48%, at least 61%, and even at least 66% above the melting temperature of this metallic phase of the material. In different embodiments, the molding technique used in step 2 is a polymer molding technique, metal injection molding (MIM), particle injection molding (PIM), injection molding, compression molding, thermoforming, or any other similar technique. In one embodiment, the metallic phase comprises 56% %Li by weight relative to the weight of such metallic phase. The inventors have discovered that the correct selection of particle size is crucial in some embodiments. In different embodiments, particles having a D50 of less than 50 micrometers, less than 20 micrometers, and even less than 20 micrometers are desirable. Moreover, in alternative embodiments, any other particle sizes disclosed herein can be combined within this method, provided they are not immiscible. In some embodiments, when performing this method 9, the inventors have surprisingly discovered that, when step 3 is applied, the melting temperature of the inorganic portion of the shaped material (the resulting shaped material) increases after step 2 or after step 3 compared to the melting temperature of the inorganic portion of the material (the inorganic portion of the material taken in step 1 before shaping), and the melting temperature of the inorganic portion of the resulting shaped material is, in different embodiments, 1.2 times or more, 1.4 times or more, 1.8 times or more, and even 2.1 times or more higher than the melting temperature of the inorganic portion of the material. In some embodiments, when carrying out this method 9, the inventors have surprisingly discovered that when step 3 is applied, the melting temperature of the metal portion of the shaped material (the resulting shaped material) after step 2 or after step 3 is increased compared to the melting temperature of the metal portion of the material (the metal portion of the material taken in step 1 before shaping), and the melting temperature of the metal portion of the resulting shaped material is, in different embodiments, 1.2 times or more, 1.4 times or more, 1.8 times or more, and even 2.1 times or more higher than the melting temperature of the metal portion of the material. In alternative embodiments of method 9, the heat deflection temperature of the relevant element of the material can be replaced in different embodiments by either the glass transition temperature, or degradation temperature, or melting temperature of such relevant element of the organic phase, and the same relationship should be satisfied with respect to the melting temperature of the phase or element with the lowest melting temperature among the relevant elements / phases in the inorganic portion of the material. Some types of lattice structures achieve good mechanical strength, deformability, compliance, or any other relevant functional mechanical property, especially in normalized terms (property divided by the density of the lattice). Metal lattices achieve these highly normalized mechanical property values, in part because the metal arrangement is highly optimized, resulting in a very high air content in the total volume occupied by the material. Because air has a very low density, it strongly reduces the overall density. While the authors have discovered that most of the organic materials used have densities much higher than that of air, the inventors have found that functionality can be significantly improved, and the solution is surprisingly advantageous despite the increased weight. In one embodiment, this applies to the construction of elements using lattices made of materials with organic portions and inorganic portions comprising at least one metal or one metal alloy. In one embodiment, the lattice is a so-called superlattice. In one embodiment, the lattice is a three-dimensional repetition of a unit cell found in nature. In one embodiment, the lattice is any structure that can be multiplied by the repetition of a basic unit cell. In one embodiment, a lattice is a structure that can be expanded by more than 85% by repeating a basic unit cell. In one embodiment, a lattice is any structure that achieves normalized mechanical properties that are superior to those of a bulkier material with the same alloying and microstructure (normalized mechanical properties mean the mechanical properties divided by the density of the structure, where the volume does not account for voids within the material). In some embodiments, it is unique that the material comprises an organic portion and an inorganic portion comprising a metal alloy that is at least partially consolidated in a manner that comprises exposure to a temperature, but at least a relevant fraction of the organic portion does not significantly degrade (the meaning of temperature and relevant fraction and significant degradation can be found expressed in the same or equivalent terms elsewhere in this document). In many applications, it is beneficial in this aspect for the material to be capable of at least two states. One state is amenable to molding by additive manufacturing (AM) or traditional polymer material molding methods. In a second state, the material exhibits, in some embodiments, high mechanical properties and, in some embodiments, high resistance to high temperatures, etc. In this group of embodiments, one difference between the two states is the degree of aggregation or consolidation of the inorganic phase. In one embodiment, at least some of the inorganic phase is in the form of single particles in the original state, and at least some of these particles are aggregated or consolidated in the later state. In one embodiment, particle aggregation / consolidation involves the diffusion of atoms from one particle to another, in one embodiment involving diffusion bonding. In one embodiment, it involves the formation of a particle network through diffusion. In one embodiment, particle aggregation / consolidation is so strong that, when the organic portion is removed and the aggregated / consolidated particles are measured, the equivalent average diameter is, in different embodiments, at least 12 times larger, at least 110 times larger, at least 1100 times larger, and even at least 110,000 times larger than the D50 of the original particles. In an alternative embodiment, D50 can be replaced with D50m. In one group of embodiments, one difference between the two states is the glass transition temperature (Tg) of at least one organic phase. In a different embodiment, at least one of the organic components is selected from the group of organic components whose glass transition temperature (Tg) can be increased by 55°C or more, 105°C or more, 155°C or more, or 205°C or more when subjected to a transformation treatment (such as heat treatment, exposure to radiation, or chemical treatment). In one embodiment, the increase in glass transition temperature refers to the difference between the glass transition temperature of the organic component in its initial state and the glass transition temperature of the same organic material after being subjected to a transformation treatment, such as any of the methods and / or molding techniques disclosed herein or any other treatment that can be applied to the organic component, such as application of pressure and / or temperature. Test conditions for identifying the glass transition temperature can be found at the end of this document. For a group of embodiments, it is beneficial to have rod-shaped materials (filaments, wound wires, or other filaments) and filament-based additive manufacturing (AM) processes can benefit from such formats. This can be adapted to very large robotic structures for the fabrication of extremely large components. In different embodiments, the filaments have inorganic phases with length-to-equivalent-diameter ratios greater than 6, greater than 11, greater than 16, greater than 26, greater than 10, and even greater than 10. In one embodiment, the filaments or rod-shaped materials are stretched by mechanical action to promote alignment of the inorganic phases with high length-to-equivalent-diameter ratios. In one embodiment, the filaments or rod-shaped materials are stretched by mechanical action to promote elongation of the inorganic phases with high length-to-equivalent-diameter ratios. In one embodiment, the mechanically stretched filaments or rod-shaped materials comprise carbon nanotubes with high length-to-equivalent-diameter ratios. In one embodiment, the filaments or rod-shaped materials comprise fibers other than those already described (and therefore by appropriate definition) in this document. The materials described in this aspect are highly beneficial for the manufacture of elements by conventional manufacturing routes, especially if the majority of the organic portion is maintained and the inorganic particles have a high ratio of length to equivalent diameter, and even more so if the material comprises inorganic portions that are initially present as particles but undergo an aggregation / consolidation process. In one embodiment, the material is molded by particle injection molding (PIM) (metal injection molding (MIM) or ceramic injection molding (CIM)), and in one embodiment by known polymer material molding techniques. In one embodiment, the organic portion is largely retained in the manner defined above. One embodiment refers to a method in which the materials disclosed previously herein are formed by additive manufacturing (defined herein as a technique that applies additive manufacturing principles, thereby assembling a physical three-dimensional shape by the sequential addition of material per ACS for Testing and Materials 52900-15), specifically the method disclosed below is applied to a material that can be hardened when exposed to radiation, and the forming technique comprises exposing at least a portion of the material to such radiation. The method for shaping the material comprises the following steps. Step 1: Provide a material that will "harden" when exposed to "appropriate radiation." Step 2: Molding the material provided in step 1 using an additive manufacturing method comprising exposing at least a portion of the material to "suitable radiation." Step 3: Separate the cured or partially cured material from the uncured material. In one embodiment, "suitable radiation" refers to the proper radiation to cause such curing, the values of such radiation in different embodiments being disclosed later in this document. Any embodiment directed to materials previously disclosed in this document can be combined with any embodiment of this method, provided they are not immiscible. In one embodiment, the "hardening" material is a curable material. In one embodiment, the "hardening" material is a resin. In one embodiment, the resin is polymerizable upon exposure to radiation of interest (often referred to as a photopolymerizable resin). In one embodiment, the "hardening" material is a polymeric liquid comprising a monomer or a mixture of monomers and a photoinitiator that is sensitive to "appropriate radiation." In one embodiment, the "hardening" material is a polymeric liquid comprising a monomer or a mixture of monomers and a dye that is sensitive to "appropriate radiation." In different embodiments, the "hardening" material further comprises a reaction accelerator, a photochromic compound that can be sensitized when exposed to "appropriate radiation" (azobenzene, spiropyran, stilbene, fulgites, diarylethene, etc., as some examples), a chromophore that can generate heat when exposed to "appropriate radiation," and a thermal initiator. In one embodiment, the "hardening" material further comprises an element that affects the viscosity of the mixture. In one embodiment, the "hardening" material further comprises a minor amount of an element that reduces the viscosity of the mixture. In one embodiment, the reduced viscosity is dynamic viscosity. In one embodiment, the reduced viscosity is cinematic viscosity. In one embodiment, the reduced viscosity is absolute viscosity. In different embodiments, the minor amount of viscosity-reducing element is at 19% or less, 14% or less, 9% or less, 4% or less, 1.8% or less, 0.9% or less, and even 0.4% or less by volume relative to the volume of the organic portion of the material. In an alternative embodiment, the percentages disclosed above refer to the volume of the material. In an alternative embodiment, the percentages disclosed above are by weight. Whether it is a single element or multiple elements that reduce viscosity, a minor amount must be indicated. In different embodiments, the minor amount is at 0.1% or more, 0.6% or more, 1.1% or more, 2.1% or more, and even 5% or more by volume relative to the volume of the organic portion of the material. In an alternative embodiment, the percentages disclosed above are by weight.Reducing the viscosity of a mix means that a mix of all ingredients except the ingredients assigned to the viscosity reduction (and these ingredients are believed to have multiple functionalities in addition to reducing the viscosity of the mix, such as dispersing particulate loads, adding color, etc.) has a higher viscosity than the same mix when the viscosity-reducing ingredients are added. In different embodiments, the viscosity is reduced by at least 2%, at least 6%, at least 11%, at least 16%, at least 22%, at least 42%, at least 52%, and even at least 72%. Viscosity is measured according to ISO 3219:1993 (at room temperature of 23°C and 1 atmosphere). In one embodiment, the "hardening" material is a resin. In one embodiment, it is a resin that can be polymerized by exposure to "appropriate radiation" of interest. In a different embodiment, sufficient loading is achieved in the "hardening" material to achieve 12% or more, 16% or more, 22% or more, 36% or more, 42% or more, 52% or more, 62% or more, or 82% or more conversion, as measured using differential scanning calorimetry (DSC). In a different embodiment, the upper values of conversion are measured using differential scanning calorimetry (DSC) selectively according to the monomers and / or oligomers used according to the methods disclosed in DOI:10.1007 / s10853-005-5689-y, with the appropriate adjustments made according to the monomers and / or oligomers used, or further according to DOI:10.1007 / s10965-011-9811-3, with the appropriate adjustments made using Fourier transform infrared spectroscopy. In a different embodiment, sufficient loading is achieved to achieve 0.26 J / cm 2 More than 0.42J / cm 2 More than 0.94J / cm 2 Above, 1.72J / cm 2 Above, 3.6J / cm 2 Above, 5.2J / cm 2 Above, 16J / cm 2 Above, 26J / cm 2 or more, and an additional 56 J / cm 2 That's all. In this and subsequent related aspects, whether or not repeated in this paragraph, "suitable radiation" refers to radiation having a wavelength within a defined range. For some embodiments, a specified power density may also be included. The range for specifying "suitable radiation" depends on the application or embodiment selected. For some embodiments, a sufficiently high or low frequency is crucial. In various embodiments, "suitable radiation" has a frequency of 120 THz or less, 89 THz or less, 69 THz or less, 49 THz or less, 19 THz or less, 9 THz or less, 2.1 THz or less, and even 0.8 THz or less. In some embodiments, the frequency of "suitable radiation" should not be too low. In various embodiments, "suitable radiation" has a frequency of 0.2 THz or more, 1.1 THz or more, 11 THz or more, 21 THz or more, 56 THz or more, and even 102 THz or more. The use of this precise radiation (upper and lower limits) allows for unexpectedly fast curing, even in opaque suspensions. In one set of embodiments, "suitable radiation" is non-ionizing radiation. This greatly simplifies setup construction, as the harmful potential of the radiation is greatly reduced. In one embodiment, "suitable radiation" is coherent radiation, in one embodiment remaining coherent after penetration into the material, in one embodiment remaining coherent after penetration of 0.1 mm into the material (usually referring to the brightest point of the penetration distance, with the remaining coherence often interpreted as the relevant phase, maintaining a difference of at least 20% in the ratio value between the phases). In one embodiment, "suitable radiation" is free-propagating radiation, in one embodiment consisting of one or more discrete wavelengths, in one embodiment consisting of one discrete wavelength, and in one embodiment consisting of more than one but less than nine discrete wavelengths. The inventors have found this aspect to be highly beneficial for materials such as any of the materials previously disclosed herein, particularly those containing a high volume of particles within the material, and have discovered that for some applications, the arrangement of particles within the material can be highly detrimental to proper molding operation. In various embodiments, the material comprises 6% or more, 31% or more, 41% or more, 52% or more, 61% or more, 71% or more, and even 81% or more particles by volume relative to the volume of the material. In an alternative embodiment, the percentages disclosed above are by weight. In some applications, the volume content of particles should be controlled to allow for desirable conversion, and in various embodiments, the volume of particles is 89% or less, 84% or less, 79% or less, 69% or less, 59% or less, and even 39% or less by volume relative to the volume of the material. In an alternative embodiment, the percentages disclosed above are by weight. In some embodiments, these particles refer to the inorganic portion of the material. In some embodiments, it is the relative size of the cavities between the particles that is important. In various embodiments, the relative size of the interparticle voids is 980 micrometers or less, 480 micrometers or less, 180 micrometers or less, 80 micrometers or less, 40 micrometers or less, 19 micrometers or less, 9 micrometers or less, and even 0.9 micrometers or less. In various embodiments, the relative size of the interparticle voids is D50, D90, and even D10. In one embodiment, the relative size of the interparticle voids is the equivalent diameter of the average cavity between the particles volume of all interparticle voids. In some applications, the inventors have discovered that it is very important to properly select the wavelength of radiation to use as a function of the relative particle size. In various embodiments, the particle size is 0.98 times the wavelength or less, 0.88 times or less, 0.68 times or less, 0.58 times or less, 0.48 times or less, 0.28 times or less, 0.08 times or less, and even 0.008 times or less. In some embodiments, the size of the cavity is difficult to control, and it is better to control the minimum size of the particles (the maximum size specified as a function of the wavelength of the "suitable radiation" as already described above).In various embodiments, the minimum particle size should be 0.79 times or more, 0.68 times or more, 0.49 times or more, and even 0.18 times or more the maximum particle size. In some applications, the inventors have discovered that it is crucial to properly select the wavelength of radiation to use as a function of the relative particle size. In various embodiments, the relative size of the interparticle cavity is 0.98 times or less, 0.88 times or less, 0.68 times or less, 0.58 times or less, 0.48 times or less, 0.28 times or less, 0.08 times or less, and even 0.008 times or less the wavelength length. In one embodiment, the wavelength is selected to maximize the resonance effect. In one embodiment, the wavelength is selected to ensure the resonance effect is present. In various embodiments, the wavelength is selected between 400 and 2000 nm, between 2 and 600 micrometers, between 1.1 and 12 micrometers, between 5 and 100 micrometers, between 5 and 20 micrometers, and even between 20 and 600 micrometers. In one embodiment, the wavelength is selected to reach a resonance effect with the relative size of the particles. In one embodiment, the wavelength is selected to reach a resonance effect with the relative size of the cavities between the particles. In one embodiment, a magnetic field is applied. In one embodiment, if the particles comprise a ferromagnetic material, a magnetic field is applied. In one embodiment, a magnetic field is applied that is perpendicular to the direction of propagation of the relevant radiation. In one embodiment, a magnetic field is applied that is between 45° and 135° to the direction of propagation of the relevant radiation. In one embodiment, a magnetic field is applied that is parallel to the direction of propagation of the relevant radiation. In one embodiment, a magnetic field is applied that is between 30° and -30° to the direction of propagation of the relevant radiation. In one set of embodiments, it is crucial to have the correct ratio of particles and inter-particle voids (areas not filled with particles of material, often containing organic liquid material or any other non-solid material). In one embodiment, this ratio is the volume fraction of particles. In an alternative embodiment, this ratio is the weight fraction of particles. In an alternative embodiment, the value provided above for the volume fraction of particles is relative to this ratio. In different embodiments, the particles are selected to comprise a material having a specific heat of 0.3 J / (g*K) or more, 0.41 J / (g*K) or more, 0.64 J / (g*K) or more, 0.82 J / (g*K) or more, 0.96 J / (g*K) or more, or 1.1 J / (g*K) or more. In one embodiment, the specific heat values specified above refer to the average specific heat of all particles present in the material. The specific heat values are at room temperature (23°C). Test conditions are disclosed at the end of this document. In a different embodiment, the particles have a density of 1.1 J / (cm 3 *K) or more, 1.6J / (cm 3 *K) or more, 2.3J / (cm 3 *K) or more, 3.1J / (cm 3 *K) or more, 3.6J / (cm 3 *K) or more, and 4.1J / (cm 3 The material is selected to have a specific heat*density of equal to or greater than (*K), where the specific heat is at room temperature (23°C). In one embodiment, the density*specific heat value defined above refers to the average specific heat of all particles multiplied by the average density of all particles present in the material. Test conditions are disclosed at the end of this document. In one embodiment, the particles are selected to comprise a material with a parameter PTC value of 11 or greater. The parameter PTC is calculated by multiplying specific heat * density * thermal conductivity, where specific heat is defined in J / (g*K), density in g / cm3, and thermal conductivity in W / (m*K), and specific heat and thermal conductivity are at room temperature (23°C). In different embodiments, the particles are selected to comprise a material with a parameter PTC value of 21 or greater, 42 or greater, 62 or greater, 110 or greater, 160 or greater, and even 210 or greater. In an alternative embodiment, the PTC values defined above refer to the average of all particles present in the material. Test conditions are disclosed at the end of this document. In this manner, extremely fast polymerization rates are possible. This is quite surprising, since fast polymerization requires a strong input power into the material, and since polymerization is itself an exothermic reaction, it is even conceivable that the polymerized material may re-melt. Indeed, proceeding in this manner, surprisingly fast printing speeds can be used with organic moieties that undergo highly exothermic polymerization. In different embodiments, fast printing is defined as speeds of 110 cm 3 / h or more, 310cm 3 / h or more, 710cm 3 / h or more, 1100cm 3 / h or more, 1600cm 3 / h or more, and even 20,000 cm 3 / h or greater. In one embodiment, printing speed refers to the printing speed achieved with a single print head. In different embodiments, highly exothermic polymerization refers to a heat of polymerization of 3 Kcal / mol or greater, 6 Kcal / mol or greater, 11 Kcal / mol or greater, 16 Kcal / mol or greater, 21 Kcal / mol or greater, and even 31 Kcal / mol or greater. Polymerization rate is measured according to the method disclosed in Santos JC et al., 2008, "Comparison of techniques for the determination of conversion during suspension polymerization reactions," Braz. J. Chem. Eng., vol. 25 no. 2, Sano Paulo, April / June 2008 (doi.org / 10.1590 / S0104-66322008000200017). J. Chem. Eng. vol. 25 no. 2 Sano Paulo April / June 2008 (doi.org / 10.1590 / S0104‐66322008000200017). The heat of polymerization is determined by an isothermal upstream calorimeter as disclosed in Joshie RM, Polymer Chemistry and Physics, Vol. 62, No. 1; pp. 1–218...
Claims
1. 1. A method of forming a material, comprising the steps of: (1) obtaining a material; (2) forming the material using a molding technique; (3) subjecting the material formed in step (2) to a process comprising a pressure of more than 55 MPa and a temperature of more than 0.45×Tm, where Tm is the melting point of the phase or component having the lowest melting point among the relevant components or phases in the inorganic portion of the material; having In addition, if necessary, (4) subjecting the shaped material obtained in step (3) to a debinding process; (5) subjecting the shaped material obtained in step (3) or (4) to a solidification process; The method comprising:
2. 2. The method of claim 1, wherein the molding technique is selected from a polymer molding technique, a metal injection molding (MIM) technique, a particle injection molding (PIM) technique, an injection molding technique, a compression molding technique, a thermoforming technique, or an additive manufacturing technique.
3. 3. The method of claim 1 or 2, wherein the material collected in step (1) comprises an element in an amount of at least 1.2%, by weight of the material, having a melting point below 580°C.
4. 4. The method of claim 1, wherein the material harvested in step (1) has an organic portion comprising at least one component and an inorganic portion comprising at least one component.
5. the material harvested in step (1) having an organic portion comprising at least one component and an inorganic portion comprising at least one component; 5. The method of claim 1, wherein the organic portion of the component has a deflection temperature measured according to ASTM D648-07 test at a load of 0.46 MPa (66 psi) that is more than 0.45 times higher than the melting point of the corresponding component of the inorganic portion of the material.
6. 6. The method according to claim 1, wherein the inorganic portion of the material is at least 52% by weight relative to the weight of the material.
7. 7. The method according to claim 1, wherein after applying the method, less than 24% by volume of the organic moieties remains in the material.
8. 8. The method according to claim 1, wherein the density of the resulting shaped material is greater than 96% of the theoretical density.
Citation Information
Patent Citations
Low rare earth high strength magnesium lithium alloy and preparation method thereof
CN101787471A
Compressor bearing seat of gas turbine
CN104451305A
Rapidly degradable magnesium alloy material as well as manufacturing method and application thereof
CN104651691A
High-performance alkenyl magnesium alloy material and preparation method thereof
CN106319310A
Lightweight high-strength magnesium alloy
JP1994025788A